Genome-wide identification and functional validation of asparagine synthetase genes (NtASNs) in Nicotiana tabacum - Yan-Qun Zhang; Xin-Yao Huang; Wu-Xia Xi; Pei-Song Yang; Jia-Rong Wu; Jian-Cheng Wu; Shao-Ming Zhao; Hang Li; Rong Zhang; Shi-Ping Zhou; Wei-Guang Wang; Qiu-Fen Hu; et al. (Plant Science, 2026)

Leaching of scandium from a basalt weathering crust-type scandium deposit: An alkali-acid combined treatment method - Xiaorui Wang; Ruidong Yang; Wei Cheng; Rong Chen; Jun Chen; Xinzheng Li (Minerals Engineering, 2026)

Bacterial cellulose guided In-Situ growth of ZIF-8 toward hierarchical N-doped porous carbon for enhanced CO2 capture - Shijie Wang; Xudong Zheng; Sifan Bao; Zihuai Xu; Zhouzhou Yang; Wei Sun; Jinfeng Mei; Jian Rong; Zhongyu Li (Fuel, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Temperature-influenced deformation analysis of a full-scale steel-concrete-steel cable support tower model during construction - Zhi-Li Qi; Wei-Le Chen; Jian Li; Jian-Sheng Fan; Rong Xian; Fei Tian; Yu-Fei Liu (Engineering Structures, 2026)

Spiro-donor modified blue thermally activated delayed fluorescence emitters with high efficiency, narrowband emission, and excellent lysosomal targeting ability - Deli Li; Qingchao Liu; Ruizhe Xu; Wei Liu; Rong Hu; Wei Li; Shi-Jian Su; Ziyi Ge; Yuhua Tong (Chemical Engineering Journal, 2026)

Orders-of-magnitude reactivity enhancement in persulfate activation by curvature-dependent oxygenated carbon nanotubes - Xin Yang; Zhongyuan Guo; Pufan Wang; Justin Prabowo; Yangyang Wang; Jiaxiang Chen; Jiacheng Wu; Xinyi Huang; Yichen Feng; Chengli Rong; Fangzhou Liu; Hao Li; et al. (Chemical Engineering Journal, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Biochar promotes methane production from anaerobic digestion: Pore structure regulation and quantitative correlation assessment - Ze-Mu Li; Ai-Hua Li; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Spatiotemporal dynamics of PFAS ecological risk in major Chinese river networks: a data-driven assessment (2011–2024) - Letian Zhang; Wei Lin; Zhouyun Xie; Yewei Wang; Rong Wu; Jiaqi Yang; Nanyang Yu; Xiaodong Li; Jie Liang (Water Research, 2026)

Katian (Late Ordovician) bellerophontoids (Gastropoda) from the shallow-water carbonate succession of Qilian, Northwest China - Wen-Jie Li; Jia-Qi Song; Xin Wei; Yu-Chen Zhang; Rong-Chang Wu; Yong Wang; Peng Tang; Yi Wang; Ren-Bin Zhan (Palaeoworld, 2026)

The needs-solution-prototype-validation model: A feasibility study of nurse-led interdisciplinary collaboration in medical device innovation - Xiaodong Zhang; Fengli Wang; Aiying Gu; Haoyuan Li; Wei Wang; Yongchao Huo; Rong Xu; Yuanfeng Xue; Guohong Li; Yan Geng (Next Research, 2026)

TF2A ameliorates lipid metabolism in high fat diet mice as an oxidative derivative of EGCG with altered gut microbiota and hepatic transcriptomic profiles - Yiyun Zhang; Zongzhen Guo; Kefan Wei; Rong Li; Jiaqian Cao; Liang Zhao; Sujing Wu; Caili Feng; Qiliu Jiang; Yong Xue (Food Bioscience, 2026)

Flexural bandgap of a metaplate carrying zigzag beam-mass systems - Jung-San Chen; Jie-Sheng Zheng; Yi-Chen Wu; Song-Rong Lin; Wei-Chang Li; Bhisham Sharma; Chin-Han Yang; Yu-Kai Lin (Engineering Structures, 2026)

Biomimetic damping eutectic gels enabled by comonomer-regulated phase separation for motion-artifact-resistant bioelectrodes - Menghan Pi; Yichun Zhang; Zihe Liu; Wenhao Li; Min Li; Honglin Wu; Wei Cui; Rong Ran (Chemical Engineering Journal, 2026)

Molecular mechanisms of neutron irradiation damage in CL-20: A multiscale modeling approach from collision cascades to real-space defect mapping - Wei-Yi Li; Tao Wang; Rong Liu; Yu-Heng Li; Wan-Xiao Guo; Xi-Yao Yun; Yi-Lin Fang; Jin-Tao Wang; Ning Gao (Chemical Engineering Journal, 2026)

Toxicity-weighted source prioritization of PFAS and antibiotics in an urban watershed - Letian Zhang; Jiaqi Yang; Nanyang Yu; Hao Luo; Zhouyun Xie; Yewei Wang; Rong Wu; Wei Lin; Xiaodong Li; Jie Liang (Journal of Hazardous Materials, 2026)

Divergent responses of ecosystem water use efficiency to environmental drivers in arid versus humid regions - Hailing Li; Maohong Wei; Hongling Yang; Ya Hu; Shaokun Wang; Ping Yue; Xujun Ma; Fangwei Hao; Rong Ma; Xiaoan Zuo (Journal of Environmental Management, 2026)

Potential of RNAi targeting β-N-acetylglucosaminidase(NAG1)for controlling Dendroctonus valens LeConte (Coleoptera: Scolytidae) - Yue Sun; Qin Cao; Yong-Hao Nan; Yang-Nan Hou; Chun-Fang Qi; Ji-Gang Li; Jian-Rong Wei (Journal of Asia-Pacific Entomology, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Geomorphic filtering of pollen signals across a reef-to-basin transect and its implications for paleoenvironmental reconstruction in the Xisha archipelago, South China Sea - Jiani Chen; Sui Wan; Wei Li; Yi Zhong; Rong Xiang; Xiang Su; Chuanxiu Luo; Dizhu Cai (CATENA, 2026)

Heavy silicon isotope and mass-independent mercury isotope fractionation signals of Archean TTGs: Insights into the recycling of the silicified oceanic crust in the source region - Xiao Hu; Wenbin Zhu; Haizhen Wei; Runsheng Yin; Yongxiang Li; Yiwei Rong; Di Chen (Chemical Geology, 2026)

Botany, extraction methods, chemical constituents, pharmacological activities, and food applications of Stauntonia chinensis - Chen-Yu Chang; Xiao-Yun Wang; Ke-Jia Liu; Qi Li; Shu-Yan Lu; Qin-Ge Ma; Rong-Rui Wei (Natural Product Research, 2026)

Cinnamoylphenethyl amides from fissistigma bracteolatum and their anti-inflammatory activities - Jin-Feng Xue; Yao-Yao Jia; Jing-Wei Lei; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhen-Zhu Zhao; Dong-Rong Zhu; Guo-Sheng Li; Gui-Min Xue (Natural Product Research, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Cenozoic evolution of the Yangtze River, China: Constraints from quantitative detrital zircon UPb provenance modeling - Qiqi Song; Jie Hu; Zhiwu Li; Shengbiao Hu; Rong Tang; Chenghao Wei; Tianyao Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

An innovative immobilization-free homogeneous electrochemical strategy facilitated by buoyancy -magnetism separation for evaluating the acetamiprid in food - Ya-Rong Xie; Yue-Han Wang; Jia-Le Wang; Li-Ping Jia; Wei Zhang; Lei Shang; Xiao-Jian Li; Qing-Wang Xue; Huai-Sheng Wang; Rong-Na Ma (Food Chemistry, 2026)

Mechanistic insights into triclocarban-induced skin barrier disruption via integrating imaging localization, multi-omics, and network toxicology - Jingwen Zheng; Run Guo; Rong Zhang; Xinyu Liu; Rouyue Guo; Haozheng Li; Juntong Wei; Yuxin Zheng; Hongna Zhang (Environmental Pollution, 2026)

Impacts of urban open space environments on residents' health: A perspective on potentially toxic metals in dust - Yue Zeng; Qiang Ban; Junjie Yu; Changchun Qiu; Yajie Jiang; Xinyu Liu; Dian Lin; Shiqi Yan; Yunqin Li; Binxin Wu; Wei Yu; Rong Yu (Environmental Pollution, 2026)

Differential Enrichment of Deep Shale Gas in Southeastern Sichuan Basin: Dynamic Evolution and Preservation Mechanisms - Ke Zhang; Haikuan Nie; Songhang Zhang; Tianwu Xu; Zhujiang Liu; Chuanxiang Sun; Chengxiang Wan; Wei Dang; Pei Li; Jia Rong; Shuheng Tang (Journal of Earth Science, 2026)

Additive effects of heat and volatile organic compounds co-exposure on metabolic syndrome: evidence from petrochemical workers in China - Minhua Li; Rui Xu; Yilin Zhang; Shanshan Du; Rong Xu; Qing Zu; Zihu Lv; Wei Zheng; Weimin Ye; Jianjun Xiang (International Archives of Occupational and Environmental Health, 2026)

Three new diterpenoids from the aerial parts of Callicarpa macrophylla - Liang Gou; Rong-Shuai Li; Jian-Lin Lai; Yan-Mei Ning; Xue-Ting Ji; Xiong Qiu; Chao Peng; Xiao-Li Li; Xing-Jie Zhang; Wei-Lie Xiao (Natural Product Research, 2026)

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

Study on the anti-inflammatory effects of active ingredients in Vespa velutina auraria Smith - Ming-Rong Li; Xiu-Qin Pang; Chao-He Liu; Wei Zhang; Heng Liu; Hai-Rong Zhao; Zhi-Bin Yang; Yan Wang; Yi-Hao Che; Huai Xiao (Natural Product Research, 2026)

Corrigendum to “Progress in the application of Salmonella vaccines in poultry: A mini review” [Vet. Immunol. Immunopathol. 278(2024), 110855] - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2026)

Non-stationary dynamic responses during continuous load transfer process of float-over installation: Experimental and numerical investigations - Yuhao Wei; Shuqing Wang; Xiancang Song; Gen Rong; Xiang Li; Yiyuan Yang (Ocean Engineering, 2026)

Organic fertilizer substitution combined with Bacillus velezensis SQR9 inoculation reduces carbon footprint and enhances net eco-economic benefits in tropical vegetable fields - Wei Tian; Huacheng Yin; Ziheng Zou; Rong Li; Yawen Huang; Jinyang Wang; Shuwei Liu; Zhaoqiang Han; Jianwen Zou (Journal of Environmental Management, 2026)

Mussel-inspired surface modification for high-rate and effectively complex wastewater systems purification - Minrui Zhan; Xi Zhang; Rong Liu; Manman Zhao; Wenkai Li; Huiyu Yang; Jiehao Du; Wei Chen; Shaojin Gu; Xin Liu; Bin Shang (Desalination, 2026)

An approach for detecting hemodynamic parameters in the carotid arterial system based on the priori relationship between blood pressure and arterial radius - Jin Wang; Yong-Jiang Li; Yu-Yuan Zhang; Jing-Rui Gu; Xian-Wei Wang; Dong Chen; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2026)

Cerebellar Contributions to Cognitive Affective Function and Postural Tremor in Neurological Wilson’s Disease - Ping Jin; Dong-xu Yin; Yu-xie Huang; Zi-wen Li; Xin-feng Ma; Kang Lin; Ya-yun Xu; Wei-ming Gao; Qun-rong Ye; Yong-zhu Han; Gong-qiang Wang (The Cerebellum, 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Crotiglianoids A−M, tigliane-type diterpenoids from the seeds of Croton tiglium and their anti-hepatic fibrosis activity - Guang-Hai Zhu; Zhen-Zhou Han; Rong Huang; Li-Fen Ma; Xin-Yi Hu; Fei-Yu Zhang; Yi-Ling Liao; Lu Gan; De-an Guo; Wei Li (Phytochemistry, 2026)

A novel phytoformula targeting lipid peroxidation inhibition attenuates UV-induced skin photoaging - Ling-Ping Wu; Wei Chen; Qian-Pei Lin; Shi-Yun Feng; Jin Dai; Qiong-Yi Zhang; Wen-Yi Chen; Hiroshi Kurihara; Xiao-Min Li; Shu-Hua Ouyang; Yi-Fang Li; Rong-Rong He (PharmaNutrition, 2026)

Indole metabolites produced by Lactobacillus acidophilus impedes bisphenol F- aryl hydrocarbon receptor interaction and ameliorates bisphenol F induced depression-like changes - Miaoyang Hu; Ayiguzaili Manglike; Xiaozhu Li; Jin Wei; Xinyu Lou; Jing Liu; Zhiru Tang; Weiping He; Guixiang Ji; Wenjuan Wang; Tengfei Ma; Rong Gao; et al. (Journal of Hazardous Materials, 2026)

Proanthocyanidin/laccase-mediated cross-linking enhances the structural stability and rheological properties of collagen solutions - Junhong Xie; Li Feng; Fanghui Deng; Wei Yue; Wei Liang; Qiannan Zhao; Wentao Ma; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2026)

Green derivative synchronous fluorescence spectroscopy approach for rapid quantification of Rhodamine B in food samples - Hong-Jun Liu; Jia-Rong He; Yi-Han Guo; Jia-Lin Li; Wei-Peng Cai; Ping-Ping Wu; Yao-Qun Li (Food Control, 2026)

Dual-configuration arabinogalactan-II synergizes with rhamnogalacturonan-I in Lycium barbarum pectin to construct an intestinal anti-inflammatory glycan scaffold - Guoqiang Li; Yajun Qiao; Qiannan Wang; Xingfang Zhang; Lin Rong; Lixin Wei; Tingting Gao; Hongtao Bi (Carbohydrate Polymers, 2026)

Depth-coupling pattern between forest soil microorganisms and carbon mineralization in southwestern China - Shuang Ding; Shengzhao Wei; Honghong Lin; Li Rong; Enwei Zhang; Xue Yang; Huanxu Lv; Xingwu Duan (CATENA, 2026)

Novel Method for Preparing Pseudo-Male Common Carp by Inducing Secondary Female-to-Male Sex Reversal Under High Temperature Conditions - Yulai Wei; Yi Rong; Kuangxin Chen; Yongming Li; Yanlong Song; Binbin Tao; Ji Chen; Wei Hu (Marine Biotechnology, 2026)

Hormonally and chemically induced male-to-female sex reversal is independent of Y-chromosome number in common carp - Kuangxin Chen; Yuanqi Guo; Yi Rong; Zhaoxian Li; Mouyan Jiang; Rui Li; Xiya Zhang; Yongming Li; Yulai Wei; Yanlong Song; Ji Chen; Binbin Tao; et al. (Aquaculture, 2026)

A multicomponent Fc-fused subunit vaccine induces cross-protective immunity against porcine reproductive and respiratory syndrome virus QYYZ-like and NADC30-like strains - Linxing Tian; Zhengdan Lin; Mengxi Pan; Yanwen Wen; Mingxing Lu; Shudan Liu; Chao Zhang; Zhenxiang Rong; Jiahui Ma; Ruiqu Zhou; Nan Cao; Xinghua Chen; et al. (Veterinary Microbiology, 2026)

HGS+ enlarged vesicular compartments serve as the sites for coronavirus assembly at later infection stage - Xubing Long; Buyun Tian; Rongrong Chen; Rong Bai; Jinping Yang; Yushuang Fang; Xinyue Fu; Yanhong Xue; Wei Ji; Tao Xu; Zonghong Li (Science Bulletin, 2026)

Brain gray matter atrophy in adult population with cognitive impairment due to chronic cadmium exposure - Zhentao Gao; Longtao Yang; Rong Ma; Xiaoying Li; Fang Pei; Wei Hu; Yixuan Wu; Xiaojiang Tang; Jun Liu (NeuroToxicology, 2026)

Molecular epidemiology reveals co-circulation of five Anaplasma species with zoonotic potential in sheep and goats from Henan province, China - Jia-Run Yang; Wei-Hao Tan; Jie-Yue Liang; Jing-Rong Li; Yu-Ru Cao; Wan-Yu Li; Jian-Wei Shao (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Non-volumetric phase transition of PNIPAM enables high-sensitivity temperature monitoring and photoelectric therapy for wound care - Jie Ding; Danni Hou; Yuan Tian; Rong Li; Yuyan Wang; Junzhong Jiang; Yucai Hu; Chengheng Wu; Dan Wei; Jing Sun; Zi Qiao; Hongsong Fan (Chemical Engineering Journal, 2026)

From the perspective of resource recovery: Electrochemical treatment technology system for heavy metal complex wastewater - Rong Wang; Chenyang Zhang; Junyi Li; Wei Sun (Chemical Engineering Journal, 2026)

Aluminum modulation of cobalt states in perovskite for higher alcohols synthesis from syngas - Pengfei Song; Rong Liu; Zihan Shen; Yuwei Zhang; Xijun Li; Chenxi Zhang; Fei Wei; Yuan Liu; Chuan Wang; Zhichuan J. Xu (Chemical Engineering Journal, 2026)

Investigating the synergistic role of dual solid additives in morphology engineering and photogenerated charge dynamics for high-efficiency all-polymer solar cells - Liping Zhou; Tengxiang Gao; Shuonan Li; Wei Zhang; Rong Hu (Chemical Engineering Journal, 2026)

Nanoscale insights into the immobilization of coexisting As(V) and Cd(II) during Fe(II)-driven ferrihydrite transformation - Wei Li; Zhuohao Wu; Yang Lu; Rong Li; Qianying Sun; Zheng Liang; Wencheng Wu; Zhenqing Shi (Chemical Geology, 2026)

Insights to how tubular pore biochar affects anaerobic digestion of waste activated sludge: Performances and mechanisms - Ze-Mu Li; Ai-Hua Li; Qing-Bin Meng; Cong-Cong Tang; Qian Li; Ai-Juan Zhou; Wenzong Liu; Zhi-Ling Li; Zhang-Wei He; Rong Chen (Bioresource Technology, 2026)

Evaluation of protein and metabolic engineering strategies on (−)-α-bisabolol production by Escherichia coli - Jiayi Ma; Rong Fang; Xiaoyuan Yue; Hui Jiang; Qixuan Kong; Tiankuo Jiang; Jiale Yu; Chang Zhou; Yuanyuan Xia; Wei Shen; Haili Liu; Yaqin Shen; et al. (Systems Microbiology and Biomanufacturing, 2026)

Mechanisms by Which Humic Acid Reduces Copper Toxicity in Citrus Roots Based on Omics and Physiology - Wei-Tao Huang; Rong-Rong Xie; Liang-Yuan Tong; Tian-Tian Xia; Jiuxin Guo; Ning-Wei Lai; Zeng-Rong Huang; Lin-Tong Yang; Li-Song Chen (Journal of Plant Growth Regulation, 2026)

ANKFN1 in skin fibroblasts may modulate mast cell activity and is associated with dupilumab response in atopic dermatitis - Qiu-ju Wei; Jia-rong Lu; Wan-yan Xiang; Hai-qi Liang; Si-qi Zhang; Si-yu Huang; Jun-wen Peng; Ze-feng Zhou; Qiu-ju Li; Wen-jun Zheng (Immunologic Research, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

The causal relationship between polycystic ovary syndrome and structural changes in brain: a Mendelian randomization study - Han Yang; Wei Xie; Camilo Alberto Pinzon Galvis; Si Huang; Xu He; Si-yi Yu; Qing You; Fan-rong Liang; Zhi-yong Xiao; Ning Li (Brain Imaging and Behavior, 2026)

Climate resilience of grain production in China: measurement, dynamic evolution, and spatial spillover effects - Mingliang Li; Rong Kong; Jiyu Wei; Yuanyuan Xiong; Guoxin Yu (Environment, Development and Sustainability, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

Erosion obliges fungi to maintain community diversity through stochastic processes - Shuang DING; Shengzhao WEI; Li RONG; Xingwu DUAN (Pedosphere, 2026)

Impact of organic carbon composition on bacterial community assembly in organic and mineral soil layers under phosphorus addition in a Robinia pseudoacacia plantation - Ahejiang SAILIKE; Yujie LIANG; Rong FU; Hongjian HAO; Rong WANG; Ning PENG; Shicai LI; Zhouchang YU; Fangxin ZHENG; Wei ZHANG; Yangyang LIU; Peizhi YANG; et al. (Pedosphere, 2026)

High-CH4-selectivity CO2 photoreduction enabled by in-situ constructed S-scheme Cs2CuCl4/NiAl-LDH heterojunction - Hai-bing Zhao; Yue Shu; Sheng-ning Zeng; Wen-rong Ouyang; Duo-fu Li; Hong Zhong; Wei Huang; Yan Sui (Journal of Environmental Chemical Engineering, 2026)

Research progress on the structure of edible fungi polysaccharides and their anti-obesity mechanisms via the regulation of intestinal microbiota and metabolites - Xin Wei; Weiya Rong; Liyang Jin; Limin Zhang; Daoqin Ren; Yue Jiang; Jinling Cao; Shaojun Yun; Feier Cheng; Wenfei Zhao; Yong Li; Mingchang Chang; et al. (Food Bioscience, 2026)

Nitrogen doped graphene quantum dots modified a crystalline zinc phosphite based non-enzymatic electrochemical sensor for the ultra-low detection of tyramine - Pi-Chen Wei; Asit Kumar Panda; Yu-Chung Chang; Yi-Rong Li; Todd Hsu; Chih-Min Wang (Food Control, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Stage-specific ion release from dual-crosslinked alginate/boron-doped bioactive glass hydrogel accelerates infected wound healing - Fuqiang Song; Linyuan Jiang; Anqi Ye; Rong Huang; Anwen Lai; Longyang Xu; Wei Shen; Junjun Li; Jiayan Hui; Andi Suo; Yanzhi Xiong; Xiaoyu Dong; et al. (Carbohydrate Polymers, 2026)

Therapeutic effects of Gardenia jasminoides Ellis on salpingitis in laying hens: mechanisms of inflammatory regulation and egg quality improvement - Ruo-Yi Zhang; Hua-Lin Peng; Wei Zhang; Rong-Qiang Li; Hong-Jie Cui; Jian Li (Veterinary Research Communications, 2026)

Development and validation of a copolymerized thiol-silica based DGT technique for the assessment of bioavailable As(Ⅲ) speciation - Yue Zeng; Zhennan Liu; Yajie Jiang; Yunqin Li; Wei Yu; Rong Yu; Xiang Xu; Meiling Xiao (Environmental Geochemistry and Health, 2026)

Crop rotation benefits for nitrogen-oxide mitigation and soil health in tropical vegetable fields - Wei Tian; Feilong Liang; Rong Li; Jinyang Wang; Shuwei Liu; Zhaoqiang Han; Jianwen Zou (Agriculture, Ecosystems & Environment, 2026)

Silencing NRBP1 Gene with shRNA Improves Cognitive Function and Pathological Features in AD Rat Model - Xinxue Wei; Xiaobei Liu; Yunqing Ban; Jing Li; Rong Huang (Biochemical Genetics, 2026)

Chronic heat stress attenuates innate immunity and increases susceptibility to Aeromonas hydrophila in Siberian sturgeon (Acipenser baerii) - Xiaowen Wang; Huijuan Li; Rong Zhang; Lili Liu; Wei Wang; Hua Zhu (Aquaculture International, 2026)

SVA virus-like vesicle vaccine based on VEEV-VSVG vector elicits efficient immune responses and protection in swine - Zhenxiang Rong; Mingjin Jiao; Nan Cao; Mingxing Lu; Shudan Liu; Chao Zhang; Liuqing Wei; Yamei Li; Huanchun Chen; Xiangmin Li; Ping Qian (Veterinary Microbiology, 2026)

Pharmacotranscriptomics-based discovery and hydrogel-mediated delivery of drug combinations for potentiated cancer immunotherapy - Rong Liu; Hui-Han Yu; Wei-Rong Li; Jia-Si Wu; Jing-Yang Zhang; Jia-Qi Luo; Yu Pang; Ying Chen; Yan-Dan Yao; Run Lin; Ling Wang; Jin-Zhi Du; et al. (Science Bulletin, 2026)

cGAS-STING activation mediated by FAM83H-AS1/HMGB1 elicits NF-κB-dependent immune evasion in breast cancer - Zhi-Mei Liang; Lili Lin; Shu-Rong Li; Xin-Yu Ma; Wenda Zhang; Na-Na Li; Zheng-Hao Lai; Guorun Liang; Wei Zhao; Yiming Zhao; Man-Li Luo (Science Bulletin, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

New mechanistic insights into the antiviral candidate CA-P: Activation of plant redox-mediated defense and suppression of virus biosynthesis - Rong-Shuang Luo; Yan-Wei Huang; Yu-Cheng Gu; Long Cheng; Wu-Bin Shao; Yan-Mei Liao; Qian Guo; Dan Zeng; Hong-Mei Xiang; Xiang Zhou; Li-Wei Liu; Zhi-Bing Wu; et al. (Pesticide Biochemistry and Physiology, 2026)

Effect of structural characteristics of highland barley β-glucan by various thermal processing methods on intestinal microbial community and fermentative products - Rong Li; Ji Gao; Yiyun Zhang; Zijian Dai; Siqi Li; Tong Wu; Jiaqian Cao; Kefan Wei; Chao Wang; Qun Shen; Yong Xue (Food Bioscience, 2026)

One stone, two birds: Preparation of nutritionally fortified and easy-to-swallow 3D printed pea protein gel based on high internal phase emulsions - Wei Liang; Junhong Xie; Qiannan Zhao; Chenghong Jiang; Xiaofeng Zhan; Mingrong Chen; Lu Zhang; Chuan Li; Jianhua Rong; Yang Hu (Food Hydrocolloids, 2026)

Clostridium dalinum: A Novel Lactic Acid Bacterium with Excellent Antioxidant and Anti-inflammatory Functions Through NF-κB, Keap1-Nrf2-ARE Signaling Pathways - Zheng-Qiang Li; Rui Li; Wei Deng; Rui An; Ping Ma; Jun Li; Rong She; Xiao-Yan Yang; Xu Yang; Wen Xiao (Probiotics and Antimicrobial Proteins, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Unique ecological functions of viral communities potentially influence microbial adaptability in deep-sea ferromanganese nodule deposits - Yu-Kang Li; Ge-Yi Fu; Zhen Rong; Jun-Qing Chen; Zhi-Hao Ding; Zu-Xin Zhang; Hua-Hua Jian; Wen-Sheng Shu; Yue-Hong Wu; Xue-Wei Xu (Journal of Hazardous Materials, 2026)

How human-perceived urban green spaces contribute to mental well-being: a machine learning approach - Enqi Cheng; Yuejing Rong; Yan Yan; Chenxing Wang; Lijie Wang; Yu Zhao; Zetong Wang; Wei Li (Journal of Environmental Management, 2026)

Unlocking a new application of coal and biomass co-ethanolysis: high-performance supercapacitor based on N/O self-doped hierarchical porous carbons - Li Li; Yu-Fan Ren; Chang-Wang Shao; Long-Yu Zhang; Guo-Rong Qi; Xing-Shun Cong; Xian-Yong Wei; Zi-Chun Fan; Xiao-Yu Zhang (Fuel, 2026)

Amine modified porous carbon aerogel templated by the natural structure of wood for CO2 capture and selective separation - Zhouzhou Yang; Xudong Zheng; Zihuai Xu; Sifan Bao; Wei Sun; Shijie Wang; Jinfeng Mei; Jian Rong; Zhongyu Li (Fuel, 2026)

Bionic cellulose fiber-based columnar solar evaporator with interfacial regulation for superfast water purification - Ying Qian; Zhexuan Lan; Shunfang Wen; Rong Liu; Haifeng Zhang; Ruiqing Li; Du Nie; Seeram Ramakrishna; Wei Zhang; Jiamu Dai (Desalination, 2026)

Boosting surface basicity of In2O3 aerogel for high-performance H2S sensors via an in-situ annealing strategy of carbon-composited In(OH)3 - Zheng Yang; Qian Rong; Wei Zhang; Qi Xu; Mengen Shao; Jiang Li; Chunchang Wang; Youmin Guo (Chemical Engineering Journal, 2026)

Ion−dipole−induced high stability of acidic DESs for efficient extractive and oxidative desulfurization - Dongao Zhu; Jie Yin; Siyi Han; Rong Zhang; Chunyan Dai; Jing He; Hongping Li; Wenshuai Zhu; Huaming Li; Wei Jiang (Chemical Engineering Journal, 2026)

Decomplexation for resource recovery from heavy metal complex wastewater: mechanisms, challenges, and future roadmaps - Rong Wang; Chenyang Zhang; Shujuan Zhang; Wei Sun; Wenzhang Li (Chemical Engineering Journal, 2026)

Phthalocyanine-based prodrug with H₂S-triggered domino cascade for photodynamic and multiple-mechanism synergistic anti-metastatic therapy - Mengyu Yao; Qi-Qi Yang; Huang-Hao Tang; Xue-Yan Li; Wei Xie; Chao Wang; Song Yang; Xingshu Li; Mei-Rong Ke; Jian-Dong Huang (Chemical Engineering Journal, 2026)

Novel 2-aminothiazole derivatives incorporating 9-alkyl purine moiety: design, synthesis, crystal structure, and bioactivity evaluation - Song Bai; Suran Wan; Miao Li; Rong Wu; Shouying Tang; Fang Wang; Lijun Chen; Xiaokang Lv; Xian Wei; Shuang Feng; Miaohe Zhang (Molecular Diversity, 2026)

Everything is everywhere, but everywhere is different: evidence from the phylogeography of asexual bdelloid rotifer Rotaria rotatoria species complex - Lingyun Zhu; Rong Huang; Sen Feng; Fan Gao; Meng Li; Hairong Lian; Zhizhong Li; Xinfeng Cheng; Mingbo Yin; Wei Zhang; Yilong Xi; Xianling Xiang (Hydrobiologia, 2026)

Fabrics of forsterite in CBa chondrite Sierra Gorda 013 - Rong Li; Wei Chen; Chun-Hui Li (Acta Geochimica, 2026)

Three new species of Scleroderma from Southern China - Ling Li; Hua Qu; Rong-Qian Bi; Rui Wu; Hai-Jiao Li; Zai-Wei Ge (Mycological Progress, 2026)

Field-free topological spin textures enable spin selectivity for spin light-emitting diodes - Yongping Wei; Shuo Cao; Chenhao Zhang; Xinran Wang; Sihao Ren; Hongshu Li; Yi Yang; Jiangpeng Zhou; Mingyu Chen; Shiming Wu; Weisheng Zhao; Xichao Zhang; et al. (Science Bulletin, 2026)

Efficient low-temperature NO reduction via constructing Cu+ −O−Co3+ sites to enhance lattice oxygen release and CO adsorption - He Wang; Ye Zhu; Wei Wang; Xiaoqing Dang; Yufei Zhang; Dandan Zhu; Rong Li; Dongjie Yan; Qian Ma; Jiaxin Qu; Jiaquan Zhang; Yu Huang (Journal of Hazardous Materials, 2026)

Plantation type regulates molecular characteristics and chlorine reactivity of soil-derived DOM: Enhanced DBPs formation in legume plantations - Xin-Yi Jiao; Su-Ping Liu; Cai-Shan Wang; Ying-Zhi Ding; Shuang Peng; Zi-Hao Wu; Yan-Chao Jin; Peng Liu; Ding Pan; Xue-Rong Wang; Dong-Bin Wei; Xin-Hui Liu; et al. (Journal of Hazardous Materials, 2026)

Development of green low-carbon denitrogenation process for EAF- reaction behavior and industrial performance of Ar-CH4 injection via hollow electrode - Xin Li; Guangsheng Wei; Ting Li; Shufeng Ye; Rong Zhu (Journal of Cleaner Production, 2026)

Green Intelligent Fertilizer derived from yellow phosphorus slag boosts rice yield and mitigate environmental impacts in high-altitude watersheds - Suoqian Kang; Ou Yu; Shuntao Zhang; Yujiao Tan; Rui Wang; Xueli Du; Jun Cao; Zhong Duan; Fei Huang; Rong Li; Changzhou Wei; Jiujiang Xu (Field Crops Research, 2026)

The low R = d/d high-entropy strategy enables high-performance sodium layered oxide cathode materials - Jun-Jie Liao; Min Wen; Wei-Wei Yuan; Qi-Lin Zheng; Kang Chen; Fu-Sheng Zhou; Zhen-Xin Qiu; Su-Yun Wang; Li-Li Wang; Lituo Zheng; Yiyin Huang; Jia-Xin Li; et al. (Chemical Engineering Journal, 2026)

Synchronously interfacial fire retardancy and mechanical strengthening of glass fiber nylon 6 by temperature-responsive coupling agent - Han Li; Zhi Li; Rong Kuai; Wei-Zheng Zhang; Yanhao Huang; Qing-Wen Zeng; Zhi Hu; De-Yi Wang (Chemical Engineering Journal, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

Phytochemistry, pharmacology and bibliometrics insight of the genus Callicarpa L.: an extensive review encompassing the years from approximately 2010 to 2024 - Wang Jiang; Si-Rong Huang; Wen-Jie Ma; Yi-Qiu Yi; Ping Li; Zhong-Hui Ma; Zhi-Wei Su (Phytochemistry Reviews, 2026)

Quercetin Alleviates Postoperative Cognitive Dysfunction of Aged Mice by Regulating Microglial Polarization through Inducing miR-379-5p RNA Modification - Shu Rong Li; Long Wang; Yi Wei Li; Yi Xiao Li; Ren Wei Li; Zhi Fang Zhuo; Qing Hua Wu (Molecular Neurobiology, 2026)

Transcriptomics and Experiments Verified that Astaxanthin Reduces the Apoptosis of Nerve Cells in Ischemic Stroke by Inhibiting the Toll-like Receptor Signaling Pathway - Shan Gao; Jinjian Li; Yuetong Zhao; Zhen Wei; Chunshu Rong; Kuiyang Zuo; Xu Wang; Dexi Zhao (Molecular Neurobiology, 2026)

Cu–N4 active site sensing platform for point-of-care colorimetric detection of environmental organophosphorus pesticide - Rong Huang; Zhong Dong; Wanyi Zhang; Zhenggang Xue; Dongmei Deng; Wei Wang; Yuanyuan Li; Haibo He; Liqiang Luo (Analytica Chimica Acta, 2026)

SREBP2 confers ferroptosis resistance by targeting GPX4 in colorectal cancer - Huage Zhong; Ruiqi Chen; Tianyu Chen; Min Lin; Siqi Wen; Man Zhang; Dejun Liu; Junfeng Yu; Jinchi Chen; Bei Yi; Rong Liang; Wei Jiang; et al. (Apoptosis, 2026)

Cloning, heterologus expression and characterization of a thermophilic and salt tolerant GH11 xylanase from Allostreptomyces psammosilenae YIM DR4008T - Xin-Wei Li; Dan Zhu; Lei Li; Run-Feng Yang; Shi-Yuan Fan; Zhi-Hua Lv; Meng-Di Rao; Rong-Huang Song; Peng Sang; Yi-Rui Yin; Li-Quan Yang (Antonie van Leeuwenhoek, 2026)

Ferroptosis at the intersection of radiotherapy and immunotherapy - Gui-Xia Wei; Ya-Qin Zhao; Rong Tang; Hua-Shan Shi; Zhi-Ping Li (Cancer and Metastasis Reviews, 2025)

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Rainfall, seasonal variation, and stream type governing the multi-media fate and ecological risks of tire additives and their transformation products in mega-urban streams - Li-Ni Wei; Nian-Nian Wu; Ru Xu; Yuan Liu; Shan Liu; Hai-Yan Zhang; Zi-Tong Li; Yue-Hong Liu; Xiang-Rong Xu; Jian-Liang Zhao; Guang-Guo Ying (Water Research, 2025)

Integrating the neuro-immune-cancer axis into CAR-T cell therapy: advances and challenges - Yi-Jin Li; Rong Shen; Wei-Li Zhao (Science Bulletin, 2025)

One new rearranged pyranone derivative with antibacterial activity from Xylaria curta YSJ-5 - Shan-Shan Wei; Dao-Jun Rong; Jia-Ying Lai; Chen Chen; Si-Ran Li; Zhong-Hua Yu; Hai-Bo Tan (Phytochemistry Letters, 2025)

Influence of multiple environmental factors on plastics in facility agriculture soils at a national scale, China - Guiming Liu; Sashuang Rong; Cun Liang; Yang Yang; Xuyang Zheng; Shutao Wang; Shiming Su; Zhenyong Li; Wei Liu (Journal of Environmental Chemical Engineering, 2025)

Unravelling the migration of bioactive and volatile compounds coupled with water sublimation from grapes to recovered water during dynamic freeze-drying - Mengru Li; Wei Zhang; Yuan Huang; Xiaoying Zhang; Wuernisha Kadeer; Leihong Mao; Yuqian Jiang; Rong Tsao; Yao Tang (Food Chemistry, 2025)

Development and validation of a magnetic - based corrosion detection system for reinforced concrete structures - Jian Cheng; Yu-meng Xie; Rong-sen Gao; Ye Tian; Guo-yi Zhang; Dongming Yan; Bo Chen; Ruo-yi Zhao; Bei Li; Jun Chen; Dong-yang Cai; Wei-qiang Wu; et al. (Engineering Structures, 2025)

Imidazole-modified separator for uniform polysulfide anchoring and accelerated redox in Li S batteries - Xiangwei Zhao; Qin Dong; Wei Hong; Rong Li; Xinglong Gou; Ruiyi Gan; Tao Wang; Cunpu Li (Chemical Engineering Journal, 2025)

Langmuir/BET ratio as a quantitative indicator: Chain length-dependent adsorption modes of fillers regulating ion transport and high-voltage performance in PEO-based composite electrolytes - Ding Nan; Altan Bolag; Rong Zhang; Ji Qi; Bila Ga; Tana Bao; Wei Li; Lei Li (Chemical Engineering Journal, 2025)

Effects of Optimized Nitrogen Fertilizer Application on Chlorophyll Fluorescence Characteristics and Dry Matter Accumulation in Sugar Beet - Shi-Feng Dong; Lei Wei; Xing-Bo Tong; Yi-Na Zhang; Rong-Li Jia; Xu-Ming Xing; Shu-De Shi (Sugar Tech, 2025)

Satb2 Ablation Impairs Hippocampus-Based Long-Term Spatial Memory and Short-Term Working Memory and Immediate Early Genes (IEGs)-Mediated Hippocampal Synaptic Plasticity - Ying Li; Qiang-Long You; Sheng-Rong Zhang; Wei-Yuan Huang; Wen-Jun Zou; Wei Jie; Shu-Ji Li; Ji-Hong Liu; Chuang-Ye Lv; Jin Cong; Yu-Ying Hu; Tian-Ming Gao; et al. (Molecular Neurobiology, 2025)

IFNGR1, IRF8 genetic polymorphisms modulate the susceptibility of non-tuberculous mycobacteria pulmonary disease and influence the patients’ treatment outcomes and immune status - Li-ping Cheng; Zhi-bin Liu; Lei Wang; Jie Cao; Qing-rong Qu; Hai Lou; Xiao-na Shen; Juan Yang; Yuanyuan Yu; Rui Juan Zheng; Wei Sha; Qin Sun (Inflammation Research, 2025)

Acute systemic inflammation induces region-specific morphological remodeling of astrocytes and microglia concurrent with depression-like behavior - An-Qi Zhang; Meng-Meng Zhang; Ling-Jie Li; Mei-Xue Yuan; Rong-Yu Liu; Peng Chen; Chen-Wei Wang; Yu Wang; Jiang-Ning Zhou; Qing-Hong Shan; Xin-Ya Qin (Histochemistry and Cell Biology, 2025)

WISP2/CCN5 revealed as a potential diagnostic biomarker for endometriosis based on machine learning and single-cell transcriptomic analysis - Sheng Dou; Shaohua Ling; Weihua Nong; Bixiao Wei; Yuehua Huang; Guangjing Li; Rong Wang; Haimei Qin (Functional & Integrative Genomics, 2025)

High-Resolution Three-Pressure Prediction of Lianggaoshan Formation in LT1 Well block of Eastern Sichuan Risk Exploration Area - Yu-wei Wang; Ke-zhen Wan; Rong-rong Zhao; Wen-hao Li; Yang Lin; Hao Long; Hu Zhao (Applied Geophysics, 2025)

Application of ambient noise tomography to coastal granite islands: A case study of Wuzhizhou Island in Hainan, China - Cheng Huang; Sheng Liu; Jun-Qiao Long; Chang-Rong Zhang; Bo Xiao; Da-Cheng Wang; Cheng-Long Wei; Rui Wang; Li Yan; Xuan Hu; Zhuo Xin; Xiu-Ji Meng; et al. (Applied Geophysics, 2025)

Limonoids and protolimonoid from Swietenia macrophylla - Yun-Peng Sun; Wen-Fang Jin; Ze-Rong Xu; Ying-Wei Liu; Li-Juan Sun; Yang Yu; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

Carbon stabilization by iron plaque on rice roots: The role of oxygen loss - Liang Wei; Xuechi Rong; Hongzhao Yuan; Yongfu Li; Xiaorong Fan; Ning Ling; Zhenke Zhu; Bahar S. Razavi; Yakov Kuzyakov; Pil Joo Kim; Jianping Chen; Tida Ge (Soil Biology and Biochemistry, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

A BrDof2.4-BrHDA6 module is involved in ABA-CTK-mediating leaf yellowing in Chinese flowering cabbage by affecting histone H3 and H4 acetylation of CCGs - Zhen-liang Mou; Lei Yan; Zong-li Liu; Xin-guo Su; Ze-xiang Zeng; Yuan Rong; Wei Shan; Jian-fei Kuang; Wang-jin Lu; Jian-ye Chen; Wei Wei; Jia Si (Postharvest Biology and Technology, 2025)

Scandium enrichment in the weathering crust of Emeishan basalt, Dali: geochemical abundance, occurrence states, and pre-concentration potential - Xiaorui Wang; Ruidong Yang; Wei Cheng; Rong Chen; Jun Chen; Xinzheng Li (Minerals Engineering, 2025)

Carbohydrate-metabolizing gastrointestinal bacteria mediate resistome divergence in high feed efficiency Holstein dairy calves - Tianyu Chen; Shangru Li; Jianxin Xiao; Rong Peng; Mo Sha; Jingjun Wang; Jiaying Ma; Wei Wang; Mei Ma; Shengli Li; Zhijun Cao; Shuai Liu (Journal of Hazardous Materials, 2025)

Hydrothermal carbonization: A potent strategy for simultaneously eliminating ARGs-associated pollutants in livestock manure and blocking ARGs horizontal gene transfer - Sunlin Chi; Jinmei Xiao; Jinying Xu; Aijing Li; Jianhui Hu; Xinyi Wang; Meiyan Zhang; Wei Liu; Yalan Zhang; Huijun Ding; Jun Rong; Li Leng; et al. (Journal of Hazardous Materials, 2025)

Residue carbon and C-degradation gene indicated the increase of soil organic carbon following vegetation restoration on the Loess Plateau, China - Rong Wang; Shicai Li; Yixian Ruan; Runhao Shi; Hongjian Hao; Yujie Liang; Ahejiang Sailike; Zhouchang Yu; Rong Fu; Ning Peng; Xinhui Han; Wei Zhang; et al. (Journal of Environmental Management, 2025)

A biodegradable cellulose-based ionic conductor for sustainable and high-safety quasi-solid-state sodium batteries - Yuejing Zeng; Rong Tang; Minghui Chen; Yaqi Zhang; Wei Li; Huiya Yang; Ruilai Ye; Xue Li; Yang Yang; Jinbao Zhao (Chemical Engineering Journal, 2025)

Crystal facet optimization in cadmium sulfide/reduced graphene oxide-based photosynthetic biohybrid systems for enhanced light-driven biohydrogen production - Xue-Meng Wang; Zhi-Xuan Zhang; Lin Chen; Rong Chen; Wen-Wei Li (Bioresource Technology, 2025)

ZxSAUR15 regulates root growth and abiotic stress tolerance: from genome-wide characterization of SAUR genes in Zygophyllum xanthoxylum to functional validation - Chunli Liu; Mengzhan Li; Yuting Yang; Rong Chai; Li Wei; Hongju Yin (Plant and Soil, 2025)

The potential role of hydrogen sulfide-autophagy axis in diseases - Ti Chu; Yan-Wen Wang; Lei Cao; Xue-Li Wang; Yong-Qi Fan; Yu-Hang Chen; Yi Zhang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Journal of Physiology and Biochemistry, 2025)

Three new triterpenoids from the fruit of Eleutherococcus senticosus (Rupr.) Harms - Yan Liu; Yu-Xuan Lin; Xiao-Hui Rong; Meng-Meng Li; Juan Pan; Wei Guan; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2025)

Decoupled motion planning method for 7-DOF manipulator and lifting joint in automated tomato harvesting - Jiacheng Rong; Yu Liu; Xianjun Li; Chao Gao; Pengbo Wang; Ting Yuan; Wei Li (Computers and Electronics in Agriculture, 2025)

Carbon dots promote tomato growth and yield via photosynthesis enhancement and leaf senescence delay - Shuang Li; Wenbo Zhao; Wei Zhao; Zhen Jiao; Keqiao Cui; Rong Wang; Aiying Wang; Yuantao Tan; Huandong Li; Yue Yin; Feijuan Gao; Kaikai Liu; et al. (Journal of Plant Physiology, 2025)

Deep eutectic solvent-mediated green synthesis of phosphorylated biomass adsorbents for high-efficient uranium removal from uranium tailings wastewater - Ya Wei Yang; Jie Liu; Jing Huang; Cheng Rong Zhang; Sai Jin Xiao; Xin Xin Shao; Han Wu; Li Zhang (Journal of Environmental Chemical Engineering, 2025)

Interfacial regulation of natural magnetite for oil-water separation in oily petrochemical wastewaters - Rong Wang; Jiarui Du; Junyi Li; Chenyang Zhang; Wei Sun (Journal of Environmental Chemical Engineering, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

DPP-IV inhibitory peptides from highland barley via machine learning and multi-scale validation - Xin Bao; Yiyun Zhang; Liyang Wang; Zijian Dai; Rong Li; Kefan Wei; Jiaqian Cao; Qingyu Zhao; Qun Shen; Yong Xue (Food Chemistry, 2025)

A ZnO packaged MEMS hydrogen sensor for reliable SIBO breath analysis with anti-H2S interference - Zheng Yang; Qian Rong; Wei Zhang; Xintao Fan; Mengen Shao; Jiang Li; Chunchang Wang; Youmin Guo (Chemical Engineering Journal, 2025)

Residual polyacrylamide-induced membrane fouling in short-flow coagulation-ultrafiltration: Behavior and mechanism - Mohan Wei; Yaozhong Zhang; Xing Zheng; Chi Zhang; Jiheng Duan; Kai Guo; Menghan Wang; Dongfei Li; Tianshuo Huang; Rong Chen (Chemical Engineering Journal, 2025)

The development of biological soil crusts shifts the drivers of soil multifunctionality in drylands - Mingming Wang; Boyi Song; Benfeng Yin; Ye Tao; Jing Zhang; Xiaoying Rong; Yonggang Li; Shihang Zhang; Zihan Kan; Yongxing Lu; Hao Guo; Xing Guo; et al. (CATENA, 2025)

Construction of LncRNA-miRNA-mRNA regulatory network in IgA nephropathy mice model by RNA-sequencing and bioinformatics analysis - Wen Jia Zheng; Tao Liu; Xiao Li Zhu; Yu Ting Zhang; Liang Bing Wei; Ya Chen Gao; Xing Xing Zhuang; Jia Rong Gao (Genes & Genomics, 2025)

One-pot construction of monodisperse core-shell silica microsphere with quinine-containing hybrid fibrous shell for racemates separation - Chenyang Wang; Tiantian Guo; Rong Li; Shujuan Ma; Yinmao Wei; Junjie Ou (Analytica Chimica Acta, 2025)

Targeting cuproptosis in liver cancer: Molecular mechanisms and therapeutic implications - Yun-Fei Zhou; Yi-Wen Zhu; Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Yan-Ge Li; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

Elucidation of the anti-fibrotic diseases mechanism of chelerythrine by integrative approach of network pharmacology and experimental verification - Wei Han; Gui-yun Qian; Qin-rong Wang; Jie Liu; Yong-ping Zhang; Jian Xu; Tingting Li; Zhe Li (Natural Product Research, 2025)

In vitro physiological and biochemical responses underlying salt tolerance of five turfgrass species - Zhen-Peng Wei; Yu-Ping Xiong; Jaime A. Teixeira da Silva; Jian-Rong Li; Jun-Yu Liu; Yuan Li; Zhan Bian; Xin-Hua Zhang; Guo-Hua Ma (Vegetos, 2025)

Biogenic Cu2-xSe nanoparticles with vacancy engineering quickly upcycle cobalt from wastewater for photothermal antibacterial and desalination - Xue-Meng Wang; Zhi-Xuan Zhang; Yun-Jie Wang; Hao-Yu Li; Wen-Wei Li; Rong Chen (Water Research, 2025)

Regulatory mechanism of microplastics on arsenic bioavailability in a subtropical estuary, China - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Rong Yu; Wei Yu; Binxin Wu; Meiling Xiao (Science of The Total Environment, 2025)

Ten eudesmane sesquiterpenoids from Dobinea delavayi and their antimalarial and lipid-lowering activities - Wei Chen; Li-Tian Dong; Pei-Mi He; Wei-Juan Zu; Yi-Ling Yang; Rong Liu; Bei Jiang; Chao-Jiang Xiao (Phytochemistry, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

Complete genome of Thalassotalea piscium NK451B, an Antarctic bacterium with abundant extracellular proteases - Jia-Yi Song; Zi-Ying Li; Xiao-Hui Yang; Jin-Rong Wei; Kang Li; Yi Zhang (Marine Genomics, 2025)

Evaluation of probiotic properties of lactic acid bacteria and physicochemical characteristics of fermented jujube (Ziziphus jujuba Mill.) polysaccharides - Rong Wang; Shufan Xie; Fei Li; Lanjian Qin; Jianming Ye; Jiaqi Chen; Xiao Yang; Yunlu Wei (Food Bioscience, 2025)

Synergistic electrostatic, coordination, and redox mechanisms in cationic covalent organic frameworks for ultrafast and selective gold recovery - Meng-Yao Zhou; Xiu Wang; Shun-Hao Zeng; Qian-Qian Zhao; Yibao Li; Wei-Rong Cui (Chemical Engineering Journal, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

Cloning and Bioinformatics Analysis of the StGRAS46 Gene in Potato - Shulin Wang; GuoHong Weng; Rong Zhang; Wei Li; YongJie Bai; YaHui Zhang; JianWu Li (Potato Research, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

Genetic diversity and population structure of four Trapa species from the Yangtze River and Amur River basins, China - Miriam Chepkwemoi Tengwer; Godfrey Kinyori Wagutu; Henry Kariuki Njeri; Wei Li; Yuan-Yuan Chen; Xiang-Rong Fan (Aquatic Botany, 2025)

Front margin tectonic deformation characteristics of the Xu–Su arc tectonic belt and its tectonic implications - Rong-ying Zheng; Yun-sheng Yao; Jun Shen; Hao-yuan He; Chun-shan Guo; Xiao-hui Yu; Xun-ye Dai; Lu-wei Li; Xuan-kai Jiao; Zhong-yuan Yu; Zhi-tao Gao (Applied Geophysics, 2025)

Two new steroidal saponins from the roots and rhizomes of Helleborus thibetanus - Hao Wei; Xin Zhang; Chao Ding; Yuze Li; Ziqiang Wang; Xiaomei Song; Dongdong Zhang; Rong Lin (Natural Product Research, 2025)

An end-to-end maturity prediction and hierarchical counting method for cherry tomatoes - Jiacheng Rong; Xianjun Li; Wanli Zheng; Tongqiang Chen; Ting Yuan; Pengbo Wang; Wei Li (Biosystems Engineering, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

3,4-seco-Prenyllabdane sesterterpenoids and 3,4-seco-labdane diterpenoids with Zika virus inhibitory potential from Callicarpa nudiflora - Xue-Wen Wu; Guan-Rong Qiao; Xue-Rong Zhao; Qi Li; Muhammad Aurang Zeb; Xiao-Li Li; Chang-Bo Zheng; Wei-Lie Xiao (Phytochemistry, 2025)

Elimination of antibiotic resistance genes and adaptive response of Firmicutes during chicken manure composting - Wei-Li Jia; Ben Wang; Lu-Kai Qiao; Fang-Zhou Gao; Wang-Rong Liu; Liang-Ying He; Guang-Guo Ying (Journal of Hazardous Materials, 2025)

All-weather highly efficient degradation of persistent organic pollutants over RhB-sensitized BiOCl under natural sunlight - Wen Sun; Chunping Su; Wei Zhang; Hui Li; Huiping Zhao; Rong Chen (Journal of Environmental Chemical Engineering, 2025)

Molecular characterization and expression analysis of IL-21 and its four receptor genes in yellow catfish (Pelteobagrus fulvidraco) in response to Edwardsiella ictaluri infection - Zhang-Ping Li; Xin-Xin Jiang; Zi-Rui Tang; Mao-Mao Dong; Ping Jiang; Gui-Rong Zhang; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2025)

A novel multi-dimensional viscoelastic mitigation device: Shake table tests and numerical assessment of precast concrete sandwich wall panel structure - Jia-Xuan He; Zhao-Dong Xu; Zhong-Wei Hu; Lian-Yu Zhang; Qiang-Qiang Li; Yao-Rong Dong; Gabriele Milani (Engineering Structures, 2025)

Surface engineering of copper peroxide nanodots and Au nanozyme on porphyrin-based metal-organic frameworks induces cascade reactions for colorectal cancer treatment - Haoyu Chen; Rong Liu; Jiaxin Fu; Xiaohan Zhang; Xiaohua Zhu; Mingjie Wei; Feng Liu; Peng Yin; Haitao Li; Youyu Zhang; Meiling Liu; Juewen Liu (Chemical Engineering Journal, 2025)

Protective effect of cartilage oligomeric matrix protein (COMP) on osteoarthritis-like chondrocytes based on the nuclear factor kappa B (NF-κB) pathway - Wei Weng; Rong Wu; Zhenguo Sun; Haidong Li; Yuxin Shen; Heng Li; Jikang Min (Journal of Molecular Histology, 2025)

Exploring morphological heterogeneity of circulating tumor cells: machine learning-based approach for cell identification and prognostic implications - Peng-Xiang Wang; Yu-Chen Zhong; Bin Duan; Jian-Wen Cheng; Yun-Fan Sun; Wen-Jing Zheng; Kai-Qian Zhou; Yang Xu; Hai-Xiang Peng; Wei-Xiang Jin; Hai-Min Li; Xiao-Juan Sun; et al. (Science Bulletin, 2025)

PtBi nanocatalysts with controlled chain-like structure and composition: Solvothermal synthesis and ethanol oxidation performance - Luo-Yi Yan; Han-Tao Zhang; Xiao-Yu Lu; Li-Ming Liu; Rong-Hua Zhang; Zheng Cheng; Shuai-Wei Fan; Xin-Wen Zhou (Fuel, 2025)

Reductive dechlorination of 1,1,2-trichloroethane in groundwater by zero valent iron coupled with biostimulation under sulfate stress: Differences and potential mechanisms - Naijin Wu; Yi Li; Yizhou Liu; Yangfan Feng; Wenbo Fei; Tianwen Zheng; Liming Rong; Nan Luo; Yun Song; Wenxia Wei; Peizhong Li (Environmental Research, 2025)

Rapid and efficient nitrogen removal by a novel heterotrophic nitrification-aerobic denitrification bacteria Marinobacterium maritimum 5-JS in aquaculture wastewater: Performance and potential applications - Fu-Rong Wang; Shi-Yu Feng; Shuai Liang; Wei-Yu Du; Long-Qi Wang; Yu-Wei Zhang; Jia-Yu Ren; Shuang Gao; Yu-Jie Zhu; Yu-Ting Cong; Li Wang; Jing Gu; et al. (Environmental Research, 2025)

Seismic behavior of CFST components for shear walls using double corrugated steel plates - Xu Liao; Xian Li; Wei Li; Rong Su; Ming Chen (Engineering Structures, 2025)

A green-solvent processed multifunctional bamboo composite with high strength, robust fire retardancy, and dimensional stability - Xiangyu Ren; Huijun Zhang; Weibing Xue; Tongda Liu; Rong Liu; Xin Ran; Ping Wang; Wei Gao; Yanmei Li; Guanben Du; Long Yang (Chemical Engineering Journal, 2025)

Collaborative mechanism of microbial fuel cell native bacteria and Sporosarcina pasteurii: Improving mineralization performance - Jin-Di Liu; Wei-Min Cheng; Xiang-Ming Hu; Xiao Li; Yue Feng; Yan-Yun Zhao; Ming-Yue Wu; Hui Rong; Xiao-Niu Yu; Yin-Bo Xiang; Zhi-Rong Zhang (Chemical Engineering Journal, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

Anthropogenic Influence on the Compound Hot and Dry Event in Summer 2022 in the Tibetan Plateau Based on Statistical Downscaling CMIP6 Models - Kening Xue; Wei Li; Siyan Dong; Rong Yu; Leibin Wang (International Journal of Climatology, 2025)
In the summer of 2022, the Tibetan Plateau experienced a record‐breaking compound hot and dry event (CHDE). This study quantifies the contribution of anthropogenic influence to this compound event using a set of high‐resolution statistical downscaling results from six CMIP6 models. The Copula function was used to calculate the joint probability of the compound event. The results show that in the summer of 2022, hot conditions in the Tibetan Plateau broke records since 1961, with a return period of 408 years. The dry conditions were also uncommon, with a return period of 47 years. The hot and dry compound event is particularly rare, with a return period of more than 20,000 years. Based on the results from statistical downscaling models, it was found that anthropogenic influence has increased the risks of dry and hot conditions similar to those in the Tibetan Plateau in 2022 by factors of 3.3 [1.5, 5.2] and 14 [8.6, 21.2], respectively. Additionally, the risk of compound events has been increased by a factor of 46.7 [26.7, 77.6]. In the future, with the intensification of warm‐wet situations on the Tibetan Plateau, the hot conditions similar to 2022 are expected to increase remarkably, with the risk of occurrence rising by factors of 56 [34, 108] and 75 [44, 162] during the periods 2021–2040 and 2051–2070, respectively. Conversely, dry conditions are projected to decrease, with reductions of 0.21 [0.075, 0.46] and 0.51 [0.3, 1.2] times in the two future periods. However, the risk of compound events is expected to increase, with increases of 3.3 [1.5, 5.2] times and 11 [6, 25] times during the two periods. This study is the first to use downscaled simulation to conduct event attribution analysis for the Tibetan Plateau, which can deepen the understanding of the influence of human activities on compound events.

Molecular Insight Into the Hydrolysis of Phthalate Esters by a Family IV Esterase - Zhen Rong; Li‐Guo Hong; Ying‐Yi Huo; Jixi Li; Dao‐Qiong Zheng; Yang Ha; Jeffrey Fan; Xue‐Wei Xu; Yue‐Hong Wu (Environmental Microbiology, 2025)
Phthalate esters (PAEs) are prevalent environmental contaminants, with their biodegradation efficiently driven by microorganisms through ester bond hydrolysis. This study investigates the mechanism of Poc14, a novel family IV esterase, using x‐ray crystallography, bioinformatics, biochemistry and site‐directed mutagenesis. Phylogenetic analysis classifies Poc14 as a family IV esterase with conserved catalytic motifs crucial for its activity. Poc14 retains over 80% activity at 50°C for 4 h and tolerates up to 5% methanol or DMF, though surfactants like Tweens inhibit its function. Poc14 activity is independent of metal ions, and the addition of EDTA further enhances its activity by approximately 130%. The 1.8 Å crystal structure reveals a CAP domain and two substrate channels. Enzyme assays show Poc14 hydrolyses short‐chain diethyl phthalate (DEP) ( K m = 0.068 mM, V max = 9975 μM/min/mg) but not long‐chain di(2‐ethylhexyl) phthalate (DEHP) due to steric hindrance. Molecular docking assessed Poc14's potential to hydrolyse DEP and DEHP after residue mutations, resulting in the Poc14‐AAG variant. Poc14‐AAG could hydrolyse one bond of DEHP and diester bonds of DEP. Our study positions Poc14 as a promising enzyme for environmental remediation, with potential for optimising DEHP degradation and exploring dimerisation effects.

Active spermatogenesis in YY supermale common carp makes it suitable for potential control of this invasive species - Kuangxin Chen; Yi Rong; Yuanqi Guo; Mouyan Jiang; Yulai Wei; Xishuang Shan; Yongming Li; Yanlong Song; Ji Chen; Binbin Tao; Wei Hu (Aquaculture, 2025)

Investigation of antibacterial activity and mechanism of action: Design and synthesis of coumarin derivatives containing sulfonamide groups - Song Bai; Miaohe Zhang; Miao Li; Suran Wan; Fang Wang; Shouyin Tang; Lijun Chen; Xian Wei; Rong Wu (Phytochemistry Letters, 2025)

Size-dependent internalization of polystyrene microplastics as a key factor in macrophages and systemic toxicity - Wei-Qiang Luo; Meng-Ting Cao; Chen-Xuan Sun; Jun-Jian Wang; Meng-Xi Gao; Xue-Rui He; Le-Ning Dang; Yang-Yang Geng; Bing-Yao Li; Jing Li; Zhi-Cheng Shi; Xing-Rong Yan (Journal of Hazardous Materials, 2025)

Climate warming will alter the impact of microplastics on the bioavailability of arsenic in a subtropical estuary - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Wei Yu; Rong Yu (Journal of Hazardous Materials, 2025)

The food application of a novel Staphylococcus aureus bacteriophage vB_SA_STAP152 and its endolysin LysP152 with high enzymatic activity under cold temperature - Yuanyu Li; Jingsha Dai; Shi Wu; Dongli Rong; Jiahui Huang; Miao Zhao; Jumei Zhang; Qinghua Ye; Qihui Gu; Youxiong Zhang; Xianhu Wei; Qingping Wu (Food Microbiology, 2025)

Nectar characteristics and pollination ecology of Camellia perpetua in South China - Hai-du Jiang; Dan-juan Zeng; Hui-zhen Qin; Li-hui Peng; Yi-shan Yang; Zong-you Chen; Rong Zou; Jian-min Tang; Yun-sheng Jiang; Zhong-chen Xiong; Xiao Wei; Sheng-feng Chai (Flora, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Microwave-assisted pyrolysis of spent bleaching clay: A study of pyrolysis characteristics, kinetics, and intrinsic mechanism - Bang Yao; Li Chao; Yingwen Zhang; Yang Liu; Chunbao Zhou; Dekai Fan; Yunxiang Li; Pengfei Zhu; Wei Li; Yanran Lin; Lei Gao; Chen Chen; et al. (Chemical Engineering Journal, 2025)

Development of Agro-Based Engineered Biochars for Low Concentration Nitrate Adsorption: Modification Selection, Performance, Factors, Mechanism, and Reliability - Wenjia Han; Ai Chen; Zhuocan Li; Rong Zhou; Kai Zhang; Wei Zhao; Xiaotao Bi; Xiali Zhang (Water, Air, & Soil Pollution, 2025)

Glymphatic Impairment Associated with Neurocognitive Dysfunction in Moyamoya Disease - Chaofan Zeng; Yuanren Zhai; Peicong Ge; Chenglong Liu; Xiaofan Yu; Wei Liu; Junsheng Li; Qiheng He; Xingju Liu; Xun Ye; Qian Zhang; Rong Wang; et al. (Translational Stroke Research, 2025)

Identification and validation of mitochondrial endoplasmic reticulum membrane-related genes in atherosclerosis - Li-Rong Wang; Chun-Xi Zhang; Lv-Bo Tian; Jie Huang; Li-Jun Jia; Hao Tao; Neng-Wei Yu; Bing-Hu Li (Mammalian Genome, 2025)

Mineral fertilizer substitution and application of Bacillus velezensis SQR9 reduced nitrogen-oxide emissions in tropical vegetable fields - Wei Tian; Feilong Liang; Longping Tu; Zhe Xu; Rong Li; Ruoya Ma; Yawen Huang; Shuang Wu; Shuqing Li; Jinyang Wang; Shuwei Liu; Zhaoqiang Han; et al. (Agriculture, Ecosystems & Environment, 2025)

Atmospheric nitrogen deposition has minor impacts on the abundance and diversity of arbuscular mycorrhizal fungi and their contribution to soil carbon stock in tropical forests - Andi Li; Peter Meidl; Senhao Wang; Bo Tang; Matthias C. Rillig; Guangcan Yu; Jing Chen; Rongzhen Liu; Zhiyang Lie; Anchi Wu; Lili Rong; Cheng Peng; et al. (Soil Biology and Biochemistry, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Recent progress in protein-based high internal-phase Pickering emulsions: Composition, stabilization, applications, and future trends - Wei Liang; Xiaofeng Zhan; Pengkai Wang; Chuan Li; Lu Zhang; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Research International, 2025)

Interfacial clustering-derived fluorescent, mechanically strong and fire-safe epoxy composites - Dong-Qing Zeng; Xin-Miao Li; Feng Chen; Wei-Bin Bai; Yu-Cai Lin; Rong-Kun Jian (Chemical Engineering Journal, 2025)

Iron isotopic fractionation during seafloor hydrothermal alteration of oceanic upper crust, as recorded in Geotimes lavas of Semail ophiolite, Oman - Rong-Zhong Bo; Yildirim Dilek; Wei-Qiang Li; Sobhi Nasir; Peng-Jie Cai; Hui-Chao Rui; De-Hong Du; Shi-Chao An; Yu-Xiao Lu; Hao-Chen Duan; Dong-Yang Lian; Jing-Sui Yang; et al. (Chemical Geology, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Monitoring-based analysis of the responses of upper structure and tunnel lining during shield tunneling with pile cutting - Zhi-Xiong Liu; Xiao-Wei Ye; Ke Song; Ci-Rong Lu; Yue-Jun Song; Xiao-Jun Li; Li-An Zhao (Tunnelling and Underground Space Technology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Effects of triclosan on microalgal-bacterial symbiosis system operating in stable phase: Performances and mechanisms - Qiang Chao; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian (Journal of Water Process Engineering, 2025)

Simultaneous recovery of water and antiscalant from cooling tower blowdown water by electrodialysis: Mechanism and cost-effectiveness - Jia-Rong Li; Jing-Han Wei; Yu-Chen Jin; Xian-Qiu Zhang; Hai-Ou Song; Ming-Xia Du (Journal of Cleaner Production, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Petrogenesis and age of granitoids associated with the Dongshan Cu polymetallic deposit, East Kunlun Orogenic Belt, NW China: Implications for the Middle to Late Triassic tectonic setting and Cu polymetallic mineralization - Yi-Chen Chen; Zheng-Jiang Ding; Jun-Wei Bo; Shi-Jiong Han; Ting-Ting Li; Pan Ji; Rong-Qiang Guo (Geochemistry, 2025)

Interfacial structure design enables rapid reaction kinetics for high-voltage NCM 613 cathodes - Yuan Xiao; Rong Gu; Tingting Zheng; Bowen Chang; Qiaoxia Li; Shuaiqi Gong; Xin Wei; Qunjie Xu; Yulin Min (Chemical Engineering Journal, 2025)

Construction of phenothiazine-decorated ZnO quantum dots with intelligent response to bacterial pH/amidase microenvironment for inducing bacterial ferroptosis-like death - Wu-Bin Shao; Rong-Shuang Luo; Yan-Wei Huang; Long Cheng; Dan Zeng; Xiang Zhou; Li-Wei Liu; Song Yang (Chemical Engineering Journal, 2025)

Legume intercropping improves soil organic carbon stability in drylands: A 7-year experimental validation - Wei Wang; Meng-Ying Li; Yang Wang; Jian-Ming Li; Wei Zhang; Qin-Hui Wen; Shuang-Jin Huang; Guang-Rong Chen; Shuang-Guo Zhu; Jing Wang; Fazal Ullah; You-Cai Xiong (Agriculture, Ecosystems & Environment, 2025)

Recent advances in the role of gasotransmitters in necroptosis - Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Ti Chu; Yan-Wen Wang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

Observed seasonal evolution and origins of the western Yellow Sea Cold Water Mass - Chuanjie Wei; Xiaohui Tang; Kai Ge; Anqi Xu; Yuanlong Li; Yong Jiang; Zengrui Rong; Fei Yu (Frontiers in Marine Science, 2025)
The Yellow Sea Cold Water Mass (YSCWM) is one of the most prominent hydrological features of the Yellow Sea. As a low-temperature, nutrient-rich subsurface water mass, the YSCWM fundamentally regulates biogeochemical cycles, functions of marine ecosystems, and fishery resources of the YS. In boreal summer, the YSCWM shows a robust triple-core structure, in which the western component, dubbed the “western YSCWM”, is revisited in this study. Through analyzing in-situ observational data collected by research cruises of the Institute of Oceanology, Chinese Academy of Sciences (IOCAS) and Lagrangian tracing experiments based on a high-resolution ocean model, we provide a thorough investigation for seasonal evolution and origins of the western YSCWM. In-situ observations during 2006-2007 and 2014-2015 suggest that the western YSCWM bears a tight connection to the colder coastal waters near the Shandong Peninsula and achieves the coldest temperature in summer. Analysis of model simulations confirms that the cooling of the western YSCWM in spring and summer is caused mainly by southward cold-water transport of the Shandong Coastal Current (SDCC) from the Shandong coasts and the northern Yellow Sea. We also reveal a contribution of the Subei Shoal water via the Subei Coastal Current (SCC) in summer, which plays a critical role in the quick vanishing of the western YSCMW in early autumn. These findings contribute to our understanding of the formation, seasonal evolution, and heat budgets of the YSCWM.

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Optimizing nitrogen fertilization and irrigation strategies to balance agroecosystem services in the wheat-maize double cropping system: A 21-year field study - Xinyue Qu; Wei Yao; Huijia Ji; Yi Xu; Rong Jia; Xinjie Chen; Hongjun Li; Antonio Rafael Sánchez-Rodríguez; Yanjun Shen; Yadong Yang; Zhaohai Zeng; Huadong Zang (Field Crops Research, 2025)

Ventral Hippocampal CA1 GADD45B Regulates Susceptibility to Social Stress by Influencing NMDA Receptor-Mediated Synaptic Plasticity - Mengbing Huang; Jian Bao; Xiaoqing Tao; Yifan Niu; Kaiwei Li; Ji Wang; Xiaokang Gong; Rong Yang; Yuran Gui; Hongyan Zhou; Yiyuan Xia; Youhua Yang; et al. (Neuroscience Bulletin, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

The effect of soil depth on stoichiometry was greater than that of elevation in Abies georgei var. Smithii forest in Southeastern Tibet, China - Si-jie Zhu; Jiang-rong Li; Bo Zhang; Fang-wei Fu; Liang-na Guo (Acta Oecologica, 2025)

Late Quaternary slip rate of the Northern Margin Fault of the Huaizhuo Basin in the North China Block and its seismological implications - Lu-wei Li; Zhong-yuan Yu; Chun-miao Qiu; Wen-xuan Wang; Qian Zhao; Rong-ying Zheng; Yan-Lin Yang (Applied Geophysics, 2025)

α-asarone activates mitophagy to relieve diabetic encephalopathy via inhibiting apoptosis and oxidative stress - Xiao-dan Yan; Rong-hua Fan; Yu Wang; Xiao-xu Duan; Xuan Wei; Lin-sen Li; Qing Yu (Metabolic Brain Disease, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Advancements in the development of porous nanomaterials for CO2 capture of deep decarbonization: Pore structure and chemical group optimization - Sifan Bao; Xudong Zheng; Zihuai Xu; Biao Ji; Zhouzhou Yang; Wei Sun; Lin Guo; Youming Zhu; Jinfeng Mei; Jian Rong; Zhongyu Li (Journal of Environmental Chemical Engineering, 2025)

Analysis of genetic diversity and population structure of Pinellia ternata using EST-SSR markers - Mingxing Wang; Rong Xu; Ming Luo; Xinyao Li; Lu Wei; Mi Lei; Dahui Liu; Yuhuan Miao (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Amine-impregnated elastic carbon nanofiber aerogel templated by bacterial cellulose for CO2 adsorption and separation - Sifan Bao; Xudong Zheng; Zihuai Xu; Biao Ji; Zhouzhou Yang; Wei Sun; Jinfeng Mei; Jian Rong; Zhongyu Li (Fuel, 2025)

Lipid peroxidation inhibition by icaritin and its glycosides as a strategy to combat iron overload-induced osteoporosis in zebrafish - Chang-Yu Yan; Xiao-Yuan Gu; Shuo-Yan Tan; Ao-Yu Mei; Jiang-Hao Mao; Yi Dai; Jie Niu; Wei-Xi Li; Hiroshi Kurihara; Yi-Fang Li; Rong-Rong He (Food Research International, 2025)

Effect of magnetic field-assisted thawing on the quality and microstructure of Portunus trituberculatus meat - Rong Shi; Zhongqi Sun; Xuemei Yu; Huamao Wei; Gaoshang Li; Wenge Yang (Food Research International, 2025)

Design, synthesis and antifungal activity of novel pyrazole-amide-isothiazole derivatives as succinate dehydrogenase inhibitors - Ai-ling Bao; Xian-song Xie; De-yuan Wang; Zi-quan Deng; Yun Chen; Dan Liu; Wei-yi Li; Xiao-rong Tang; Wei Cheng; Ying-kun Yan (Food Chemistry, 2025)

Inhibition of electron transfer in anaerobic ammonia-oxidized granular sludge by polyethylene terephthalate microplastics and nanoplastics: A new perspective on molecular docking and molecular dynamics simulations - Chaofan Xie; Dongyue Li; Jiarui Li; Linzhu Du; Yanshuo Wu; Rong Luo; Zheng Wang; Jun Li; Yuhan Zhu; Wei Guo (Chemical Engineering Journal, 2025)

PVA-enhanced green synthesis of CMC-based lithium adsorption films - Shengkai Liu; Huiling Li; Xi Li; Wei Wang; Chunguang Rong; Mengjie Yang; Yonggui Wang; Jing Wang; Yabei Xu; Daxin Liang; Yanjun Xie (Carbohydrate Polymers, 2025)

Revealing microbial compatibility of partial nitritation/Anammox biofilm from sidestream to mainstream applications: Origins, dynamics, and interrelationships - Yanxiao Wei; Weizhe Xia; Yunzhi Qian; Chao Rong; Min Ye; Yujie Chen; Jun Kikuchi; Yu-You Li (Bioresource Technology, 2025)

Different contributions of microbial and plant residues to soil organic carbon accumulation during planted forest and abandoned farmland restoration, Loess Plateau, China - Hongjian Hao; Rong Wang; Shicai Li; Duo Pian; Ning Peng; Ahejiang Sailike; Zhouchang Yu; Jiayi Shi; Xingbo Wang; Zihan Wang; Wei Zhang (Plant and Soil, 2025)

Transcriptome Sequencing Reveals Effects of Artificial Feed Domestication on Intestinal Performance and Gene Expression of Carnivorous Mandarin Fish (Siniperca chuatsi) and Related Mechanisms - Jia-Xing Luo; Xiao-Tian Gao; Zhen Rong; Li-Han Zhang; Yan-Feng Sun; Zun-Li Qi; Qi Yu; Khor Waiho; Wei-Xu Zhao; Yi-Huan Xu; Chun-Long Zhao; Cheng-Bin Wu (Marine Biotechnology, 2025)

Soil labile organic carbon and nitrate nitrogen are the main factors driving carbon-fixing pathways during vegetation restoration in the Loess Plateau, China - Yujie Liang; Rong Fu; Ahejiang Sailike; Hongjian Hao; Zhouchang Yu; Rong Wang; Ning Peng; Shicai Li; Wei Zhang; Yangyang Liu (Agriculture, Ecosystems & Environment, 2025)

Analysis of factors influencing microseismic detection and location in shale gas extraction areas of western Hubei - Wan-peng Hao; Li-fen Zhang; Yan-nan Zhao; Rong-ying Zheng; Wei-bing Qin; Jing-gang Li (Applied Geophysics, 2025)

Performance prediction of urban tunnel purification system based on the verified random number screening algorithm - Jie Xia; Hao-Yi Zhao; Hui Ren; Long Chen; Fang Li; Wei-Rong Shi; Yi-Song Xie; Mei-Lan Tan; Fei Li; Bin Zhou (Sustainable Cities and Society, 2025)

Geothermal distribution and evolution of fault-controlled Linyi geothermal system: Constrained from hydrogeochemical composition and numerical simulation - Yuzhong Liao; Wei Zhang; Yuwei Rong; Long Li; Guoqing Hu (Geothermics, 2025)

Weavable composite filament for sustained electricity generation from multiple sources - Rong Liu; Haoyu Li; Zhenzhou Fu; Hailou Wang; Jiamu Dai; Kai Dong; Ick Soo Kim; Wei Zhang (Chemical Engineering Journal, 2025)

Characterization of Gut Microbiota in Rats and Rhesus Monkeys After Methamphetamine Self-administration - Li He; Jia-hui Zhou; Huan Li; Wen-lei Zhang; Tie-qiao Liu; Hai-feng Jiang; Rong-wei Zhai; Xiao-jie Zhang (Molecular Neurobiology, 2025)

Intermittent fasting shifts the diurnal transcriptome atlas of transcription factors - Min Fu; Siyu Lu; Lijun Gong; Yiming Zhou; Fang Wei; Zhigui Duan; Rong Xiang; Frank J. Gonzalez; Guolin Li (Molecular and Cellular Biochemistry, 2025)

Pollution status and assessment of seven heavy metals in the seawater and sediments of Hangzhou Bay, China - Rong Zhu; Yan-Yan Zeng; Li-Min Liu; Lu Yin; Kai-Ping Xu; Wei-Feng Chen; Shang-Chun Li; Xiao-Feng Zhou (Marine Pollution Bulletin, 2024)

Progress in the application of Salmonella vaccines in poultry: A mini review - Jie Pan; Rong-rong Wei; Ping Xu; Yun-ying Liu; Chen Li; Guo-wei Ding; Juan Fan; Yu-he Li; Jing-yi Yu; Peng Dai (Veterinary Immunology and Immunopathology, 2024)

Learning-guided cross-sampling for large-scale evolutionary multi-objective optimization - Haofan Wang; Li Chen; Xingxing Hao; Rong Qu; Wei Zhou; Dekui Wang; Wei Liu (Swarm and Evolutionary Computation, 2024)

Unveiling spatiotemporal distribution, partitioning, and transport mechanisms of tire additives and their transformation products in a highly urbanized estuarine region - Hai-Yan Zhang; Yue-Hong Liu; Li-Ni Wei; Rui-Qi Zhu; Jian-Liang Zhao; Shan Liu; Xiang-Rong Xu; Guang-Guo Ying (Science of The Total Environment, 2024)

Long-term cereal-legume intercropping accelerates soil organic carbon loss in subsoil of dryland - Wei Wang; Guang-Rong Chen; Meng-Ying Li; Yinglong Chen; Yang Wang; Hong-Yan Tao; Hui-Zhi Hou; Muhammad Maqsood Ur Rehman; Muhammad Ashraf; Yajie Song; Levis Kavagi; Bao-Zhong Wang; et al. (Resources, Conservation and Recycling, 2024)

The correlation between single and mixed trace elements exposure in systemic lupus erythematosus: A case-control study - Rong-Gui Huang; Kai-Di Li; Hong Wu; Yi-Yu Wang; Ya Xu; Xue Jin; Yu-Jie Du; Yi-Yuan Wang; Jing Wang; Zhang-Wei Lu; Bao-Zhu Li (Journal of Trace Elements in Medicine and Biology, 2024)

A tumor-pH-responsive phthalocyanine as activatable type I photosensitizer for improved photodynamic immunotherapy - Ling Zhang; Rong-Bin Que; Ting-Ting Ke; Chao Wang; Wei Xie; Hong-Jie Sun; Bi-Yuan Zheng; Mei-Rong Ke; Jian-Dong Huang; Xingshu Li (Journal of Photochemistry and Photobiology B: Biology, 2024)

Association between indoor PM2.5 components and accelerated biological aging in schizophrenia patients: Evidence from multi-omics mechanisms - Rubing Pan; Xingxu Yi; Yanlong Xu; Jian Song; Weizhuo Yi; Jintao Liu; Rong Song; Xuanxuan Li; Li Liu; Jiajun Yuan; Ning Wei; Yuxing Huang; et al. (Journal of Hazardous Materials, 2024)

Origin of the Narenwula quartz vein-type W deposit, Inner Mongolia, China: Insights from geochemistry of hosting granites, fluid inclusions, H-O-S isotopes, and wolframite trace elements - Lin-Wei Wang; De-Hui Zhang; Jia-Jun Liu; Zhu Li; Rong-Zhen Zhang; Xi Diao; Bin Zhang; Guo-Ming Weng (Journal of Asian Earth Sciences, 2024)

Exploring the dynamic characteristic of typical kombucha induced by symbiotic microbiota succession from four Chinese regions: A comprehensive analytical framework - Shiqi Li; Ruinan Wang; Rong Liu; Leran Wang; Xingnan Wang; Jianping Wei; Yahong Yuan; Tianli Yue; Rui Cai; Zhouli Wang (Food Research International, 2024)

Ultra-low temperature heating system based on dual-source solar assisted heat pump using compound parabolic concentrator-capillary tube solar collector - Li Wei Yang; Jin Huan Pu; Rong Ji Xu; Tong Yang; Hua Sheng Wang (Energy and Buildings, 2024)

Electrodialysis with ultrafiltration membrane for efficient isolation of oxymatrine from simulated eluent of traditional Chinese medicine - Zhiguo Dong; Rong Zhou; Zengqiang Wei; Yiwei Dong; Li Sun; Xixi Ma; Wenlong Liu; Qiuhua Li; Jinfeng He; Chuanrun Li; Haiyang Yan (Desalination, 2024)

Multiple NADPH-cytochrome P450 reductases from Lycoris radiata involved in Amaryllidaceae alkaloids biosynthesis - Yuqing Wu; Yifeng Zhang; Haitong Fan; Jie Gao; Siyu Shen; Jifan Jia; Rong Liu; Ping Su; Yating Hu; Wei Gao; Dan Li (Plant Molecular Biology, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

A compound heterozygous mutation of ERCC8 is responsible for a family with Cockayne syndrome - Meng-Wei Liu; Cheng-Feng Hu; Jie-Yuan Jin; Rong Xiang; Liang-liang Fan; Ya-Li Li; Lei Zhu (Molecular Biology Reports, 2024)

Correction: A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Amplification of warming-wetting in high mountains and associated mechanisms during the 21st century in Xinjiang, Central Asia - Rong Chen; Keqin Duan; Peihong Shi; Wei Shang; Junhua Yang; Jinping He; Yali Meng; Mingyu Dou; Liang Li (Climatic Change, 2024)

Nitrifying and denitrifying microbes exhibit distinct community structure and activity responses to different crop rotation systems in subtropical paddy soils - Huifang Xu; Ke Li; Rong Sheng; Hongling Qin; Yi Liu; Anlei Chen; Haijun Hou; Baoli Zhu; Wenxue Wei; Wenzhao Zhang (Applied Soil Ecology, 2024)

Host preference and mortality caused by the parasitoid Sclerodermus guani on different cerambycid species - Qun Yu; Shuang Li; Yu-Jun Kong; Zuo-Xiang Sun; Dan-Dan Cao; Jian-Rong Wei (BioControl, 2024)

Exploring secretory signal sequences useful in excreting recombinant proteins in Beauveria bassiana as biocontrol fungus - Kang Wei; Jin-Li Ding; Hang-Rong Xu; Ming-Guang Feng; Sheng-Hua Ying (Archives of Microbiology, 2024)

Active tectonic deformation and its seismic–geological significance of boundary faults of the Daxing Uplift and Langgu–Dachang Depression, Beijing Plain, China - Rong-Ying Zheng; Zhong-Yuan Yu; Bai-Xu Chen; Lu-Wei Li; Yi-Cheng Wang (Applied Geophysics, 2024)

Early Cretaceous mafic dikes in the eastern North China Craton: implications for the effect of slab subduction on the mantle sources - Chao Li; Lin Li; Ju-Quan Zhang; M. Santosh; Sheng-Rong Li; Bowen Wei; Cong Li (International Geology Review, 2024)

White matter lesions contribute to motor and non-motor disorders in Parkinson’s disease: a critical review - Yue-Qi Jiang; Qiu-Zhu Chen; Yang Yang; Cai-Xia Zang; Jing-Wei Ma; Jin-Rong Wang; Yi-Rong Dong; Ning Zhou; Xing Yang; Fang-Fang Li; Xiu-Qi Bao; Dan Zhang (GeroScience, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Changes in secondary sexual characteristics of female red swamp crayfish (Procambarus clarkii) and relationship to ovarian development: Implications for intensive breeding of seedlings - Lirong Qin; Jinhui He; Kuan Rong; Chao Guo; Jiashou Liu; Tanglin Zhang; Wei Li (Aquaculture, 2024)

Exploring the variations in molecular characteristics of dissolved organic matter driven by aquaculture types - Li-Ping Li; Xin-Yi Jiao; Shuang Peng; Dong-Bin Wei; Yan-Chao Jin; Cai-Shan Wang; Ding Pan; Peng Liu; Xue-Rong Wang; Yu-Ping Tang; Dong Ren; Xin-Hui Liu (Water Research, 2024)

A novel cleaner production for ferromagnetic materials from red mud: Process design, thermodynamic study and environment assessment - Yadong Wu; Fangqi Li; Wei Liu; Chaosen Yang; Rong Liu; Hongsheng Huang (Process Safety and Environmental Protection, 2024)

Microplastics from polyvinyl chloride agricultural plastic films do not change nitrogenous gas emission but enhance denitrification potential - Xiaofang Ma; Zhijun Wei; Xiaomin Wang; Chenglin Li; Xueying Feng; Jun Shan; Xiaoyuan Yan; Rong Ji (Journal of Hazardous Materials, 2024)

Improving curcumin bioavailability: Targeted delivery of curcumin and loading systems in intestinal inflammation - Junyi Zhao; Wei Jia; Rong Zhang; Xin Wang; Li Zhang (Food Research International, 2024)

Fate and drivers of mariculture-derived microplastics from ponds to mangrove forests - Zhen Zhao; Yihua Wei; Yijin Wang; Gen Peng; Eddy Y. Zeng; Kefu Yu; Xiang-Rong Xu; Ruilong Li (Environmental Pollution, 2024)

3D printing technologies in water Treatment: Applications, Challenges, and emerging trends - Yun-fei Zhang; Jin-ze Li; Yue Zou; Yan-lin Liu; Lei Li; Jian-hui Xu; Dan Li; Qiang-qiang Rong; Jian-ying Li; Yi-xin Geng; Jia-wei Lai (Chemical Engineering Journal, 2024)

Weakly solvated electrolyte enables the robust solid electrolyte interface on SiOx anodes for lithium-ion battery - Zuojie Xu; Rong Huang; Pengfei Huang; Chaowei He; Shenwen Liu; Haonan Zheng; Wenlong Song; Lu Shi; Weiwei Gao; Dan Li; Hui Huang; Hangjun Ying; et al. (Chemical Engineering Journal, 2024)

Controlled assembly and synthesis of oxygen-deficient W18O49 films based on solvent molecular strategy for electrochromic energy storage smart windows - Xiaohui Sun; Wei Wu; Nana Liu; Peng Li; Xueying Zhao; Zhaozhu Qu; Kunming Zhao; Bo Wang; Xianhui Rong; Xuyang Zhang; Guohua Wu; Xiangwei Wang (Chemical Engineering Journal, 2024)

Fabrication of graphene oxide/ammonium molybdophosphate composite membrane for decontamination of cesium ions from seawater - Xiao-Yi Tang; Zi-Jie Li; Lin Wang; Peng-Cheng Zhang; Kong-Qiu Hu; Li-Rong Zheng; Zhi-Hui Zhang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2024)

A novel hollow flower shaped Cu9S8 antibacterial agent for removing sulfonamide in water environment: effects of composite with magnetic biochar, differential adsorption, and mechanism study - Rui-peng Li; Zheng-rong Hu; Xing Wang; Jun Chen; Qing-qing Liu; Ying Zhao; Zhong-bao Zhao; Xu-lin Lu; Zhi-wei Zhang (Environmental Science and Pollution Research, 2024)

Isobavachin induces autophagy-mediated cytotoxicity in AML12 cells via AMPK and PI3K/Akt/mTOR pathways - Ning Xia; Qing-Hai Chen; Zhao-Jun Meng; Shu-Yue Ma; Jia-Li Huang; Rong Shen; Yu-Tong Dong; Hai-Wei Du; Kun Zhou (Toxicology in Vitro, 2024)

Impaired thyroid hormone sensitivity exacerbates the effect of PM2.5 and its components on dyslipidemia in schizophrenia - Jintao Liu; Yinguang Fan; Jian Song; Rong Song; Xuanxuan Li; Li Liu; Ning Wei; Jiajun Yuan; Weizhuo Yi; Rubing Pan; Xiaoyu Jin; Jian Cheng; et al. (Science of The Total Environment, 2024)

Elemental and isotopic perspective on the formation of Permian mafic magmatic rocks from the Xing'an Mongolia Orogenic Belt and northern North China Craton - Wei Liu; Dongya Zou; Xiaolong Zhang; Xiaoyan Gu; Rong Xu; Gangzhu Li (Lithos, 2024)

Construction of oxygen-doped g-C3N4/BiOCl (S-scheme) heterojunction: Efficient degradation of tetracycline in wastewater - Yuan Wei; Yu-Bing Liu; Chao Liu; Xin Li; Guang-Hong Zhao; Rong-Hui Liu; Hong-Yu Wang; Yan-Yan Jiang; Yu-Lan Zhang; Yu-Hui Gao; Gao-Feng Shi; Guo-Ying Wang (Journal of Environmental Chemical Engineering, 2024)

Enhanced hydrate formation at the liquid CO2-brine interface with shear flow for solid CO2 sequestration - Ming-Long Wang; Yi-Fei Sun; Wei-Xin Pang; Qing-Ping Li; Ting Huang; Hong-Nan Chen; Ming Wang; Jin-Rong Zhong; Liang-Liang Ren; Dan Rao; Bei Liu; Chang-Yu Sun; et al. (Gas Science and Engineering, 2024)

Ru0.7Cu0.3/W18O49 Schottky junction for visible-light-driven hydrogen generation from ammonia borane hydrolysis - Shu-Bin Li; Wei-Yang Long; Chuan-Qi Li; Yan-Xin Duan; Rong-Chao Cui; Zhong-Yi Liu; Xin-Zheng Yue (Fuel, 2024)

Effects of soy protein on alleviating iron deficiency anemia in suckling rats with different iron supplements - Mengxiao Hu; Jun Zhou; Lili Qiu; Rui Song; Xiyu Qin; Zidi Tan; Wei Wang; Rong Liu; Yun Li; Yingyi Mao; Xiang Li; Fei Li; et al. (Food Bioscience, 2024)

Development of easy-to-swallow and lipid-enhanced 3D printed surimi based on high internal phase emulsions - Wei Liang; Yuhang Wang; Chuan Li; Pengkai Wang; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2024)

N, S-carbon quantum dots as inhibitor in pickling process of heat exchangers for enhanced performance in multi-stage flash seawater desalination - Bochuan Tan; Yan Liu; Haiqin Ren; Zhili Gong; Xin Li; Wenpo Li; Lei Guo; Rong Chen; Juxiang Wei; Qingwei Dai; Abeer A. AlObaid (Desalination, 2024)

Successful subduction of oceanic plate after failed attempts in the Late Archean: Petrological and geochemical constraints - Xi Wang; Rong-Feng Ge; Yong-Fei Zheng; Wen-Bin Zhu; San-Zhong Li; Rong-Song Tian; Yue Wang; Yi-Wei Rong (Earth and Planetary Science Letters, 2024)

Simultaneous carbon, nitrogen and phosphorus removal in sequencing batch membrane aerated biofilm reactor with biofilm thickness control via air scouring aided by computational fluid dynamics - Chun-Hai Wei; Xin-Yu Zhai; Yu-Duo Jiang; Hong-Wei Rong; Li-Gong Zhao; Peng Liang; Xia Huang; Huu Hao Ngo (Bioresource Technology, 2024)

Influenza A Virus PB1-F2 Induces Affective Disorder by Interfering Synaptic Plasticity in Hippocampal Dentate Gyrus - Saiying Wang; Haijun Zhang; Rui Liu; Peijun Han; Qi Yang; Caiyan Cheng; Yue Chen; Zheng Rong; Chang Su; Fei Li; Gaofei Wei; Minggao Zhao; et al. (Molecular Neurobiology, 2024)

Effects of Humic Acid-Copper Interactions on Growth, Nutrient Absorption, and Photosynthetic Performance of Citrus sinensis Seedlings in Sand Culture - Wei-Tao Huang; Qian Shen; Hui Yang; Xu-Feng Chen; Wei-Lin Huang; Han-Xue Wu; Ning-Wei Lai; Lin-Tong Yang; Zeng-Rong Huang; Li-Song Chen (Journal of Plant Growth Regulation, 2024)

Label-Free Detection of Programmed Death-Ligand 1 for Prognosis Using a Truncated Aptamer and SYBR Green I - Ling Li; Zheng-Ling Li; Wei Wang; Xin-Xin Long; Ping Liu; Guo-Tian Wang; Shi-Qing Sun; Rong-Lian Du (Journal of Fluorescence, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Investigating protistan predators and bacteria within soil microbiomes in agricultural ecosystems under organic and chemical fertilizer applications - Chen Liu; Zeyuan Zhou; Shuo Sun; Qi Zhang; Shiqi Sun; Xinnan Hang; Mohammadhossein Ravanbakhsh; Zhong Wei; Rong Li; Shimei Wang; Wu Xiong; George A. Kowalchuk; et al. (Biology and Fertility of Soils, 2024)
Organic farming can enhance biodiversity and soil health and is a sustainable alternative to conventional farming. Yet, soil protists especially protistan predators, have received inadequate attention, and their contributions to the sustainability of organic farming remained underexplored. In this study, we examined soil microbial communities from 379 samples, including both organic and chemically fertilized soils from China. Our findings revealed higher bacterial diversity and increases in plant-beneficial bacteria in organically farmed soils. Notably, organic farming systems facilitated dynamic predator-prey interactions, which may be disrupted by the application of chemical fertilizers. Additionally, organic farming enriched protistan predators, enhancing the relative abundance of functional PGPR, thus improving soil health. We further conducted a case study highlighting the critical role of organic matter in sustaining protistan predator populations and their interactions with bacteria. We propose the crucial contributions of organic inputs for supporting protistan predators and the interplay of predator-prey, ultimately enhancing soil functions and promoting agricultural sustainability.

Glutamine deprivation in glioblastoma stem cells triggers autophagic SIRT3 degradation to epigenetically restrict CD133 expression and stemness - Zhengcao Xing; Xianguo Jiang; Yalan Chen; Tiange Wang; Xiaohe Li; Xiangyun Wei; Qiuju Fan; Jie Yang; Hongmei Wu; Jinke Cheng; Rong Cai (Apoptosis, 2024)

Numerical Analysis of Leading-Edge Roughness Effects on the Aerodynamic Performance of a Thick Wind Turbine Airfoil - Wei Zhang; Kuichao Ma; Chang Cai; Xiangyu Sun; Jun Zhang; Xiaohui Zhong; Xiaomin Rong; Qing’an Li (Journal of Marine Science and Engineering, 2024)
The aerodynamic performance of wind turbine airfoils is crucial for the efficiency and reliability of wind energy systems, with leading-edge roughness significantly impacting blade performance. This study conducts numerical simulations on the DU 00-W-401 airfoil to investigate the effects of leading-edge roughness. Results reveal that the rough airfoil exhibits a distinctive “N”-shaped lift coefficient curve. The formation mechanism of this nonlinear lift curve is primarily attributed to the development of the trailing-edge separation vortex and variations in the adverse pressure gradient from the maximum thickness position to the trailing-edge confluence. The impact of different roughness heights is further investigated. It is discovered that when the roughness height is higher than 0.3 mm, the boundary layer can be considered fully turbulent, and the lift curve shows the “N” shape stably. When the roughness height is between 0.07 mm and 0.1 mm, a transitional state can be observed, with several saltation points in the lift curve. The main characteristics of different flow regimes based on different lift curve segments are summarized. This research enhances the understanding of the effects of leading-edge roughness on the aerodynamic performance of a thick wind turbine airfoil, and the simulation method for considering the effect of leading-edge roughness is practical to be applied on large-scale wind turbine blade to estimate the aerodynamic performance under rough leading-edge conditions, thereby supporting advancements in wind turbine technology and promoting the broader adoption of renewable energy.

Sulphur in apatite: a potential monitor of the magmatic redox state in the world-class gold fields of the North China Craton - Jia-Wei Liu; Lin Li; Sheng-Rong Li; M. Santosh; Mao-Wen Yuan; Masroor Alam; Shun-Feng Yan (International Geology Review, 2024)

High-risk ARGs (HRA) Chip: A high-throughput qPCR-based array for assessment of high-risk ARGs from the environment - Huan-Qin Li; Mei-Rong Xu; Xin-Li An; Hu Liao; Li-Juan Li; Wei Li; Jian-Qiang Su (Water Research, 2024)

CXCR3 participates in asymmetric division of mouse oocytes by modulating actin dynamics - Wei-jian Li; Rong-yang Li; Da-yu Wang; Ming Shen; Hong-lin Liu (Theriogenology, 2024)

Genetic variation in a heat shock transcription factor modulates cold tolerance in maize - Lei Gao; Lingling Pan; Yiting Shi; Rong Zeng; Minze Li; Zhuoyang Li; Xuan Zhang; Xiaoming Zhao; Xinru Gong; Wei Huang; Xiaohong Yang; Jinsheng Lai; et al. (Molecular Plant, 2024)

Biofilm growth characteristic and footprint identification in gravity-driven ceramic membrane bioreactor with electro-coagulation under extreme conditions for roofing rainwater purification - Wei Song; Rong Ma; Zhenhao Liang; Jiawan Li; Jiahao Dong; Xing Du; Zhihong Wang; Xianhui Li (Journal of Environmental Management, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Enhanced reaction kinetics and structure integrity of Cu/F co-doped SnO2@C composite for high-performance lithium-ion batteries - Shixin Huang; Longjun Guo; Wei Liu; Chunjin Hang; Rong An; Yongfeng Li; Yanhong Tian (Chemical Engineering Journal, 2024)

Synergistic optimization of the water state and transport pathway in hydrogels via pullulan and directional Freezing-Assisted salting out for efficient evaporation - Huanwei Shen; Xiayue Yang; Wenhao Li; Zhihua Sha; Hongmei Luo; Zixuan Li; Sihan Dong; Wei Cui; Rong Ran (Chemical Engineering Journal, 2024)

Argon non-thermal plasma treatment promotes the development of rice (Oryza sativa L.) in saline alkali environments - Kai Liu; Yan-Jiang Feng; Jun-Xiang Guo; Gui-Ling Wang; Li-Li Shan; Shi-Wei Gao; Qing Liu; Hu-Nan Sun; Xi-Yu Li; Xing-Rong Sun; Jing-Yang Bian; Taeho Kwon (Protoplasma, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Development of a loading and diagnostic system to study laboratory earthquakes - Rong Chen; Ying Xu; Xuan Li; Wei Yao; Sheng Huang; Qi Zhao (Bulletin of Engineering Geology and the Environment, 2024)

Dietary anthocyanins as natural phytochemicals for regulating hyperuricemia: Proposed intestinal flora, key enzyme activity, and anti-inflammatory pathways - Shuai Lv; Wei Jia; Rong Zhang; Li Zhang (Trends in Food Science & Technology, 2024)

Temporal variations in dissolved organic matter properties in a eutrophic lake under water dilution and aquatic plant litter decomposition: A simulated microcosm study revealing the environmental and microbial driving factors - Rong Wu; Haoyu Wang; Wei Li; Xiaowan Chen; Qichao Zhou; Junjun Chang (Journal of Water Process Engineering, 2024)

Polydopamine/chitosan hydrogels-functionalized polyurethane foams in situ decorated with silver nanoparticles for water disinfection - Shuhan Wu; Huayong Luo; Shiyin Li; Zexin Zheng; Qingwu Long; Chunhai Wei; Hongwei Rong (Journal of Environmental Management, 2024)

Digestion and absorption characteristics of iron-chelating silver carp scale collagen peptide and insights into their chelation mechanism - Qiannan Zhao; Wei Liang; Zhe Xiong; Chuan Li; Lu Zhang; Jianhua Rong; Shanbai Xiong; Ru Liu; Juan You; Tao Yin; Yang Hu (Food Research International, 2024)

Seasonal dynamics of the microbiota and nutritional composition in bee bread from Apis cerana and Apis mellifera colonies - Jia-Li Li; Wan-Li Li; Jun Zhang; Yan-tao Pang; Jian Xiong; Ping Wu; Bang-rong Wei; Xi-Jie Li; Qi Huang; Qi-He Tang; Chong-Hui Zhao; Qian Wang; et al. (Food Research International, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

Mass cytometry revealed the circulating immune cell landscape across different Suzuki stages of Moyamoya disease - Chenglong Liu; Peicong Ge; Bojian Zhang; Liujia Chan; Yuheng Pang; Chuming Tao; Junsheng Li; Qiheng He; Wei Liu; Siqi Mou; Zhiyao Zheng; Zhikang Zhao; et al. (Immunologic Research, 2024)
Moyamoya disease (MMD) is a cerebrovascular disorder marked by progressive arterial narrowing, categorized into six stages known as Suzuki stages based on angiographic features. Growing evidence indicates a pivotal role of systemic immune and inflammatory responses in the initiation and advancement of MMD. This study employs high-dimensional mass cytometry to reveal the immunophenotypic characteristics of peripheral blood immune cells (PBMCs) at various Suzuki stages, offering insights into the progression of MMD. PBMC samples from eight patients with early-stage MMD (Suzuki stages II and III) and eight patients with later-stage MMD (Suzuki stages IV, V, and VI) were analyzed using high-dimensional mass cytometry to evaluate the frequency and phenotype of immune cell subtypes. We identified 15 cell clusters and found that the immunological features of early-stage MMD and later-stage MMD are composed of cluster variations. In this study, we confirmed that, compared to later-stage MMD, the early-stage MMD group exhibits an increase in non-classical monocytes. As the Suzuki stage level increases, the proportions of plasmacytoid DCs and monocyte-derived DCs decrease. Furthermore, T cells, monocytes, DCs, and PMN-MDSCs in the early-stage MMD group show activation of the canonical NF-κB signaling pathway. We summarized and compared the similarities and differences between early-stage MMD patients and later-stage MMD patients. There is a potential role of circulating immune dysfunction and inflammatory responses in the onset and development of MMD.

Microneedle electrochemical sensor based on disposable stainless-steel wire for real-time analysis of indole-3-acetic acid and salicylic acid in tomato leaves infected by Pst DC3000 in situ - Lingjuan Tang; Daodong Li; Wei Liu; Yihui Tang; Rongcheng Zhang; Yiran Tian; Rong Tan; Xiaolong Yang; Lijun Sun (Analytica Chimica Acta, 2024)

Timing and Kinematics of late Cenozoic Strike-slip Faults in the Western Tibetan Plateau: New Constraints from Provenance Analysis and Detrital Thermochronology - Xiaochun Wei; Hanlin Chen; Rong Yang; Ping Wang; Shanying Li; Xuhua Shi; Jin Ge (Tectonophysics, 2024)

Combined effects of cadmium and sulfamethoxazole on Eisenia fetida: Insights into accumulation, subcellular partitioning, biomarkers and toxicological responses - Sheng-Nan Zhang; Yi-Tong Zhou; Jun Xia; Yu-Meng Wang; Jun-Wei Ma; Li-Kun Wang; Kashif Hayat; Shan-shan Bai; Cheng-han Li; Ming-Rong Qian; Hui Lin (Science of The Total Environment, 2024)

Biocontrol performance of a novel Bacillus velezensis L33a on tomato gray mold and its complete genome sequence analysis - Lixinyu Sun; Yu Chen; Shiyu Liu; Xiaogang Ou; Yangyang Wang; Zhengwu Zhao; Rong Tang; Yingzhe Yan; Xinyue Zeng; Shun Feng; Tao Zhang; Zhengguo Li; et al. (Postharvest Biology and Technology, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

Molecular characterization, expression analysis and function identification of Pf_IL-12p35, Pf_IL-23p19 and Pf_IL-12p40 genes in yellow catfish (Pelteobagrus fulvidraco) - Xin-Xin Jiang; Zi-Rui Tang; Zhang-Ping Li; Gui-Rong Zhang; Xu Zhou; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2024)

Hemorrhagic Shock and Resuscitation Causes Excessive Dopaminergic Signaling in the mPFC and Cognitive Dysfunction - Rong-Xin Song; Hui-Tao Miao; Shi-Yan Jia; Wen-Guang Li; Ji-Zhen Liu; Wei Zhang; Bao-Rui Xing; Jian-Yong Zhao; Li-Min Zhang; Xiao-Ming Li (Molecular Neurobiology, 2024)

NCOA4-mediated ferritinophagy participates in cadmium-triggered ferroptosis in spermatogonia - Didi Jia; Mingming Zhang; Mengyuan Li; Wenjing Gong; Wei Huang; Rong Wang; Yihang Chen; Qizi Yin; Jie Wu; Zhongxiu Jin; Juan Wang; Yehao Liu; et al. (Toxicology, 2024)

Long-term chemical and organic fertilization induces distinct variations of microbial associations but unanimous elevation of soil multifunctionality - Ke Li; Anlei Chen; Rong Sheng; Haijun Hou; Baoli Zhu; Wenxue Wei; Wenzhao Zhang (Science of The Total Environment, 2024)

Phytoremediation capacity of the hyperaccumulator Solanum nigrum L. and Solanum lycopersicum L. cultivars at the flowering stage in cadmium-polluted soil - Jibao JIA; Huiping DAI; Shuhe WEI; Lidia SKUZA; Jianming XUE; Rong LI; Quan SUN (Pedosphere, 2024)

Formation behavior of PCDD/Fs during waste pyrolysis and incineration: Effect of temperature, calcium oxide addition, and redox atmosphere - Yuanjun Tang; Dongsheng Tao; Guoneng Li; Chao Ye; Zhongming Bu; Rong Shen; Yonghui Lin; Wei Lv (Environmental Pollution, 2024)

Role of phytoliths in carbon stabilization of Zostera marina L. plants: One unreported mechanism of carbon sequestration in eelgrass beds - Bowen Rong; Li Zhang; Zhaojun Liu; Weihao Bai; Weidong Gu; Xiangtao Wei; Wenhao Hou; Changzi Ge (Estuarine, Coastal and Shelf Science, 2024)

Effects of Hericium erinaceus polysaccharide in porcine IPEC-J2 intestinal epithelial cells against apoptosis induced by oxidative stress - Jian Li; Jia-rong Mo; Shi-yu Hu; Xin Dong; Jia-wei Li; Li-yu Yang; Yi-jian Wu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Synergistic chemo-photodynamic therapy based on hollow mesoporous organosilica nanoparticles for reducing psoriasis-like inflammation - Zhijia Fan; Gang Zhao; Yixiao Gan; Li Wei; Rong Xia; Min Lu; Zhicheng Wang (Chemical Engineering Journal, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

A Higher Stomatal Aperture is Associated with the Growth Promotion of Centipedegrass (Eremochloa ophiuroides (Munro) Hack.) Under High Concentrations of Ammonium - Dong-Li Hao; Jin-Yan Zhou; Xiao-Hui Li; Jia Qu; Wei-Yi Kong; Rong-Rong Chen; Dan-Dan Li; Jian-Jian Li; Hai-Lin Guo; Jian-Xiu Liu; Jun-Qin Zong; Jing-Bo Chen (Journal of Soil Science and Plant Nutrition, 2024)

Stochastic community assembly of abundant taxa maintains the relationship of soil biodiversity-multifunctionality under mercury stress - Shuai Du; Xin-Qi Li; Li Bi; Dong Zhu; Hang-Wei Hu; Xiuli Hao; Jiao Feng; Qiaoyun Huang; Yu-Rong Liu (Soil Ecology Letters, 2024)

Index construction and real-time hazard assessment of rice sterile-type chilling injury process in Northeast China - Bilige Sudu; Kaiwei Li; Suri Guga; Teri Gele; Feng Zhi; Ying Guo; Sicheng Wei; Guangzhi Rong; Yongbin Bao; Xingpeng Liu; Jiquan Zhang (Agricultural and Forest Meteorology, 2024)

Special clinical entity with 15q26 deletion: a novel case report - Wei-Liang Liu; Fang Li; Lu Liu; Rong Ai (Journal of Genetics, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

Northward shift of Indian summer monsoon and intensifying winter westerlies cause stronger precipitation seasonality over Pamirs and its downstream basins in the 21st century - Jinping He; Keqin Duan; Shuangshuang Li; Wei Shang; Qiong Wang; Rong Chen; Yali Meng (Science of The Total Environment, 2024)

Biodegradation of various grades of polyethylene microplastics by Tenebrio molitor and Tenebrio obscurus larvae: Effects on their physiology - Meng-Qi Ding; Jie Ding; Zhi-Rong Zhang; Mei-Xi Li; Chen-Hao Cui; Ji-Wei Pang; De-Feng Xing; Nan-Qi Ren; Wei-Min Wu; Shan-Shan Yang (Journal of Environmental Management, 2024)

Soil inorganic carbon stock and its changes across the Tibetan Plateau during the 1980s–2020s - Honghong Lin; Xingwu Duan; Yifan Dong; Ronghua Zhong; Hua Zheng; Yun Xie; Li Rong; Haijuan Zhao; Shengzhao Wei (Global and Planetary Change, 2024)

hOGG1: A novel mediator in nitrosamine-induced esophageal tumorigenesis - De-Rong Tang; Cheng-Lin Li; Zhi-Yun Xu; Zhen-Zhong Zhang; Qian-Wei Wang; Jian-Qiang Zhao (Food and Chemical Toxicology, 2024)

Unravelling the safety improving and failure mechanisms of a 56.5 Ah high-energy–density Li-ion cell containing solid-state electrolyte - Wei Zhang; Xiaopeng Qi; Min Liu; Bingxue Liu; Yuansen Hu; Jing Ye; Rennian Wang; Bin Li; Changhong Wang; Qian Huang; Bing Yu; Rong Yang; et al. (Chemical Engineering Journal, 2024)

The phylogenetic analysis of two invasive Trapa species in the United States revealed by chloroplast genomes and morphological traits - Xiang-Rong Fan; Nancy Rybicki; Lynde L. Dodd; Jie Min; Wei Li; Xiu-Ling Li; Godfrey Kinyori Wagutu; Yuan-Yuan Chen (Biological Invasions, 2024)

LSTM-based deformation forecasting for additional stress estimation of existing tunnel structure induced by adjacent shield tunneling - Xiao-Wei Ye; Si-Yuan Ma; Zhi-Xiong Liu; Yan-Bo Chen; Ci-Rong Lu; Yue-Jun Song; Xiao-Jun Li; Li-An Zhao (Tunnelling and Underground Space Technology, 2024)

Synchronous fluorescence spectra-based machine learning algorithm with quick and easy accessibility for simultaneous quantification of polycyclic aromatic hydrocarbons in edible oils - Jia-Wen Wei; Jia-Rong He; Shi-Yi Chen; Yi-Han Guo; Xuan-Zhu Huo; Nuan Zheng; Shuo-Hui Cao; Yao-Qun Li (Food Control, 2024)

Early warning of urban heavy metal pollution based on PMF- MeteoInfo model combined with physicochemical properties of dust - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Xinying Zhang; Wei Yu; Rong Yu; Xinyu Liu (Stochastic Environmental Research and Risk Assessment, 2024)

A human-specific insertion promotes cell proliferation and migration by enhancing TBC1D8B expression - Hui Zhao; Lin-Lin Liu; Jian Sun; Lian Jin; Hai-Bing Xie; Jian-Bo Li; Hui Xu; Dong-Dong Wu; Xiao-Lin Zhuang; Min-Sheng Peng; Ya-Jun Guo; Wei-Zhu Qian; et al. (Science China Life Sciences, 2024)

Modulation of plasmacytoid dendritic cell and CD4+ T cell differentiation accompanied by upregulation of the cholinergic anti-inflammatory pathway induced by enterovirus 71 - Li Li; Rong-Wei Huang; Xiao-Ning Liu; Xiao-Yi Xiang; Yuan-Tao Zhou; Xing-Xing Feng; Lv-Yuan Tao; Jia Yu; Qin Yi; Yan-Chun Wang; Xiao-Mei Liu (Archives of Virology, 2024)

Measuring ecosystem services and ecological sensitivity for comprehensive conservation in Giant Panda National Park - Cheng Li; Rong Hou; Ziqiang Bao; Wei Wu; Jacob R. Owens; Wenlei Bi; Qiang Xu; XiaoDong Gu; Zuofu Xiang; Dunwu Qi (Conservation Biology, 2024)
China announced the development of its first 5 national parks in 2021, the primary objective of which is to conserve the natural state and integrity of natural ecosystems. As such, ecosystem services and biodiversity levels are crucial assessment factors for the parks. For Giant Panda National Park (GPNP), we evaluated ecological sensitivity based on water and soil erosion and rocky desertification; ecosystem services based on headwater conservation, soil and water conservation, and biodiversity conservation; and presence of giant panda ( Ailuropoda melanoleuca ) and sympatric species (e.g., takin [ Budorcas taxicolor ], Asiatic black bear [ Ursus thibetanus ]) habitat suitability derived from niche modeling to identify the ecosystem status and assess ecological problems within the park. From our results, we proposed ecologically critical areas to target to meet the park's goals. The suitable habitat for pandas and sympatric species encompassed 62.98% of the park and occurred mainly in the Minshan Mountains. One quarter of the total area (25.67%) contained areas important for ecosystem services. Ecologically sensitive and extremely sensitive areas covered 88.78% of the park and were distributed mainly in Qionglaishan and Minshan Mountains. This coverage indicated that there was much habitat for pandas and sympatric species but that the ecosystems in GPNP are vulnerable. Therefore, ecologically critical areas encompassed all suitable habitats for all the species examined and areas important and extremely important to ecosystem service provision,ecologically sensitive and extremely sensitive areas, encompassed 15.17% of panda habitat, accounted for 16.37% of the GPNP area, and were distributed mainly in the Minshan Mountains. Our results indicated where conservation efforts should be focused in the park and that by identifying ecologically critical areas managers can provide targeted protection for wildlife habitat and ecosystems and effectively and efficiently protect the composite ecosystem. Additionally, our methods can be used to inform development of new national parks.

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

Adsorption characteristics of Ag+ on sphalerite surface: a combined experimental and first-principle study - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Environmental Science and Pollution Research, 2024)

Myosin heavy chain isoform expression and meat quality characteristics of different muscles in yak (Bos grunniens) - Xueyuan Bai; Feng Yin; Ang Ru; Ming Li; Wei Tian; Guiyan Zhang; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Hongmei Shi; Chaozhi Zhu; et al. (Meat Science, 2024)

Kinetics of fe-containing solid waste reduction by carbonaceous materials in CO2 atmosphere: The cause of reducing agent burnout during direct reduction treatment - Xin Li; Guangsheng Wei; Hongyang Wang; Bohan Tian; Rong Zhu; Yefeng Wang (Fuel, 2024)

Green space and its types can attenuate the associations of PM2.5 and its components with prediabetes and diabetes—— a multicenter cross-sectional study from eastern China - Zhiqian Cui; Rubing Pan; Jintao Liu; Weizhuo Yi; Yuxin Huang; Ming Li; Zichen Zhang; Lingmei Kuang; Li Liu; Ning Wei; Rong Song; Jiajun Yuan; et al. (Environmental Research, 2024)

TiO2-x modified Ni/SBA-15 catalysts for dibenzofuran hydrodeoxygenation - Yu-Kun Wang; Hao-Wei Li; Yu-Rong Liu; Zi-Zheng Xie; Zhen-Yi Du; Xing-Bao Wang; Wen-Ying Li (Chemical Engineering Journal, 2024)

Stereoisomerically enhanced polynorbornene-imide dielectric energy storage performance - Hongmei Qin; Man Liu; Shiyu Qin; Shixian Zhang; Xingnan Zhou; Chenjian Li; Yuhao Wei; Dan Chen; Rong Fan; Shan Wang; Quanling Yang; Chuanxi Xiong; et al. (Chemical Engineering Journal, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Effect of light intensity on the accumulation of protostane triterpenes in Asian water plantain (Alisma orientale) - Wenqing Wu; Simeng Li; Wei Gu; Rong Tian; Man Luo; Junjie Tang; Min Tang; Yinzhi Wu (Acta Physiologiae Plantarum, 2024)

A multi-species pest recognition and counting method based on a density map in the greenhouse - Zhiqin Zhang; Jiacheng Rong; Zhongxian Qi; Yan Yang; Xiajun Zheng; Jin Gao; Wei Li; Ting Yuan (Computers and Electronics in Agriculture, 2024)

Evidence for the transportation of aggregated microplastics in the symplast pathway of oilseed rape roots and their impact on plant growth - Sashuang Rong; Shutao Wang; Hongmei Liu; Yuxin Li; Jia Huang; Wanqing Wang; Bing Han; Shiming Su; Wei Liu (Science of The Total Environment, 2024)

Diisoprenyl-cyclohexene-type meroterpenoids from a mangrove endophytic fungus Aspergillus sp. GXNU-Y65 and their anti-nonalcoholic steatohepatitis activity in AML12 cells - Feng Qin; Li Luo; Yu-Chen Liu; Xiang-Long Bo; Fu-Rong Wu; Fan-Fan Wang; Mei-Jing Tan; You-Quan Wei; Xiao-Bing Dou; Cai Yi Wang; Xi-Shan Huang; Heng-Shan Wang (Phytochemistry, 2024)

Experimental and computational study on the adsorption mechanism of silver ions on galena surface - Heng Yu; Hongliang Zhang; Chenyang Zhang; Wei Sun; Mingjun Han; Rong Wang; Xin Wei; Songjiang Li (Journal of Water Process Engineering, 2024)

High-efficient sunlight-driven hydrogen production from methanol steam reforming on a novel photo-thermo-catalysis and thermo-catalysis dual-bed reactor - Donghui Li; Jie Sun; Zhenwen Zhang; Rong Ma; Jinjia Wei (Fuel, 2024)

A study of volatiles of young citrus fruits from four areas based on GC–MS and flash GC e-nose combined with multivariate algorithms - Qian Zhang; Rong Xue; Xi Mei; Lianlin Su; Wei Zhang; Yu Li; Jinguo Xu; Jing Mao; Chunqin Mao; Tulin Lu (Food Research International, 2024)

Constructing mesoporous biochar derived from waste carton: Improving multi-site adsorption of dye wastewater and investigating mechanism - Yan-Shan Wang; Tong-Rong Huo; Yan Wang; Jia-Wen Bai; Ping-Ping Huang; Chen Li; Shi-Yu Deng; Hong Mei; Jun Qian; Xiao-Chi Zhang; Chen Ding; Qiu-Yu Zhang; et al. (Environmental Research, 2024)

Composite aerogel incorporating low temperature phase change microcapsules for enhanced thermal insulation - Bin Yan; Min Li; Honglang Lu; Menghan Pi; Jiahao Mu; Wei Cui; Rong Ran (Chemical Engineering Journal, 2024)

Gut microbiome as a key monitoring indicator for reintroductions of captive animals - Guangping Huang; Dunwu Qi; Zhisong Yang; Rong Hou; Wenyu Shi; Fangqing Zhao; Zitian Li; Li Yan; Fuwen Wei (Conservation Biology, 2024)
Reintroduction programs seek to restore degraded populations and reverse biodiversity loss. To examine the hypothesis that gut symbionts could be used as an indicator of reintroduction success, we performed intensive metagenomic monitoring over 10 years to characterize the ecological succession and adaptive evolution of the gut symbionts of captive giant pandas reintroduced to the wild. We collected 63 fecal samples from 3 reintroduced individuals and 22 from 9 wild individuals and used 96 publicly available samples from another 3 captive individuals. By microbial composition analysis, we identified 3 community clusters of the gut microbiome (here termed enterotypes ) with interenterotype succession that was closely related to the reintroduction process. Each of the 3 enterotypes was identified based on significant variation in the levels of 1 of 3 genera: Clostridium , Pseudomonas , and Escherichia . The enterotype of captive pandas was Escherichia . This enterotype was gradually replaced by the Clostridium enterotype during the wild‐training process, which in turn was replaced by the Pseudomonas enterotype that resembled the enterotype of wild pandas, an indicator of conversion to wildness and a successful reintroduction. We also isolated 1 strain of Pseudomonas protegens from the wild enterotype, a previously reported free‐living microbe, and found that its within‐host evolution contributed to host dietary adaptation in the wild. Monitoring gut microbial structure provides a novel, noninvasive tool that can be used as an indicator of successful reintroduction of a captive individual to the wild.

Anthropogenic disturbance driving population decline of a dominant tree in East Asia evergreen broadleaved forests over the last 11,000 years - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Shuang‐Xiu Xu; Jie Liu; Feng‐Mao Yang; Ya‐Huang Luo; Jun‐Wei Ye; Yao Zhao; Jun Rong; Bing Liu; Peng‐Fei Ma; De‐Zhu Li (Conservation Biology, 2024)
Current biodiversity loss is generally considered to have been caused by anthropogenic disturbance, but it is unclear when anthropogenic activities began to affect biodiversity loss. One hypothesis suggests it began with the Industrial Revolution, whereas others propose that anthropogenic disturbance has been associated with biodiversity decline since the early Holocene. To test these hypotheses, we examined the unique vegetation of evergreen broadleaved forests (EBLFs) in East Asia, where humans have affected landscapes since the early Holocene. We adopted a genomic approach to infer the demographic history of a dominant tree ( Litsea elongata ) of EBLFs. We used Holocene temperature and anthropogenic disturbance factors to calculate the correlation between these variables and the historical effective population size of L. elongata with Spearman statistics and integrated the maximum‐entropy niche model to determine the impact of climate change and anthropogenic disturbance on fluctuation in its effective population size. We identified 9 well‐defined geographic clades for the populations of L. elongata . Based on the estimated historical population sizes of these clades, all the populations contracted, indicating persistent population decline over the last 11,000 years. Demographic history of L . elongata and human population change, change in cropland use, and change in irrigated rice area were significantly negatively correlated, whereas climate change in the Holocene was not correlated with demographic history. Our results support the early human impact hypothesis and provide comprehensive evidence that early anthropogenic disturbance may contribute to the current biodiversity crisis in East Asia.

Microplastics enhance nitrogen loss from a black paddy soil by shifting nitrate reduction from DNRA to denitrification and Anammox - Xiaofang Ma; Jun Shan; Yanchao Chai; Zhijun Wei; Chenglin Li; Ke Jin; Han Zhou; Xiaoyuan Yan; Rong Ji (Science of The Total Environment, 2024)

Visualized test of environmental water pollution and meat freshness: Design of Au NCs-CDs-test paper/PVA film for ratiometric fluorescent sensing of sulfide - Yi Huang; Shiming Chen; Wei Huang; Xiaoting Zhuang; Jiahao Zeng; Mingcong Rong; Li Niu (Food Chemistry, 2024)

Preparation of size-tunable Fe3O4 magnetic nanoporous carbon composites by MOF pyrolysis regulation for magnetic resonance sensing of aflatoxin B1 with excellent anti-matrix effect - Zhou Xu; Yanqiu Chen; Rong Wang; Maolong Chen; Jian Zhang; Yunhui Cheng; Bangben Yao; Li Yao; Jianguo Xu; Wei Chen (Food Chemistry, 2024)

Interfacial coordination-assisted construction of mechanically robust, fluorescent and intumescent flame retardant epoxy resins - Xin-Miao Li; Wei-Bin Bai; Yu-Cai Lin; Fu-Chuan Ding; Rong-Kun Jian (Chemical Engineering Journal, 2024)

Predicting the velocity and trajectory of a rockfall after collision considering the effects of slope properties - Shao-Zhen Duan; Guang-Li Li; Xin Yang; Xin-Rong Wei (Natural Hazards, 2024)

Soil pH differently affects N2O emissions from soils amended with chemical fertilizer and manure by modifying nitrification and denitrification in wheat-maize rotation system - Gong Wu; Fei Liang; Qi Wu; Xiao-Gang Feng; Wen-ding Shang; Hua-wei Li; Xiao-xiao Li; Zhao Che; Zhao-rong Dong; He Song (Biology and Fertility of Soils, 2024)

Effect comparisons of different conditioners and microbial agents on the degradation of estrogens during dairy manure composting - Yan Li; Dong Zeng; Xiao-Lu Jiang; De-Chun He; Jia-Wu Hu; Zi-Wei Liang; Jia-Cheng Wang; Wang-Rong Liu (Chemosphere, 2023)

Advances, challenges, and prospects in microalgal-bacterial symbiosis system treating heavy metal wastewater - Xing-Rui Zhou; Rong Wang; Cong-Cong Tang; Cristiano Varrone; Zhang-Wei He; Zhi-Hua Li; Xiaochang C. Wang (Chemosphere, 2023)

Dynamic human exposure to airborne bacteria-associated antibiotic resistomes revealed by longitudinal personal monitoring data - Rong-min Zhang; Xin-lei Lian; Li-wei Shi; Liuyiqi Jiang; Shan-shan Chen; Wen-qing Haung; Jia-en Wu; Fei-jing Wu; Jian Sun; Xiao-ping Liao; Yun-xiao Chong; Ya-hong Liu; et al. (Science of The Total Environment, 2023)

Relative contribution of roots and symbiotic fungi to wheat nitrogen uptake and N2O emissions under straw burial - Zheng-Rong Kan; Yanling Li; Ruoyan Yang; Xinyu Yang; Qihang Wei; Ahmad Latif Virk; Jianying Qi; Feng-Min Li; Zichang Zhang; Haishui Yang (Rhizosphere, 2023)

Comparative study on characteristics of typhoon gusts in the coastal and offshore areas of the South China Sea - Qian-Jin Zhou; Lei Li; Shao-Jia Fan; Hong-Long Yang; Wei Sun; Hai-Rong Tang (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Preparation and characterization of polyvinyl alcohol/glutaraldehyde cross-linked chitosan/ε-Polylysine degradable composite film and its antibacterial effect - Shuangfeng Guo; Xiuyun Zhang; Rong Ma; Xiangzhen Ge; Huishan Shen; Wei Liang; Guoquan Zhang; Wenhao Li (Journal of Food Engineering, 2023)

Investigation on the catalytic performance of magnetic copper ferrite nanoparticles in the catalytic hydroconversion of Hanglaiwan long flame coal - Yong Gao; Wen-Xian Qin; Jin-Jun Bai; Qi-Yang Zhu; Xia-Long Li; Guang-Hui Liu; Xian-Yong Wei; Yu-Hong Kang; Yan-Jun Li; Xiang-Rong Ma; Zhi-Min Zong (Fuel, 2023)

Effect of geographical origins and pile-fermentation on the multi-element profiles of ripen Pu-erh tea revealed by comprehensive elemental fingerprinting - Jiayi Zhu; Le Chen; Yue Chen; Yuting Rong; Yongwen Jiang; Fuqiao Liu; Qinghua Zhou; Xuehong Wei; Haibo Yuan; Junjie Zhang; Jia Li (Food Control, 2023)

Endophytic Bacillus sp. R1 and Its Roles in Assisting Phytoremediation and Alleviating the Toxicity of Aluminum Combined Phenanthrene Contaminations in Brassica napus - Li-rong Fang; Xue-cheng Yang; Chun-ya Wu; Kai Sun; Mallavarapu Megharaj; Wei He (Current Microbiology, 2023)

Projected Regional 1.50°C and 2.00°C Warming Threshold-crossing Time Worldwide Using the CMIP6 Models - Yali Meng; Keqin Duan; Wei Shang; Peihong Shi; Shuangshuang Li; Ying Cheng; Rong Chen; Zhaopeng Zhang (Chinese Geographical Science, 2023)

Acquisition parameters and sensitivity analysis affecting the seismic imaging quality of the complex piedmont zone - Hu Zhao; Wen-jun Li; Yong Wu; Zhi-xin Di; Rong-rong Zhao; Wei Chen; Ming-yi Li (Applied Geophysics, 2023)

Mesocosm experimental study on sustainable riparian restoration using sediment-modified planting eco-concrete - Yi Li; Shengxiang Rong; Chi Zhang; Hongqiang Chu; Pengcheng Wei; Shiqiang Tao (Science of The Total Environment, 2023)

Over-expression of UDP-glycosyltransferase UGT353G2 confers resistance to neonicotinoids in whitefly (Bemisia tabaci) - Tian-hua Du; Cheng Yin; Lian-you Gui; Jin-jin Liang; Shao-nan Liu; Bu-li Fu; Chao He; Jing Yang; Xue-gao Wei; Pei-pan Gong; Ming-jiao Huang; Hu Xue; et al. (Pesticide Biochemistry and Physiology, 2023)

Curcumin-mediated photodynamic treatment extends the shelf life of salmon (Salmo salar) sashimi during chilled storage: Comparisons of preservation effects with five natural preservatives - Hui-Ming Chen; Quan Zhou; Li-Jun Huang; Jun Lin; Jia-Fei Liu; Zi-Yong Huang; Rong-Lin Zhang; Jing-Jing Wang; Yong Zhao; Yong-Ning Wu; Xing-Fen Yang; Wei-Liang Wu (Food Research International, 2023)

Revealing mechanisms of triclosan on the removal and distribution of nitrogen and phosphorus in microalgal-bacterial symbiosis system - Sheng-Long Chen; Tian-Yang Wang; Cong-Cong Tang; Rong Wang; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2023)

Quantum chemical calculation assisted efficient lithium extraction from unconventional oil and gas field brine by β-diketone synergic system - Yunze Zhao; Huifang Xing; Meng Rong; Zheng Li; Xuetuan Wei; Congmei Chen; Huizhou Liu; Liangrong Yang (Desalination, 2023)

Hydrogel-based intelligent greenhouse films for simultaneous fogging prevention and indoor environmental monitoring - Honglang Lu; Huanxiong Liang; Jianle Liu; Hui Zhou; Menghan Pi; Min Li; Bin Yan; Wei Li; Wei Cui; Rong Ran (Chemical Engineering Journal, 2023)

Feeding-induced plant metabolite responses to a phoretic gall mite, its carrier psyllid and both, after detachment - Mengke Yang; Jianling Li; Haili Qiao; Kun Guo; Rong Xu; Hongshuang Wei; Jianhe Wei; Sai Liu; Changqing Xu (Experimental and Applied Acarology, 2023)

Mesoscopic measurement of damage and shear bands of granite residual soil using Micro-CT and digital volume correlation - Cheng-sheng Li; Bing-xin Zhang; Zhi-jun Liu; Ling-wei Kong; Rong-jun Shu (Journal of Mountain Science, 2023)

Hydrogeochemical characterization and precursor anomalies of hot springs in the North Tianshan orogen - Zhihua Ding; Xiaocheng Zhou; Chengguo Wang; Jingchao Li; Miao He; Jiao Tian; Kayimu Saimaiernaji; Chengying Zhu; Wei Yan; Rong Ma; Xinyong Li; Na Li; et al. (Applied Geochemistry, 2023)

Evaluation of the toxicity of clozapine on the freshwater diatom Navicula sp. using the FTIR spectroscopy - Hao-Jun Lei; Xin-Rong Wei; Li-Xia Li; Wei-Jun Sun; Hong-Xing Chen; Dan Li; Lingtian Xie (Chemosphere, 2023)

Residual chlorine persistently changes antibiotic resistance gene composition and increases the risk of antibiotic resistance in sewer systems - Jingyi Zhang; Zuxin Xu; Wenhai Chu; Feng Ju; Wei Jin; Peng Li; Rong Xiao (Water Research, 2023)

An integrative analysis of lipidomics and transcriptomics in various mouse brain regions in response to real-ambient PM2.5 exposure - Shuangjian Qin; Huixian Zeng; Qizhen Wu; Qingqing Li; Mohammed Zeeshan; Lizhu Ye; Yue Jiang; Rui Zhang; Xinhang Jiang; Miao Li; Rong Zhang; Wen Chen; et al. (Science of The Total Environment, 2023)

Research advancement on magnetic nanomaterial demulsifier for oil-water separation - Rong Wang; Junyi Li; Haigang Zhou; Siyuan Liu; Wei Sun; Chenyang Zhang (Journal of Environmental Chemical Engineering, 2023)

Forest degradation caused by dwarf bamboo overabundance reduces soil C, N and P stocks in giant panda habitat - Li Mo; Hao Yang; Rong Hou; Wei Wu; Xinqiang Song; Hong Yang; Zhisong Yang; Weichao Zheng; Dunwu Qi (CATENA, 2023)

Icariin inhibits hypertrophy by regulation of GPER1 and CaMKII/HDAC4/MEF2C signaling crosstalk in ovariectomized mice - Wenxia Zhao; Xiaoli Shan; Xueqin Li; Shuang Lu; Lei Xia; Huihua Chen; Chen Zhang; Wei Guo; Ming Xu; Rong Lu; Pei Zhao (Chemico-Biological Interactions, 2023)

Insights into roles of triclosan in microalgal–bacterial symbiosis system treating wastewater - Cong-Cong Tang; Tian-Yang Wang; Rong Wang; Cristiano Varrone; Zixuan Gan; Zhang-Wei He; Zhi-Hua Li; Xiaochang C. Wang (Bioresource Technology, 2023)

Sensitive temperature changes on the Tibetan Plateau in response to global warming - Yali Meng; Keqin Duan; Peihong Shi; Wei Shang; Shuangshuang Li; Ying Cheng; Li Xing; Rong Chen; Jinping He (Atmospheric Research, 2023)

Citrus medica var. Sarcodactylus (Siebold ex Hoola van Nooten) Swingle: an insight into its botany, traditional uses, phytochemistry, and pharmacological properties - Qin-Ge Ma; Jie Chen; Li-Hua Chen; Guang Wu; Mei-Ning Zhu; Neng-Xin He; Qin-Yuan Wang; Zhi-Pei Sang; Cai-Qing Zhu; Yong-Zhong Wu; Rong-Rui Wei (Phytochemistry Reviews, 2023)

Characterization of the fragmented mitochondrial genome of domestic pig louse Haematopinus suis (Insecta: Haematopinidae) from China - Rong Li; Yu Nie; Yi-Tian Fu; Yuan-Ping Deng; Wei Wang; Ping-Ping Ma; Guo-Hua Liu (Systematic Parasitology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

The global burden of schizophrenia and the impact of urbanization during 1990–2019: An analysis of the global burden of disease study 2019 - Xuanxuan Li; Ning Wei; Jian Song; Jintao Liu; Jiajun Yuan; Rong Song; Li Liu; Lu Mei; Shuangshuang Yan; Yudong Wu; Rubing Pan; Weizhuo Yi; et al. (Environmental Research, 2023)

Experimental investigation of the seismic resistance of RC beam–column connections after freeze–thaw cycle treatment - Xian-Liang Rong; Lei Li; Wei-Yuan Huang; Li-Guo Dong; Shan-Suo Zheng; Feng Wang; Dong Lu; Jun-Yan Wang (Engineering Structures, 2023)

Performance and mechanism of different pretreatment methods for inoculated sludge in biohydrogen production - Wei-xin Cheng; Ling-ling Wang; Yun Xu; Si-jia Li; Quan Wang; Rong-ping Chen; Lei Yu (Bioresource Technology, 2023)

Spautin-1 Protects Against Mild TBI-Induced Anxiety-Like Behavior in Mice via Immunologically Silent Apoptosis - Hui-Tao Miao; Rong-Xin Song; Yue Xin; Lu-Ying Wang; Jin-Meng Lv; Na-Na Liu; Zhi-You Wu; Wei Zhang; Yan Li; Dong-Xue Zhang; Li-Min Zhang (NeuroMolecular Medicine, 2023)

Arbuscular mycorrhizal fungi mitigate earthworm-induced N2O emissions from upland soil in a rice-rotated wheat farming system - Zheng-Rong Kan; Qihang Wei; Ruoyan Yang; Yanling Li; Jiajia Zhou; Jianying Qi; Feng-Min Li; Haishui Yang (Applied Soil Ecology, 2023)

Hyperglycemia symptom amelioration by Ascophyllum nodosum polysaccharides in mice with type 2 diabetes - Ligen Chen; Liang Shen; Lingyun Zhu; Fengwei Li; Xiaodong Ge; Xiujuan Xia; Hongwei Yan; Tingting Liu; Wei Xu; Rong Shao (Algal Research, 2023)

The association between greenery type and gut microbiome in schizophrenia: did all greenspaces play the equivalent role? - Ning Wei; Shusi Wang; Xuanxuan Li; Rubing Pan; Weizhuo Yi; Jian Song; Li Liu; Jintao Liu; Jiajun Yuan; Rong Song; Jian Cheng; Hong Su (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Detection of spatiotemporal changes in ecological quality in the Chinese mainland: Trends and attributes - Yang Li; Haifeng Tian; Jingfei Zhang; Siqi Lu; Zhixiang Xie; Wei Shen; Zhicheng Zheng; Mengdi Li; Peijun Rong; Yaochen Qin (Science of The Total Environment, 2023)

Novel_miR-1517 mediates CYP6CM1 to regulate imidacloprid resistance in Bemisia tabaci (Hemiptera: Gennadius) - Pei-Pan Gong; Xue-Gao Wei; Shao-Nan Liu; Jing Yang; Bu-Li Fu; Jin-Jin Liang; Ming-Jiao Huang; Tian-Hua Du; Cheng Yin; Yao Ji; Chao He; Jin-Yu Hu; et al. (Pesticide Biochemistry and Physiology, 2023)

Cytochrome P450 CYP6DB3 was involved in thiamethoxam and imidacloprid resistance in Bemisia tabaci Q (Hemiptera: Aleyrodidae) - Xuegao Wei; Jinyu Hu; Jing Yang; Cheng Yin; Tianhua Du; Mingjiao Huang; Buli Fu; Peipan Gong; Jinjin Liang; Shaonan Liu; Hu Xue; Chao He; et al. (Pesticide Biochemistry and Physiology, 2023)

Effect of slaughter age and postmortem aging time on tenderness and water-holding capacity of yak (Bos grunniens) longissimus thoracis muscle - Xueyuan Bai; Feng Yin; Ang Ru; Wei Tian; Qingwen Chen; Rong Chai; Yanxia Liu; Wenming Cui; Jiahui Li; Mancai Yin; Chaozhi Zhu; Gaiming Zhao (Meat Science, 2023)

Ultra-stable 3D pyridinium salt-based polymeric network nanotrap for selective 99TcO4-/ReO4- capture via hydrophobic and steric engineering - Wei Xu; Xiu Wang; Yibao Li; Wei-Rong Cui (Journal of Hazardous Materials, 2023)

Ejiao peptide-iron chelates regulate the metabolism of iron deficiency anemia mice and improve the bioavailability of iron - Xiang-Rong Cheng; Yu-Yao Chen; Cong-Cong Cao; Jia-Hui Ma; Chen-Xi Zhang; Zi-Wei Zhao; Qian Wu; Yuan-Yuan Li; Mitchell N. Muskat; Guo-Qing Wu (Food Bioscience, 2023)

Coupled behaviour and strength prediction of tapered CFDST columns with large hollow ratios for wind turbine towers - Ran Deng; Xu-Hong Zhou; Wei-Dong Ji; Rong-Fu Li; Shuai-Quan Zheng; Yu-Hang Wang (Engineering Structures, 2023)

CORM-3 alleviates the intestinal injury in a rodent model of hemorrhage shock and resuscitation: roles of GFAP-positive glia - Li-Min Zhang; Yue Xin; Rong-Xin Song; Wei-Chao Zheng; Jin-Shu Hu; Jie-Xia Wang; Zhi-You Wu; Dong-Xue Zhang (Journal of Molecular Histology, 2023)

Characteristics of mesenchymal stem cells and their exosomes derived from giant panda (Ailuropoda melanoleuca) endometrium - Yu-Liang Liu; Jia-Song Chen; Jun-Hui An; Zhi-Gang Cai; Jing-Chao Lan; Yuan Li; Xiang-Wei Kong; Ming-Yue Zhang; Rong Hou; Dong-Hui Wang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Shape Classification of Cloud Particles Recorded by the 2D-S Imaging Probe Using a Convolutional Neural Network - Rong Zhang; Haixia Xiao; Yang Gao; Haizhou Su; Dongnan Li; Lei Wei; Junxia Li; Hongyu Li (Journal of Meteorological Research, 2023)

Identification and characterization of goat milk key flavor compounds and their precursors in electron beam irradiation and pasteurization on raw - Chunlu Wen; Ya Chen; Madina; Linlu Zhang; Yue Peng; Bai Rong; Linjie Xi; Shengqi Jiang; Jiangtao Yu; Junqing Bai; Niu Wei; Li Kui; et al. (Innovative Food Science & Emerging Technologies, 2023)

Corrigendum to “Co-folding of soy protein isolates and shellac by structural interplays to induce hydrogels” [Food Hydrocolloids 139 (2023) 108527] - Yang Guo; Zhi-guo Zhang; Jing Cai; Wei-rong Li; Ling-yun Chen; Wei-cheng Wu (Food Hydrocolloids, 2023)

Preparation and mechanism of carbon felt supported iron trioxide and zero-valent iron for enhancing anaerobic digestion performance - Zheng-Wei Wang; Chun-Hai WEI; Hua-Rong Yu; Fang-Shu Qu; Hong-Wei Rong; Jun-Guo He; Guang-Li Liu; Xia Huang; Huu Hao Ngo (Chemical Engineering Journal, 2023)

Investigating the thermal conductivity and flame-retardant properties of BN/MoS2/PCNF composite film containing low BN and MoS2 nanosheets loading - Lei Yang; Wei Xu; Xiaolong Shi; Menglin Wu; Ziyi Yan; Qing Zheng; Gongneng Feng; Li Zhang; Rong Shao (Carbohydrate Polymers, 2023)

Segmentation of retinal vessels in fundus images based on U-Net with self-calibrated convolutions and spatial attention modules - YiBiao Rong; Yu Xiong; Chong Li; Ying Chen; Peiwei Wei; Chuliang Wei; Zhun Fan (Medical & Biological Engineering & Computing, 2023)

Effect of wheat crop height and canopy coverage on microsprinkling hose irrigation uniformity - Wenjuan Wang; Wene Wang; Rong Wei; Gang Ling; Hong Li; Xiaotao Hu (Irrigation and Drainage, 2023)
Crop shading affects irrigation uniformity and water distribution under microsprinkling hose irrigation (MHI). This study aims to ascertain how MHI distributes irrigation water under crop shading. Various crop heights and canopy coverages of wheat specimens were designed. The experiment was conducted under four working pressures (20, 24, 28 and 32 kPa). The irrigation water distribution of the MHI under crop shading was analysed under various crop heights and canopy coverages. The results showed that (1) the irrigation uniformity of MHI could reach approximately 50% while the planting row spacing of wheat was appropriate. Crop shading had little effect on irrigation performance. (2) During the jointing period, when the wheat height reached 0.4 m, intensive stems reduced the irrigation uniformity and spraying range of MHI. (3) The wheat height could reach 0.6–0.7 m in the maturing period. The uniformity was 25%–50%, which was far lower than the effect of irrigation during the jointing period. To obtain great irrigation performance and acceptable crop yield, it is important to select the proper pressure under the various crop heights and canopy coverages of wheat under MHI.

Spatiotemporal characteristics of high winds in Jilin Province during 1982–2021 - Xiao Wei; Kaiwei Li; Yunmeng Zhao; Yueting Yang; Guangzhi Rong; Ying Guo; Jiquan Zhang (International Journal of Climatology, 2023)
High winds are a type of catastrophic weather characterized by wind speeds over 10.8 m·s −1 , occurring in all seasons, and have become more frequent, impacting crop growth, agricultural production and quality of life. It is crucial to understand the spatial and temporal distribution patterns of high winds, as well as their speed and other characteristics, for logical planning of agricultural production and the creation of disaster resilience measures. This study applied the climate tendency, accumulative anomalies, theory of run, Mann–Kendall trend and Theil–Sen median to analyse the spatial and temporal distribution characteristics of the average wind speed and high wind days in Jilin Province, the probability of occurrence of high winds of various magnitudes in different eras, and the gale concentration degree (GCD) throughout Jilin Province for a total of 40 years from 1982 to 2021. The average wind speed and number of high wind days in Jilin Province have decreased over the past 40 years, and this trend has slowed over time. The average GCD in Jilin Province has shown an increasing trend over the last 40 years, with the average GCD being highest in Liouhe and lowest in Linjiang. In general, level six high winds were the main wind hazard level in Jilin Province, with the highest frequency occurring in different seasons and decades. In addition, the occurrence of high wind days is affected by global climate change and different underlying surfaces, which leads to maize and yield reduction. Research on the spatiotemporal distribution of high winds can provide important suggestions for the prevention and management of high wind disasters.

The spatial distribution, health risk, and cytotoxicity of metal(loid)s in contaminated field soils: The role of Cd in human gastric cells damage - Jiao-Yang Ma; Wei-Yu Li; Zi-Yue Yang; Jin-Zhou Su; Li Li; Yi-Rong Deng; Yun-Fei Tuo; You-Ya Niu; Ping Xiang (Science of The Total Environment, 2023)

Quantum oscillations in field-induced correlated insulators of a moiré superlattice - Le Liu; Yanbang Chu; Guang Yang; Yalong Yuan; Fanfan Wu; Yiru Ji; Jinpeng Tian; Rong Yang; Kenji Watanabe; Takashi Taniguchi; Gen Long; Dongxia Shi; et al. (Science Bulletin, 2023)

Nudifloids A-N, structurally diverse 3,4-seco-labdane diterpenoids from Callicarpa nudiflora with inflammatory inhibitory activity - Xue-Rong Zhao; Xiao-Rong Sun; Xing-Jie Zhang; Xue-Wen Wu; Bin Cheng; Dong-Xuan Ni; Jia-Bi Huang; Rui-Han Zhang; Xiao-Li Li; Wei-Lie Xiao (Phytochemistry, 2023)

Toward a unified and refined Ordovician stratigraphy for the western Yangtze region, South China - Guang-Xu Wang; Yu-Nong Cui; Yan Liang; Rong-Chang Wu; Xin Wei; Fang-Yi Gong; Bing Huang; Xiao-Cong Luan; Peng Tang; Li-Xia Li; Xiao-Le Zhang; Yi-Chi Zhang; et al. (Palaeoworld, 2023)

The impact of inorganic ions on the solar photolysis of chlorinated dissolved organic matter from different sources: Spectral characteristics, disinfection byproducts, and biotoxicities - Yali An; Xiaoyan Y. Ma; Wenfeng Chen; Wei Li; Siyan Yang; Rong Chen; Xiaochang C. Wang (Journal of Hazardous Materials, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

Coaxial electrospun nanofibrous substrates with tunable wettability for constructing cucurbit[n]uril-embedded organic solvent nanofiltration membranes - Qian Wang; Qin-Yuan He; Liu-Lin Zhao; Yue Wang; Rong Fang; Cong Luo; Wei-Tong Lu; Hong-Ya Jiang; Shi-Peng Sun; Xue-Li Cao (Chemical Engineering Journal, 2023)

Receiver function imaging of dense seismic array and deep dynamic mechanism beneath the eastern South China - Rubing Han; Dinghui Yang; Qiusheng Li; Rong Huang; Hongshuang Zhang; Jiangtao Li; Hao Chen; Zhuo Ye; Wei Fu (Science China Earth Sciences, 2023)

Proteomics Analysis of Lipid Metabolism and Inflammatory Response in the Liver of Rabbits fed on a High Cholesterol Diet - Jing Wu; Wei-Hua Li; Wei-Rong Wang; Xue-Qin Jin; En-Qi Liu (Cell Biochemistry and Biophysics, 2023)

Establishment of Agrobacterium-mediated transformation system to Juglans sigillata Dode ‘Qianhe-7’ - Rong Wei; Wen’e Zhang; Chunxiang Li; Zhenkun Hao; Dong Huang; Wenlong Zhang; Xuejun Pan (Transgenic Research, 2023)

Chinese version of the auditory verbal learning test: normative study and clinical applications in Chinese-speaking population in Shijiazhuang city - Fang-Ming Dong; Wei Wang; Shang-Zun Guo; Kai Shao; Ya-Xue Song; Ning Han; Yan-Li Jia; Rong-Fang Feng; Jian-Hua Wang (Acta Neurologica Belgica, 2023)

Sunshine duration and risks of schizophrenia hospitalizations in main urban area: Do built environments modify the association? - Li Liu; Qing Wu; Xuanxuan Li; Rong Song; Ning Wei; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Mesoporous zeolite Beta supported Ni nanoparticles for the catalytic hydroconversion of extraction portion from Jinjitan subbituminous coal to cycloalkanes - Juan Gao; Xian-Yong Wei; Yu-Hong Kang; Xiao-Qi Zhang; Ai-Min Wang; Xia-Long Li; Yong Gao; Guang-Hui Liu; Tao Chen; Yan-Jun Li; Xiang-Rong Ma; Jin-Jun Bai; et al. (Fuel, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Air-water interfacial properties and quantitative description of pea protein isolate-Tween 20 - Qian Shen; Wei Zheng; Fei Han; Jingnan Zuo; Jun Dai; Cuie Tang; Rong Song; Bin Li; Yijie Chen (Food Hydrocolloids, 2023)

Co-folding of soy protein isolates and shellac by structural interplays to induce hydrogels - Yang Guo; Zhi-guo Zhang; Jing Cai; Wei-rong Li; Ling-yun Chen; Wei-cheng Wu (Food Hydrocolloids, 2023)

Microplastics affect arsenic bioavailability by altering gut microbiota and metabolites in a mouse model - Shan Chen; Jin-Lei Yang; Yao-Sheng Zhang; Hong-Yu Wang; Xin-Ying Lin; Rong-Yue Xue; Meng-Ya Li; Shi-Wei Li; Albert L. Juhasz; Lena Q. Ma; Dong-Mei Zhou; Hong-Bo Li (Environmental Pollution, 2023)

Essential Trace Element Status in Systemic Lupus Erythematosus: a Meta-analysis Based on Case-Control Studies - Hua Wang; Xian-Bao Li; Rong-Gui Huang; Nv-Wei Cao; Hong Wu; Kai-Di Li; Yi-Yu Wang; Bao-Zhu Li (Biological Trace Element Research, 2023)

A pair of new oxindole alkaloids isolated from Uncaria macrophylla - Xin-Xin Liang; Jin-Xuan Yang; Jian-Mei Li; Jia-Bi Huang; Liu-Meng Yang; Tian-Tian Sun; Rong-Hua Luo; Wei-Lie Xiao; Yong-Tang Zheng; Xiao-Li Li (Natural Product Research, 2023)

Bioaccumulation determines the toxicity of carbon dots to two marine dinoflagellates - Yue-Yue Liu; Jia-Meng Li; Rong Ji; Hongguo Zhang; Wei Zhang; Ai-Jun Miao (Chemosphere, 2023)

Intensification of the East Asian winter monsoon resulted in greater preservation of terrestrial organic carbon on the inner shelf of the East China Sea since the last 1400 years - Shuai Liu; Da-Wei Li; Rong Xiang; Meng Yu; Hailong Zhang; Li Li; Meixun Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Complete genome sequence of one novel marine Pseudomonas sp. BSw22131 growing with dimethylsulfoniopropionate (DMSP) as the sole carbon source - Ting Hu; Yin-Xin Zeng; Yi-He Zhang; Yu Du; Wei Han; Hui-Rong Li; Wei Luo (Marine Genomics, 2023)

Whole-genome sequencing reveals putative underlying mechanisms of biocontrol capability of IBFCBF-5 - Chen Luo; Ai-rong Shen; Ye-song Ren; Yang Zhai; Yi Cheng; Jianping Xu; Lin Wei; Ji-lie Li; Liang-bin Zeng (Acta Physiologiae Plantarum, 2023)

Nogo-A Mediated Endoplasmic Reticulum Stress During Myocardial Ischemic-Reperfusion Injury in Diabetic Rats - Yonghong Xiong; Yan Leng; Wei Li; Wenyuan Li; Hao Tian; Jie Tao; Rong Chen; Zhongyuan Xia (Cardiovascular Toxicology, 2023)

Evaluation of negative effect of Naphthenic acids (NAs) on physiological metabolism and polycyclic aromatic hydrocarbons adsorption of Phragmites australis - Hui Jia; Guang-xi Zhang; Yi-fan Wu; Wei-wei Dai; Quan-bin Xu; Shu Gan; Xiu-yun Ju; Zhao-zhong Feng; Rong-peng Li; Bo Yuan (Chemosphere, 2023)

Olefin-linked cationic covalent organic frameworks for efficient extraction of ReO4−/99TcO4− - Wei-Rong Cui; Wei Xu; Yi-Ru Chen; Kai Liu; Wei-Bin Qiu; Yibao Li; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Properties and application of thixotropic cement paste backfill with molybdenum tailings - Shan Gao; Wei Li; Kekuo Yuan; Chuanxin Rong (Journal of Cleaner Production, 2023)

Evaluation of moisture migration characteristics of permeable asphalt pavement: Field research - Rong Lu; Wei Jiang; Jingjing Xiao; Dongdong Yuan; Yupeng Li; Yukai Hou; Congcong Liu (Journal of Environmental Management, 2023)

The impact of hazes on schizophrenia admissions and the synergistic effect with the combined atmospheric oxidation capacity in Hefei, China - Jiajun Yuan; Weiwei Chang; Zhenhai Yao; Liying Wen; Jintao Liu; Rubing Pan; Weizhuo Yi; Jian Song; Shuangshuang Yan; Xuanxuan Li; Li Liu; Ning Wei; et al. (Environmental Research, 2023)

Shaking table tests and seismic assessment of a full-scale precast concrete sandwich wall panel structure with bolt connections - Jia-Xuan He; Zhao-Dong Xu; Lian-Yu Zhang; Zhi-Hua Lin; Zhong-Wei Hu; Qiang-Qiang Li; Yao-Rong Dong (Engineering Structures, 2023)

Achieving ultrahigh energy storage properties with superior stability in novel (Ba(1-)Bi )(Ti(1-)Zn0.5Sn0.5)O3 relaxor ferroelectric ceramics via chemical modification - Ming Yin; Guang-Jian Bai; Peng Li; Ji-Gong Hao; Wei Li; Wei-Fang Han; Yu-Chao Li; Chun-Ming Wang; Guo-Rong Li; Peng Fu (Chemical Engineering Journal, 2023)

Constructing redox-active 3D covalent organic frameworks with high-affinity hexameric binding sites for enhanced uranium capture - Yi-Ru Chen; Xiu Wang; Wei Xu; Kai Liu; Wei-Bin Qiu; Yongquan Wu; Yibao Li; Wei-Rong Cui (Chemical Engineering Journal, 2023)

Dual-functional electrostatic self-assembly nanoparticles enable suppressed defects and improved charge transport in perovskite optoelectronic devices - Hu Zhang; Pengfei Xu; Zhiliang Chen; Hengkai Zhang; Wenlong Shao; Yanhui Li; Jianfeng Yao; Da Rong; Duanwangde Liu; Liangpan Yang; Siliang Wang; Pengbin Gui; et al. (Chemical Engineering Journal, 2023)

Effects of long-term grazing exclusion on vegetation structure, soil water holding capacity, carbon and nitrogen sequestration capacity in an alpine meadow on the Tibetan Plateau - Yong-sheng Yang; Fa-wei Zhang; Xian-rong Xie; Jun-bang Wang; Ying-nian Li; Xiao-tao Huang; Hui-ting Li; Hua-kun Zhou (Journal of Mountain Science, 2023)

Pipeline positioning by the surface-to-borehole electromagnetic induction method in a clayey deposit - Guo-Wei Li; Zhi-Ming Ye; Yang Zhou; Guan-Jun He; Guang-Yu Liu; Xin-Rong He (Applied Geophysics, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Exosome proteomics study of the effects of traditional cigarettes and electronic cigarettes on human bronchial epithelial cells - Weiling Wang; Rong Zeng; Min Liu; Mulan Chen; Shiqin Wei; Bowen Li; Suhong Yu (Toxicology in Vitro, 2023)

Soil organic carbon regulates CH4 production through methanogenic evenness and available phosphorus under different straw managements - Zheng-Rong Kan; Zirui Wang; Wei Chen; Ahmad Latif Virk; Feng-Min Li; Jian Liu; Yaguang Xue; Haishui Yang (Journal of Environmental Management, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Facile synthesis of spiro-core-based hole-transporting material for high-performance and stable perovskite solar cells - Kun-Mu Lee; Seid Yimer Abate; June Hung Yang; Wei-Hao Chiu; Seoungjun Ahn; Sie-Rong Li; Kang-Ling Liau; Yu-Tai Tao; Yan-Duo Lin (Chemical Engineering Journal, 2023)

Selective separation of volatile fatty acids, nitrogen and phosphorus from anaerobic acidogenic fermentation via forward osmosis membrane process - Xian-Zheng Zhu; Long-Fei Wang; Xin-Rong Pan; Feng Zhang; Min-Sheng Huang; Wen-Wei Li; Hou-Qi Liu (Chemical Engineering Journal, 2023)

A glyoxylate-containing benzene derivative and butenolides from a marine algicolous fungus Aspergillus sp. SCSIO 41304 - Xin Qi; Wei-Hao Chen; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Yong-Hong Liu; Jun-Feng Wang; Yong Li (Natural Product Research, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

An in silico and in vitro integrated analysis method to reveal the curative mechanisms and pharmacodynamic substances of Bufei granule on chronic obstructive pulmonary disease - Yuan-yuan Ma; Rong Li; Zhi-xian Shang; Wei Liu; Xin-yi Jiao; Liu-yi Liang; Rui Liu; Zheng Li (Molecular Diversity, 2023)

Coexistence of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) and IgA nephropathy - Qi Xiong; Wei Lin; Chanjuan Shen; Ting Meng; Rong Tang; Joshua D. Ooi; Peter J. Eggenhuizen; Jinbiao Chen; Wannian Nie; Xia Li; Qiaoling Zhou; Ping Xiao; et al. (Immunologic Research, 2023)

Evaluation of deep learning algorithms for landslide susceptibility mapping in an alpine-gorge area: a case study in Jiuzhaigou County - Di Wang; Rong-hao Yang; Xiao Wang; Shao-da Li; Jun-xiang Tan; Shi-qi Zhang; Shuo-you Wei; Zhang-ye Wu; Chao Chen; Xiao-xia Yang (Journal of Mountain Science, 2023)

Proactive therapeutic drug monitoring of vincristine in pediatric and adult cancer patients: current supporting evidence and future efforts - Chun-Ying Wu; Guan-Ting Li; Chen-Chao Chu; Hong-Li Guo; Wei-Rong Fang; Tao Li; Yong-Ren Wang; Jing Xu; Ya-Hui Hu; Li Zhou; Feng Chen (Archives of Toxicology, 2023)

Personalizing atomoxetine dosing in children with ADHD: what can we learn from current supporting evidence - Di Fu; Hong-Li Guo; Ya-Hui Hu; Wei-Rong Fang; Qian-Qi Liu; Jing Xu; Dan-Dan Wu; Feng Chen (European Journal of Clinical Pharmacology, 2023)

Trends in drought and effects on carbon sequestration over the Chinese mainland - Yang Li; Mengdi Li; Zhicheng Zheng; Wei Shen; Yanan Li; Peijun Rong; Yaochen Qin (Science of The Total Environment, 2023)

Short-term exposure to air pollution is an emerging but neglected risk factor for schizophrenia: A systematic review and meta-analysis - Rong Song; Li Liu; Ning Wei; Xuanxuan Li; Jintao Liu; Jiajun Yuan; Shuangshuang Yan; Xiaoni Sun; Lu Mei; Yunfeng Liang; Yuxuan Li; Xiaoyu Jin; et al. (Science of The Total Environment, 2023)

Zero-valent iron boosts nitrate-to-ammonia bioconversion via extracellular electron donation and reduction pathway complementation - Xue Li; Jie Li; Xiao-Rong Yu; Yong-Kun Zhu; Hou-Qi Liu; Lin Chen; Jing Wu; Xian-Zhong Fu; Shuo Cui; Tian-Yin Huang; Ru-Quan Ye; Wen-Wei Li (Resources, Conservation and Recycling, 2023)

Strengthen the purification of eutrophic water and improve the characteristics of sediment by functional ecological floating bed suspended calcium peroxide and sponge iron jointly - Zheng Zhu; Yi Wang; Xue-Yi Han; Wen-Huai Wang; Hao-Min Li; Zi-Qi Yue; Wei Chen; Fu-Rong Xue (Journal of Environmental Management, 2023)

Quantitative monitoring and potential mechanism of the secondary corrosion risk of PAH-contaminated soil remediated by persulfate oxidation - Zhenxia Wang; Jiuhao Song; Wenyi Yuan; Yi Li; Naijin Wu; Xiang Li; Liming Rong; Haijian Wang; Ji Zhang; Wenxia Wei; Peizhong Li (Journal of Environmental Management, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

Tailoring gas-releasing nanoplatforms for wound treatment: An emerging approach - Zixin Wang; Fan Rong; Zhao Li; Wei Li; Kuljeet Kaur; Yin Wang (Chemical Engineering Journal, 2023)

The key role of carboxylate ligands in Ru@Ni-MOFs/NF in promoting water dissociation kinetics for effective hydrogen evolution in alkaline media - Cheng-Fei Li; Ting-Yu Shuai; Li-Rong Zheng; Hai-Bo Tang; Jia-Wei Zhao; Gao-Ren Li (Chemical Engineering Journal, 2023)

The driving factors and buffering mechanism regulating cropland soil acidification across the Sichuan Basin of China - Aiwen Li; Chengji Li; Yuanyuan Zhang; Qian Deng; Hongyan Fang; Bin Zhao; Min Ran; Liangying Song; Jingling Xue; Qi Tao; Rong Huang; Yiding Li; et al. (CATENA, 2023)

The genomic, transcriptomic, and immunological profiles of perineural invasion in pancreatic ductal adenocarcinoma - Shu-Heng Jiang; Rong-Kun Li; De-Jun Liu; Jun-Li Xue; Min-Hao Yu; Shan Zhang; Li-Min Liu; Jun-Feng Zhang; Rong Hua; Yong-Wei Sun; Xu Wang; Qin Yang; et al. (Science China Life Sciences, 2023)

IL-18BP Alleviates Anxiety-Like Behavior Induced by Traumatic Stress via Inhibition of the IL-18R-NLRP3 Signaling Pathway in a Mouse Model of Hemorrhagic Shock and Resuscitation - Li-Min Zhang; Dong-Xue Zhang; Rong-Xin Song; Jin-Meng Lv; Lu-Ying Wang; Zhi-You Wu; Hui-Tao Miao; Yan-Bo Zhou; Wei Zhang; Yue Xin; Yan Li (Molecular Neurobiology, 2023)

Nitric Oxide Enhances Salt Tolerance in Tomato Seedlings by Regulating Endogenous S-nitrosylation Levels - Chunlei Wang; Lijuan Wei; Jing Zhang; Dongliang Hu; Rong Gao; Yayu Liu; Li Feng; Wenting Gong; Weibiao Liao (Journal of Plant Growth Regulation, 2023)

A new formula of recovery factor for non-equilibrium transport of graded suspended sediment in the Middle Yangtze River - Lin-lin Li; Jun-qiang Xia; Mei-rong Zhou; Shan-shan Deng; Zhi-wei Li (Journal of Mountain Science, 2023)

Copper Toxicity Differentially Regulates the Seedling Growth, Copper Distribution, and Photosynthetic Performance of Citrus sinensis and Citrus grandis - Xin-yu Li; Mei-lan Lin; Ping-ping Hu; Ning-wei Lai; Zeng-rong Huang; Li-song Chen (Journal of Plant Growth Regulation, 2022)

Study on the Relationship Between Diet, Physical Health and Gut Microflora of Chinese College Students - Xiafen Hu; Jiaqi Guo; Jiadun Wang; Wanxin Liu; Xiaochen Xiang; Siyang Chen; Xinquan Li; Jinhan Tang; Wei Zhang; Hui Chen; Rong Shu; Qingming Wu; et al. (Current Microbiology, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Mechanism of progressive failure of a slope with a steep joint under the action of freezing and thawing: model test - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Bo Lu; Xiao-ke Shen; Xiao-wei Wang; Jie-sheng Liu; Liang-liang Wu; Xin-zhou Zhang (Journal of Mountain Science, 2022)

MicroRNA-339-5p inhibits lipopolysaccharide-induced rat mesangial cells by regulating the Syk/Ras/c-Fos pathway - Jia Rong Gao; Miao Miao Shi; Hui Jiang; Xiao Li Zhu; Liang Bing Wei; Xiu Juan Qin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Synthesis and in vitro biological evaluation of novel dendrocandin analogue as potential anti-tumor agent - Jing-Yun Yan; Hao-Nan Yang; Ning Yang; Yin-Rong Xie; Xiu-Li Sun; Ye-Wei Huang; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Natural Product Research, 2022)

A strategy for establishing an efficient somatic embryo regeneration system in Castanea mollissima Blume - Xiao-wei Li; Zhi-lin Sun; Yue-rong Gao; Jing-yi Ge; Yu-zhen Tian; Bing Liu; Shi-kan Sun; Ke-feng Fang; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Runoff projections of the Qinling Mountains and their impact on water demand of Guanzhong region in Northwest China - Zhao-peng Zhang; Ke-qin Duan; Huan-cai Liu; Ya-li Meng; Rong Chen; Da-wei Li; Shuang-shuang Li (Journal of Mountain Science, 2022)

Ambient air pollutants increase the risk of immunoglobulin E–mediated allergic diseases: a systematic review and meta-analysis - Hua Wang; Xian-Bao Li; Xiu-Jie Chu; Nv-Wei Cao; Hong Wu; Rong-Gui Huang; Bao-Zhu Li; Dong-Qing Ye (Environmental Science and Pollution Research, 2022)

Comparative analysis of the structure and function of rhizosphere microbiome of the Chinese medicinal herb Alisma in different regions - Chenbin Wei; Wei Gu; Rong Tian; Fei Xu; Yun Han; Yuanyuan Ji; Tao Li; Yu Zhu; Peilei Lang; Wenqing Wu (Archives of Microbiology, 2022)

Molecular dietary analysis of Adélie (Pygoscelis adeliae) and Gentoo (Pygoscelis papua) penguins breeding sympatrically on Antarctic Ardley Island using fecal DNA - Yin-Xin Zeng; Hui-Rong Li; Wei Han; Wei Luo (Polar Biology, 2022)

Bmal1- and Per2-mediated regulation of the osteogenic differentiation and proliferation of mouse bone marrow mesenchymal stem cells by modulating the Wnt/β-catenin pathway - Jiawen Zheng; Lanxin Zhang; Zhen Tan; Qing Zhao; Xiaoyu Wei; Yuqing Yang; Rong Li (Molecular Biology Reports, 2022)

Wuzi Yanzong pill attenuates MPTP-induced Parkinson’s Disease via PI3K/Akt signaling pathway - Wei Hang; Hui-jie Fan; Yan-rong Li; Qi Xiao; Lu Jia; Li-juan Song; Yao Gao; Xiao-ming Jin; Bao-guo Xiao; Jie-zhong Yu; Cun-gen Ma; Zhi Chai (Metabolic Brain Disease, 2022)

How do precipitation events modify the stable isotope ratios in leaf water at Lhasa on the southern Tibetan Plateau? - Yong Wang; Wusheng Yu; Lun Luo; Minghui Li; Xiaoming Liu; Rong Guo; Yaoming Ma; Baiqing Xu; Guangjan Wu; Chengyi Zhao; Zhaowei Jing; Feili Wei; et al. (Isotopes in Environmental and Health Studies, 2022)

Ventromedial Thalamus-Projecting DCN Neurons Modulate Associative Sensorimotor Responses in Mice - Jie Zhang; Hao Chen; Li-Bin Zhang; Rong-Rong Li; Bin Wang; Qian-Hui Zhang; Liu-Xia Tong; Wei-Wei Zhang; Zhong-Xiang Yao; Bo Hu (Neuroscience Bulletin, 2022)

Urinary phthalate metabolites in pregnant women: occurrences, related factors, and association with maternal hormones - Wei Wu; Zhi-li Ma; Fang Yang; Ping Wu; De-xin Zhang; Rong Zeng; Dan-ling Sun; Liu Cao (Environmental Science and Pollution Research, 2022)

Influence of Notch Geometry on the Rock Fracture Toughness Measurement Using the ISRM Suggested Semi-Circular Bend (SCB) Method - Geli Zhao; Wei Yao; Xing Li; Ying Xu; Kaiwen Xia; Rong Chen (Rock Mechanics and Rock Engineering, 2022)

The solar wind plasma upstream of Mars observed by Tianwen-1: Comparison with Mars Express and MAVEN - Kai Fan; Limei Yan; Yong Wei; Aibing Zhang; Linggao Kong; Markus Fränz; Fei He; Lihui Chai; Chongjing Yuan; Yuqi Wang; Jun Zhong; Zhaojin Rong; et al. (Science China Earth Sciences, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Effect of Fertilization Regimes and Seasonal Change on nosZ-Denitrifying Bacterial Community in a Double-Rice Paddy Field - Jiangwen Nie; Yong Zhou; Wei Yang; Shaoqiu Li; Haoxuan Li; Jianwei Wu; Chengwei Li; Xiaoyuan Yan; Rong Zhu; Bo Zhu; Zhangyong Liu (Journal of Soil Science and Plant Nutrition, 2022)

Unloading Response Characteristics of Cross Fault Caverns: Effect of Fault Angles - Yong-Hui Shang; Lin-Rong Xu; Yong-Wei Li (Geotechnical and Geological Engineering, 2022)

Neoflavonoids from the heartwood of Dalbergia melanoxylon - Meng-fei Wang; Guang-qiang Ma; Feng Shao; Rong-hua Liu; Lan-ying Chen; Yang Liu; Li Yang; Xiao-wei Meng (Natural Product Research, 2022)

Digoxin Ameliorates Glymphatic Transport and Cognitive Impairment in a Mouse Model of Chronic Cerebral Hypoperfusion - Jie Cao; Di Yao; Rong Li; Xuequn Guo; Jiahuan Hao; Minjie Xie; Jia Li; Dengji Pan; Xiang Luo; Zhiyuan Yu; Minghuan Wang; Wei Wang (Neuroscience Bulletin, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Antioxidant CPA-type indole alkaloids produced from the deep-sea derived fungus Aspergillus sp. SCSIO 41024 - Wei-Hao Chen; Kun-Long Li; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Xue-Feng Zhou; Jun-Jian Wang; Yong-Hong Liu; Jun-Feng Wang (Natural Product Research, 2021)

The xyloglucan galactosylation modulates the cell wall stability of pollen tube - Qiqi Wei; Ying Yang; Hui Li; Zhiwen Liu; Rong Fu; Hanqian Feng; Chao Li (Planta, 2021)

Circulating microRNA-30a-5p, microRNA-101-3p, microRNA-140-3p and microRNA-141-3p as potential biomarkers for dexmedetomidine response in pediatric patients - Xinmei Cai; Bilian Li; Wei Wei; Yanping Guan; Xue Bai; Min Huang; Yaying Huang; Lili Rong; Xingrong Song; Guoping Zhong (European Journal of Clinical Pharmacology, 2021)

miR-125-5p inhibits thyroid cancer growth and metastasis by suppressing the ERK/PI3K/AKT signal pathway - Rong Wang; Chen Wang; Xian-Jie Meng; Li Wei (Molecular & Cellular Toxicology, 2021)

The chemical profile and biological activity of different extracts of Sapindus mukorossi Gaertn. against Cutibacterium acnes - Min-Ping Wei; Jin-Dan Qiu; Lu Li; Yun-Fei Xie; Ya-Hui Guo; Hang Yu; Yu-Liang Cheng; He Qian; Wei-Rong Yao (Natural Product Research, 2021)

The effectiveness of extended binding affinity of prophage lysin PlyARI against Streptococcus suis infection - Yuyi Xiao; Rong Chen; Min Li; Zitai Qi; Yanfei Yu; Zihao Pan; Huochun Yao; Zhixin Feng; Wei Zhang (Archives of Microbiology, 2021)

Hippocampal Interneurons are Required for Trace Eyeblink Conditioning in Mice - Wei-Wei Zhang; Rong-Rong Li; Jie Zhang; Jie Yan; Qian-Hui Zhang; Zhi-An Hu; Bo Hu; Zhong-Xiang Yao; Hao Chen (Neuroscience Bulletin, 2021)
While the hippocampus has been implicated in supporting the association among time-separated events, the underlying cellular mechanisms have not been fully clarified. Here, we combined in vivo multi-channel recording and optogenetics to investigate the activity of hippocampal interneurons in freely-moving mice performing a trace eyeblink conditioning (tEBC) task. We found that the hippocampal interneurons exhibited conditioned stimulus (CS)-evoked sustained activity, which predicted the performance of conditioned eyeblink responses (CRs) in the early acquisition of the tEBC. Consistent with this, greater proportions of hippocampal pyramidal cells showed CS-evoked decreased activity in the early acquisition of the tEBC. Moreover, optogenetic suppression of the sustained activity in hippocampal interneurons severely impaired acquisition of the tEBC. In contrast, suppression of the sustained activity of hippocampal interneurons had no effect on the performance of well-learned CRs. Our findings highlight the role of hippocampal interneurons in the tEBC, and point to a potential cellular mechanism subserving associative learning.

Evaluation of field resistance to brown stripe disease in novel and major cultivated sugarcane varieties in China - Xiao-Yan Wang; Xiao-Yan Cang; Wei Qin; Hong-Li Shan; Rong-Yue Zhang; Chang-Mi Wang; Wen-Feng Li; Ying-Kun Huang (Journal of Plant Pathology, 2021)

Effects of Mn2+ on neutral lipid content, C4 pathway, and related gene expression in Phaeodactylum tricornutum - Rong-Shi Chen; Li Zhang; Feng-Juan Wei; Lan-Ying Yuan; Pu Zhao; He-Yu Wang; Yi-Fu Gong (Journal of Applied Phycology, 2021)

Removal of phosphorus and ammonium from municipal wastewater treatment plant effluent by manganese ore in a simulated constructed wetland - Yungui Li; Xueying Bai; Ruonan Ding; Wenxuan Lv; Ying Long; Liang Wei; Fachun Xiang; Rong Wang (Environmental Science and Pollution Research, 2021)

Exposure to antibiotics and mental disorders in children: a community-based cross-sectional study - Jingjing Zhang; Kaiyong Liu; Liang Sun; Linsheng Yang; Xinji Liu; Yitian Zhu; Rong Wei; Zhongxiu Jin; Li Wang; Ying Ma; Sufang Wang; Annuo Liu; et al. (Environmental Geochemistry and Health, 2021)

Dissipation, residue, dietary, and ecological risk assessment of atrazine in apples, grapes, tea, and their soil - Longfei Yuan; Yida Chai; Congdi Li; Rong Liu; Zenglong Chen; Li Li; Wei Li; Yujian He (Environmental Science and Pollution Research, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Bioactive polyketides from the pathogenic fungus of Epicoccum sorghinum - Ching-Chia Chang; Chi-Ying Li; Yi-Hong Tsai; Mohamed El-Shazly; Chien-Kei Wei; Zih-Jie Yang; Shu-Li Chen; Chin-Chung Wu; Yang-Chang Wu; Fang-Rong Chang (Planta, 2021)

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

Markers of oxidative stress and toxicant exposure among young waterpipe smokers in the USA - Rime Jebai; Mohammad Ebrahimi Kalan; Mayra Vargas-Rivera; Olatokunbo Osibogun; Wei Li; Prem Gautam; Mu-Rong Chao; Chiung-Wen Hu; Zoran Bursac; Wasim Maziak (Environmental Science and Pollution Research, 2021)

Small-sized extracellular vesicles (EVs) derived from acute myeloid leukemia bone marrow mesenchymal stem cells transfer miR-26a-5p to promote acute myeloid leukemia cell proliferation, migration, and invasion - Dexiang Ji; Yue He; Wei Lu; Yanyan Rong; Fei Li; Xianbao Huang; Ruibin Huang; Yanxia Jiang; Guoan Chen (Human Cell, 2021)

Haloechinothrix aidingensis sp. nov., an actinomycete isolated from salt lake in Xinjiang province, north-west China - Li Yang; Ya-Rong Kou; Tong-Wei Guan; Min Yin; Bing-Bing Liu; Yong-Jiang Shi; Wen-Yong Zhu; Shu-Kun Tang (Archives of Microbiology, 2021)

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Effect of fermentation bed on bacterial growth in the fermentation mattress material and cecum of ducks - Jian- mei Wang; Xin- meng Gan; Fa-jun Pu; Wan- xia Wang; Min Ma; Ling-li Sun; Ji-wei Hu; Bo Hu; Rong-ping Zhang; Li-li Bai; Liang Li; He-he Liu (Archives of Microbiology, 2021)

Effect of bFGF on fibroblasts derived from the golden snub-nosed monkey - Xin Liu; Hao Wei; Jing Yang; Jingjing Li; Pei Zhang; Yuli Li; Rong Hou; Jinlian Hua; Xingrong Yan; Baoguo Li (Primates, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

Curcumin protects thymus against D-galactose-induced senescence in mice - Jie-han Li; Ting-ting Wei; Li Guo; Jia-hui Cao; Yuan-kang Feng; Shu-ning Guo; Guo-hong Liu; Yi Ding; Yu-rong Chai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Relationship Between Body Composition and Balance Performance in Older Adults with Hyperkyphosis - Phunsuk Kantha; Shiow-Chwen Tsai; Chien-Wen Hou; Rong-Sen Yang; Pei-Yu Su; Wei-Li Hsu (Journal of Medical and Biological Engineering, 2021)

High diversity of planktonic prokaryotes in Arctic Kongsfjorden seawaters in summer 2015 - Yin–Xin Zeng; Wei Luo; Hui–Rong Li; Yong Yu (Polar Biology, 2021)

Long-term impact of accidental pollution on the distribution and risks of metals and metalloids in the sediment of the Longjiang River, China - Qian-Li Ma; Ling-Ai Yao; Qing-Wei Guo; Guang-Jie Zhou; Rong-Chang Liang; Qiao-Li Fang; Zhen-Cheng Xu; Xue-Min Zhao (Environmental Science and Pollution Research, 2021)

Paenibacillus turpanensis sp. nov., isolated from a salt lake of Turpan city in Xinjiang province, north-west China - Li Yang; Hua-Wei Huang; Yun Wang; Ya-Rong Kou; Min Yin; Yu Li; Xue-Qian Wang; Gui-Fang Zhao; Wen-Yong Zhu; Shu-Kun Tang (Archives of Microbiology, 2021)

High-frequency compensation for seismic data based on adaptive generalized S transform - Hui-Feng Li; Jin Wang; Zheng-Rong Wei; Fei-Long Yang (Applied Geophysics, 2020)

Inverse gaussian beam stack imaging in 3D crosswell seismic exploration of deviated wells and Its application - Fei-Long Yang; Chong Zhao; Zheng-Rong Wei; Hui Sun; Hui-Feng Li; Chi Zhao; Hao Luo (Applied Geophysics, 2020)

PSD-93 Interacts with SynGAP and Promotes SynGAP Ubiquitination and Ischemic Brain Injury in Mice - Qingxiu Zhang; Hui Yang; Hong Gao; Xiaomei Liu; Qingjie Li; Rong Rong; Zhenqian Liu; Xiu-e Wei; Liping Kong; Yun Xu; Liangqun Rong (Translational Stroke Research, 2020)

Isolation and Identification of Endophytic Fungi in Kernels of Coix lachrymal-jobi L. Cultivars - Guan-rong Li; Bao-hong Cao; Wei Liu; Rui-hua Ren; Jie Feng; Da-jin Lv (Current Microbiology, 2020)

Comparative transcriptome analysis reveals a gene expression profile that contributes to rhizome swelling in Panax japonicus var. major - Jun Rong Tang; Ying Chun Lu; Zheng Jie Gao; Wan Ling Song; Kun Hua Wei; Yan Zhao; Qing Yan Tang; Xue Jiao Li; Jun Wen Chen; Guang Hui Zhang; Guang Qiang Long; Wei Fan; et al. (Plant Biosystems, 2020)

Crosstalk between PKC and MAPK pathway activation in cardiac fibroblasts in a rat model of atrial fibrillation - Wei-hua Guo; Xian Wang; Mei-sheng Shang; Zhe Chen; Qi Guo; Li Li; Hai-ying Wang; Rong-hui Yu; Chang-sheng Ma (Biotechnology Letters, 2020)

Characterization of Pingliang xiaoheidou (ZDD 11047), a soybean variety with resistance to soybean cyst nematode Heterodera glycines - Wei Guo; Jing S. Chen; Feng Zhang; Ze Y. Li; Hai F. Chen; Chan J. Zhang; Li M. Chen; Song L. Yuan; Rong Li; Dong Cao; Qing N. Hao; Shui L. Chen; et al. (Plant Molecular Biology, 2020)

Sugar transporter genes in grass carp (Ctenopharyngodon idellus): molecular cloning, characterization, and expression in response to different stocking densities - Xiao Liang; Fengying Yan; Yu Gao; Mei Xiong; Haishan Wang; Kommaly Onxayvieng; Rong Tang; Li Li; Xi Zhang; Wei Chi; Marina Piria; Mirna Mrkonjić Fuka; et al. (Fish Physiology and Biochemistry, 2020)

Disruption of functional connectivity among subcortical arousal system and cortical networks in temporal lobe epilepsy - Rong Li; Chongyu Hu; Liangcheng Wang; Ding Liu; Dingyang Liu; Wei Liao; Bo Xiao; Huafu Chen; Li Feng (Brain Imaging and Behavior, 2020)

Iridoid, phenylethanoid and flavonoid glycosides from Forsythia suspensa - Qian Wei; Rong Zhang; Qin Wang; Xin Jia Yan; Quan Wei Yu; Fu Xia Yan; Chang Li; Yue Hu Pei (Natural Product Research, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

First report of cucumber mosaic virus infecting bahizi (Angelica dahurica) in China - Ruo-Fan Wei; Wan-Long Ding; Yong Li; Rong Wang (Journal of Plant Pathology, 2020)

Immunogenicity noninferiority study of 2 doses and 3 doses of an Escherichia coli-produced HPV bivalent vaccine in girls vs. 3 doses in young women - Yue-Mei Hu; Meng Guo; Chang-Gui Li; Kai Chu; Wen-Gang He; Jing Zhang; Jian-Xiang Gu; Juan Li; Hui Zhao; Xiang-Hong Wu; BiZhen Lin; Zhi-Jie Lin; et al. (Science China Life Sciences, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Functional Analysis of Sheep POU2F3 Isoforms - Guang-Wei Ma; Yan-Kai Chu; Hua Yang; Xiao-Hong Yan; En-Guang Rong; Hui Li; Ning Wang (Biochemical Genetics, 2020)
POU domain class 2 transcription factor 3 (POU2F3) plays an important role in keratinocyte proliferation and differentiation. Our previous study identified four sheep POU2F3 transcript variants ( POU2F3-1 , POU2F3-2 , POU2F3-3 , and POU2F3-4 ), encoding three POU2F3 protein isoforms (POU2F3-1, POU2F3-2, and POU2F3-3). However, the functional differences among the three POU2F3 isoforms remain unknown. The objective of this study was to determine the tissue expression pattern of the four POU2F3 transcript variants in sheep and to investigate the functional differences in cell proliferation among the three POU2F3 isoforms. Quantitative RT-PCR analysis showed that the four POU2F3 transcripts were ubiquitously expressed in all tested adult sheep tissues, and POU2F3-1 exhibited higher expression level than the other three POU2F3 transcript variants in skin ( P P P P > 0.05). Dual luciferase reporter assays demonstrated that overexpression of any one of the three POU2F3 isoforms significantly inhibited the promoter activities of keratin 14 ( KRT14 ) and matrix metalloproteinase 19 ( MMP19 ) genes ( P KRT14 and MMP19 genes than POU2F3-1 and POU2F3-2 ( P P > 0.05). These results suggest three sheep POU2F3 isoforms have similar functional effects, but to a different extent.

Evidence of compliance with and effectiveness of guidelines for noninvasive prenatal testing in China: a retrospective study of 189,809 cases - Chan Tian; Tao Deng; Xiuhuang Zhu; Chen Gong; Yangyu Zhao; Yuan Wei; Rong Li; Xiufeng Xu; Miaonan He; Zhiwei Zhang; Jing Cheng; Mol BenWillem; et al. (Science China Life Sciences, 2020)

Reference Point Based Multi-Objective Optimization of Reservoir Operation: a Comparison of Three Algorithms - Rong Tang; Ke Li; Wei Ding; Yuntao Wang; Huicheng Zhou; Guangtao Fu (Water Resources Management, 2020)

Roles of PTBP1 in alternative splicing, glycolysis, and oncogensis - Wei Zhu; Bo-lun Zhou; Li-juan Rong; Li Ye; Hong-juan Xu; Yao Zhou; Xue-jun Yan; Wei-dong Liu; Bin Zhu; Lei Wang; Xing-jun Jiang; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2020)

Agrobacterium-mediated genetic transformation of Chinese chestnut (Castanea mollissima Blume) - Zhi-lin Sun; Xiao Li; Wan Zhou; Jun-di Yan; Yue-rong Gao; Xiao-wei Li; Jia-chen Sun; Ke-feng Fang; Qing Zhang; Yu Xing; Ling Qin; Qing-qin Cao (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)
Chinese chestnut ( Castanea mollissima ) is an important germplasm resource for the breeding of Castanea species worldwide with vital ecological and economic value. Biotechnology overcomes the limitations of traditional breeding and accelerates germplasm improvement. However, a genetic transformation system for Chinese chestnut has not yet been established. In this study, a stable and efficient Agrobacterium -mediated genetic transformation method for Chinese chestnut is described. Embryogenic calli of C. mollissima cv. ‘Yanshanhongli’ were used as the target material. The sensitivity of embryogenic calli to kanamycin was determined, whereby the proliferation of non-transformed calli was completely inhibited at 180 mg/L. Antibiotic inhibition results for Chinese chestnut embryogenic calli showed that 50 mg/L cefotaxime and 500 μM timentin completely inhibited the growth of Agrobacterium tumefaciens but did not affect the normal growth of Chinese chestnut embryogenic calli. When embryogenic calli were co-cultured for 2 days with Agrobacterium tumefaciens strain AGL1 harboring the PBI121-EGFP plasmid, an embryogenic callus transformation efficiency of 4.55% was obtained, and two transgenic chimera were acquired. This Agrobacterium -mediated transformation system for Chinese chestnut provides a fundamental platform for genetic improvement of core germplasm and for further verification of gene function.

One bis-indole alkaloid-voacamine from Voacanga africana Stapf: biological activity evaluation of PTP1B in vitro utilizing enzymology method based on SPRi expriment - Yan-Qiu Wang; Hong-Xiang Li; Xiao-Chun Liu; Jin-Shuang Zhao; Rong-Qiang Liu; Wen-ying Huai; Wei-Jun Ding; Tian-E Zhang; Yun Deng (Natural Product Research, 2019)

Molecular cloning and characterization of genes related to the ethylene signal transduction pathway in pomegranate (Punica granatum L.) under different temperature treatments - Rong Huang; Wei Li; Xiao-Wan Guan; Biao Xie; Shui-Ming Zhang (Journal of Biosciences, 2019)

Paramyxoviruses respiratory syncytial virus, parainfluenza virus, and human metapneumovirus infection in pediatric hospitalized patients and climate correlation in a subtropical region of southern China: a 7-year survey - Wen-Kuan Liu; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Li Zhang; Shu-Jun Gu; Rong Zhou; Qian Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Pedobacter changchengzhani sp. nov., isolated from soil of Antarctica - Rui-Han He; Zhen-Wei Liu; Yong Yu; Hui-Rong Li; Zong-Jun Du (Antonie van Leeuwenhoek, 2019)

A new protostane-type triterpenoid from Alisma plantago-aquatica subsp. orientale (Sam.) Sam - Hong-Mei Li; Dan Liu; Wei-Feng Dai; Xuan-Qin Chen; Rong-Tao Li (Natural Product Research, 2019)

Root diversity in sesame (Sesamum indicum L.): insights into the morphological, anatomical and gene expression profiles - Ruqi Su; Rong Zhou; Marie Ali Mmadi; Donghua Li; Lu Qin; Aili Liu; Jianqiang Wang; Yuan Gao; Mengyuan Wei; Lisong Shi; Ziming Wu; Jun You; et al. (Planta, 2019)

Effects of demethylating reagent 5-aza-2′-deoxycytidine on the growth and cephalotaxine production in Cephalotaxus mannii suspension cells - Li-Rong Wei; Wang-Yan Qin; Yong-Cheng Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Development of a loop-mediated isothermal amplification for rapid diagnosis of Aphelenchoides ritzemabosi - Dong-Wei Wang; Chun-Ling Xu; Zong-Shi Bai; Jun-Yi Li; Yu-Chun Han; Li-Rong Zhao; Hui Xie (European Journal of Plant Pathology, 2019)

Molecular cloning and functional characterization of a seed-specific VvβVPE gene promoter from Vitis vinifera - Peijie Gong; Rong Wei; Yan Li; Ruipu Wang; Yujin Tang; Ling Wang; Huijun Zhu; Yuejin Wang; Chaohong Zhang (Planta, 2019)

Abnormal dynamics of functional connectivity density in children with benign epilepsy with centrotemporal spikes - Rong Li; Liangcheng Wang; Heng Chen; Xiaonan Guo; Wei Liao; Ye-Lei Tang; Huafu Chen (Brain Imaging and Behavior, 2019)

Potassium Stimulation of IAA Transport Mediated by the Arabidopsis Importer AUX1 Investigated in a Heterologous Yeast System - Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Shih-Ming Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2019)

Hydrogen peroxide and nitric oxide are involved in programmed cell death induced by cryopreservation in Dendrobium protocorm-like bodies - Xue-ru Jiang; Rui-fen Ren; Wei Di; Meng-xue Jia; Ze-di Li; Yan Liu; Rong-fu Gao (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

The relationship between surface spectral albedo and soil moisture in an arid Gobi area - Zhenchao Li; Jiaxi Yang; Xiaoqing Gao; Ye Yu; Zhiyuan Zheng; Rong Liu; Chao Wang; Xuhong Hou; Zhigang Wei (Theoretical and Applied Climatology, 2019)

Chronic stress impairs the aquaporin-4-mediated glymphatic transport through glucocorticoid signaling - Fang Wei; Jian Song; Cui Zhang; Jun Lin; Rong Xue; Li-Dong Shan; Shan Gong; Guo-Xing Zhang; Zheng-Hong Qin; Guang-Yin Xu; Lin-Hui Wang (Psychopharmacology, 2019)

In Vitro Susceptibility of Berberine Combined with Antifungal Agents Against the Yeast Form of Talaromyces marneffei - Hong Luo; Kai-su Pan; Xiao-lu Luo; Dong-yan Zheng; Alex Andrianopoulos; Le-min Wen; Yan-qing Zheng; Jing Guo; Chun-yang Huang; Xiu-ying Li; Rong Hu; Yu-jiao Li; et al. (Mycopathologia, 2019)

A CkDREB1 gene isolated from Caragana korshinskii Kom. enhances Arabidopsis drought and cold tolerance - Ziyi Zhang; Qi Yang; Chunlin Zhang; Lili Wei; Rong Yue; Guojing Li; Xiaofei Lin; Ruigang Wang (Brazilian Journal of Botany, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

Angiogenesis in pancreatic cancer: current research status and clinical implications - Shuo Li; Hua-Xiang Xu; Chun-Tao Wu; Wen-Quan Wang; Wei Jin; He-Li Gao; Hao Li; Shi-Rong Zhang; Jin-Zhi Xu; Zi-Hao Qi; Quan-Xing Ni; Xian-Jun Yu; et al. (Angiogenesis, 2019)

Establishment and application of distant hybridization technology in fish - Shi Wang; Chenchen Tang; Min Tao; Qinbo Qin; Chun Zhang; Kaikun Luo; Rurong Zhao; Jing Wang; Li Ren; Jun Xiao; Fangzhou Hu; Rong Zhou; et al. (Science China Life Sciences, 2019)

Silurian integrative stratigraphy and timescale of China - Jiayu Rong; Yi Wang; Renbin Zhan; Junxuan Fan; Bing Huang; Peng Tang; Yue Li; Xiaole Zhang; Rongchang Wu; Guangxu Wang; Xin Wei (Science China Earth Sciences, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

A Longitudinal Functional Magnetic Resonance Imaging Study of Working Memory in Patients Following a Transient Ischemic Attack: A Preliminary Study - Wei Su; Jian Guo; Yun Zhang; Jie Zhou; Ning Chen; Muke Zhou; Rong Li; Huafu Chen; Li He (Neuroscience Bulletin, 2018)

Arctic Climate Changes Based on Historical Simulations (1900‒2013) with the CAMS-CSM - Ting Wei; Jian Li; Xinyao Rong; Wenjie Dong; Bingyi Wu; Minghu Ding (Journal of Meteorological Research, 2018)

Onosmanones A and B, two novel quinonoid xanthenes from Onosma paniculatum - Li-Qiu Quan; Wei-Feng Dai; Fei Li; Yan-Hong Li; Xuan-Qin Chen; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2018)

Immune Cells After Ischemic Stroke Onset: Roles, Migration, and Target Intervention - Lu-yao Ao; Yun-Yi Yan; Lin Zhou; Cheng-yuan Li; Wan-Ting Li; Wei-rong Fang; Yun-man Li (Journal of Molecular Neuroscience, 2018)

Mid–Late Cretaceous igneous activity in South China: the Qianjia example, Hainan Island - Sai-Jun Sun; Li-Peng Zhang; Rong-Qing Zhang; Xing Ding; Hong-Li Zhu; Zhao-Feng Zhang; Wei-Dong Sun (International Geology Review, 2018)

Genetic variability of wildlife-derived Sarcoptes scabiei determined by the ribosomal ITS-2 and mitochondrial 16S genes - Chun-Yan Li; Yin Sun; Yue Xie; Xuan Zhou; Xiao-Bin Gu; Wei-Ming Lai; Xue-Rong Peng; Guangyou Yang (Experimental and Applied Acarology, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Pleiotropic effects of the wheat domestication gene Q on yield and grain morphology - Quan Xie; Na Li; Yang Yang; Yulong Lv; Hongni Yao; Rong Wei; Debbie L. Sparkes; Zhengqiang Ma (Planta, 2018)

Regulation of H+-pyrophosphatase by 14-3-3 Proteins from Arabidopsis thaliana - Yu-Di Hsu; Yu-Fen Huang; Yih-Jiuan Pan; Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2018)

Design, synthesis and biological evaluation of novel furoxan-based coumarin derivatives as antitumor agents - Zhuo Zhang; Zhi-Wei Bai; Yong Ling; Li-Qin He; Peng Huang; Hong-Xia Gu; Rong-Feng Hu (Medicinal Chemistry Research, 2018)

Schinzel–Giedion syndrome: a novel case, review and revised diagnostic criteria - Wei-Liang Liu; Zhi-Xu He; Fang Li; Rong Ai; Hong-Wei Ma (Journal of Genetics, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Phytoactinopolyspora halotolerans sp. nov., a halotolerant actinobacterium isolated from a saline soil in Xinjiang, northwest of China - Yang Ji; Wei-Xun Chunyu; En-Yuan Li; Zhang-Gui Ding; Min Yin; Yu-Rong Zhao; Yun Wang; Shu-Kun Tang (Antonie van Leeuwenhoek, 2018)

Saikosaponin D relieves unpredictable chronic mild stress induced depressive-like behavior in rats: involvement of HPA axis and hippocampal neurogenesis - Hong-Yan Li; Ying-Hua Zhao; Min-Jie Zeng; Fang Fang; Min Li; Ting-Ting Qin; Lu-Yu Ye; Hong-Wei Li; Rong Qu; Shi-Ping Ma (Psychopharmacology, 2017)

Improved application of tribenuron-methyl as a chemical hybridizing agent with forchlorfenuron for rapeseed hybrid breeding - Yong-Hong Li; Dian-Rong Li; Wu-Sheng Liang; Jian-Hua Tian; Jian-Chang Li; Hao Wang; Mao-Teng Li; Xu-Peng Guo; Wen-Jie Chen; Zhen-Lan Zhang; Fei Mao; Wei-Guo Zhao (Euphytica, 2017)

Bioorganic fertilizer maintains a more stable soil microbiome than chemical fertilizer for monocropping - Feng Cai; Guan Pang; Rui-Xia Li; Rong Li; Xiao-Long Gu; Qi-Rong Shen; Wei Chen (Biology and Fertility of Soils, 2017)

Chronological constraints on the tectonic evolution of the Chinese Tianshan Orogen through detrital zircons from modern and palaeo-river sands - Rong Ren; Shu-Wei Guan; Bao-Fu Han; Li Su (International Geology Review, 2017)

Characterization of extracellular polymeric substance (EPS) fractions produced by Microcystis aeruginosa under the stress of linoleic acid sustained-release microspheres - Lixiao Ni; Danye Li; Shiyi Rong; Lili Su; Wei Zhou; Peifang Wang; Chao Wang; Shiyin Li; Kumud Acharya (Environmental Science and Pollution Research, 2017)

Dissipation behavior and risk assessment of butralin in soybean and soil under field conditions - Congdi Li; Rong Liu; Li Li; Wei Li; Yujian He; Longfei Yuan (Environmental Monitoring and Assessment, 2017)

Nocardia tengchongensis sp. nov., isolated from a soil sample - Shuai Li; Hong Ming; Yan-Yan Duan; Jian-Rong Huang; Zhuo-Li Zhao; Ling-Yu Zhang; Wei-Li Ji; Xiao-Lin Meng; Wen-Jun Li; Guo-Xing Nie (Antonie van Leeuwenhoek, 2017)

Phenotypic Variation and Genetic Diversity in the Collections of Erianthus Arundinaceus (Retz.) Jesw. - Xi-Hui Liu; Huan-Zhong Song; Ge-Min Zhang; Wei-Xing Duan; Rong-Hua Zhang; Yang-Rui Li (Sugar Tech, 2017)

Trichoderma-enriched organic fertilizer can mitigate microbiome degeneration of monocropped soil to maintain better plant growth - Guan Pang; Feng Cai; Ruixia Li; Zheng Zhao; Rong Li; Xiaolong Gu; Qirong Shen; Wei Chen (Plant and Soil, 2017)

Development of a Time-Resolved Fluorescence Immunoassay for the Diagnosis of Hepatocellular Carcinoma Based on the Detection of Glypican-3 - Juan-Juan Chen; Chun-Mei Xie; Cong-Rong Wang; Yong Wan; Zhi-Ning Dong; Ming Li; Wei-Wen Xu (Journal of Fluorescence, 2017)

Erratum to: Acidic domains differentially read histone H3 lysine 4 methylation status and are widely present in chromatin-associated proteins - Meng Wu; Wei Wei; Jiwei Chen; Rong Cong; Tieliu Shi; Philippe Bouvet; Jiwen Li; Jiemin Wong; James X. Du (Science China Life Sciences, 2017)

Copper-modified palygorskite is effective in preventing and treating diarrhea caused by Salmonella typhimurium - Da-wei Yao; Ze-zhong Yu; Na Li; Yu-nong Hou; Jia-rong Xu; De-ji Yang (Journal of Zhejiang University-SCIENCE B, 2017)

NaCl stress induces CsSAMs gene expression in Cucumis sativus by mediating the binding of CsGT-3b to the GT-1 element within the CsSAMs promoter - Li-Wei Wang; Mei-Wen He; Shi-Rong Guo; Min Zhong; Sheng Shu; Jin Sun (Planta, 2017)

MEF2D Mediates the Neuroprotective Effect of Methylene Blue Against Glutamate-Induced Oxidative Damage in HT22 Hippocampal Cells - Zi-wei Chen; Anmin Liu; Qingyu Liu; Jingkao Chen; Wen-ming Li; Xiao-juan Chao; Qian Yang; Pei-qing Liu; Zi-xu Mao; Rong-biao Pi (Molecular Neurobiology, 2017)

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Cloning and expression analysis of zygote arrest 1 (Zar1) in New Zealand white rabbits - DAN WANG; SHU-YU XIE; WEI ZHANG; CAI-XIA SUN; TAO HUANG; AN-SI WANG; XUE-LEI HAN; GUI-RONG SUN; MING LI (Journal of Genetics, 2017)

Use of stable isotopes to understand food webs in Macao wetlands - Qian Chen; Yang Liu; Wei-Tim Ho; Shek Kiu Chan; Qiu-hua Li; Jian-Rong Huang (Wetlands Ecology and Management, 2017)

Acidic domains differentially read histone H3 lysine 4 methylation status and are widely present in chromatin-associated proteins - Meng Wu; Wei Wei; Jiwei Chen; Rong Cong; Tieliu Shi; Jiwen Li; Jiemin Wong; James X. Du (Science China Life Sciences, 2017)

The dynamics of landscape-scale ecological connectivity based on least-cost model in Dongshan Island, China - Li-yun Wu; Dong-jin He; Wei-bin You; Zhi-rong Ji; Yong Tan; Li-li Zhao (Journal of Mountain Science, 2017)

Using PG-Liposome-Based System to Enhance Puerarin Liver-Targeted Therapy for Alcohol-Induced Liver Disease - Ying-Zheng Zhao; Lu Zhang; Pardeep K. Gupta; Fu-Rong Tian; Kai-Li Mao; Kai-Yan Qiu; Wei Yang; Chuan-Zhu Lv; Cui-Tao Lu (AAPS PharmSciTech, 2016)

The unique origin of orange carrot cultivars in China - Zhen-Guo Ma; Xiao-Ping Kong; Li-Jie Liu; Cheng-Gang Ou; Ting-Ting Sun; Zhi-Wei Zhao; Zeng-Jian Miao; Jun Rong; Fei-Yun Zhuang (Euphytica, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

Dynamic Fracture Properties of Rocks Subjected to Static Pre-load Using Notched Semi-circular Bend Method - Rong Chen; Kang Li; Kaiwen Xia; Yuliang Lin; Wei Yao; Fangyun Lu (Rock Mechanics and Rock Engineering, 2016)

Characterization of the life cycle of the tick Haemaphysalis tibetensis under field conditions in Qinghai-Tibet plateau - Ming Liu; Tuo Li; Zhi-Jun Yu; Xiao-He Gao; Chun-Wei Zuo; Rong-Rong Wang; Ning-Xin Li; Hui Wang; Jing-Ze Liu (Experimental and Applied Acarology, 2016)

Hydrochemical characteristics and quality assessment of deep groundwater from the coal-bearing aquifer of the Linhuan coal-mining district, Northern Anhui Province, China - Man-li Lin; Wei-hua Peng; He-rong Gui (Environmental Monitoring and Assessment, 2016)

Serological survey of avian influenza virus infection in non-avian wildlife in Xinjiang, China - Yu-Rong Wei; Xue-Yun Yang; Yuan-Guo Li; Jie Wei; Wen-Ge Ma; Zhi-Guang Ren; Hui-Ling Guo; Tie-Cheng Wang; Xiao-Yun Mi; Gulizhati Adili; Shu-Kui Miao; Ayiqiaolifan Shaha; et al. (Archives of Virology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

The meso-mechanism study of gypsum rock weakening in brine solutions - Wei Dong Yu; Wei Guo Liang; Yan Rong Li; Yan Mei Yu (Bulletin of Engineering Geology and the Environment, 2016)

Lentibacillus amyloliquefaciens sp. nov., a halophilic bacterium isolated from saline sediment sample - Jing-Li Wang; Ke-Dong Ma; Yan-Wei Wang; Hui-Min Wang; Yan-Bin Li; Shan Zhou; Xiao-Rong Chen; De-Long Kong; Xiang Guo; Ming-Xiong He; Zhi-Yong Ruan (Antonie van Leeuwenhoek, 2016)

Identification of a regulatory element responsible for salt induction of rice OsRAV2 through ex situ and in situ promoter analysis - Yong-Bo Duan; Juan Li; Rui-Ying Qin; Rong-Fang Xu; Hao Li; Ya-Chun Yang; Hui Ma; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Molecular Biology, 2016)

Comparison of seven colchicine-induced tetraploid clones with their original diploid clones in purple coneflower (Echinacea purpurea L.) - Rong Chen; Wei-zhen Jiang; Qing-ling Li; Xin-lian Li; Xiao-lu Chen; Yue-sheng Yang; Hong Wu (Euphytica, 2016)

Floral Transcriptome Analyses of Four Paphiopedilum Orchids with Distinct Flowering Behaviors and Development of Simple Sequence Repeat Markers - Dong-Mei Li; Wei Wu; Di Zhang; Xiao-Rong Liu; Xiao-Fei Liu; Yi-Jian Lin (Plant Molecular Biology Reporter, 2015)

Induction of follicular luteinization by equine chorionic gonadotropin in cyclic guinea pigs - Jun-rong Li; Wei Wang; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2015)

EGCG induces G-CSF expression and neutrophilia in experimental sepsis - Wei Li; Andrew H. Wu; Shu Zhu; Jianhua Li; Rong Wu; John D’Angelo; Haichao Wang (Immunologic Research, 2015)

Comparison of SPE, IFE, and FLC in Monitoring Patients with Multiple Myeloma After Autologous Stem Cell Transplantation - Wei Li; Jia-Zi Zhou; Hui-Rong Chang; Li-Jun Dai; Zi-Ling Zhu; Yu-Feng Feng; Fei-Ran Gong; De-Pei Wu (Cell Biochemistry and Biophysics, 2015)

Psychrobacter fjordensis sp. nov., a psychrotolerant bacterium isolated from an Arctic fjord in Svalbard - Yin-Xin Zeng; Yong Yu; Hui-Rong Li; Wei Luo (Antonie van Leeuwenhoek, 2015)

The inward-rectifying K+ channel SsAKT1 is a candidate involved in K+ uptake in the halophyte Suaeda salsa under saline condition - Hui-Rong Duan; Qing Ma; Jin-Lin Zhang; Jing Hu; Ai-Ke Bao; Li Wei; Qian Wang; Sheng Luan; Suo-Min Wang (Plant and Soil, 2015)

Retraction Note to: Construction of pancreatic cancer double-factor regulatory network based on chip data on the transcriptional level - Li-Li Zhao; Tong Zhang; Bing-Rong Liu; Tie-Fu Liu; Na Tao; Li-Wei Zhuang (Molecular Biology Reports, 2015)

Retraction Note to: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2015)

Transcriptome analysis reveals the potential contribution of long noncoding RNAs to brown adipocyte differentiation - Liang hui You; Li jun Zhu; Lei Yang; Chun mei Shi; Ling xia Pang; Jun Zhang; Xian wei Cui; Chen bo Ji; Xi rong Guo (Molecular Genetics and Genomics, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Modified method for estimating organic carbon density in discontinuous Karst soil using ground-penetrating radar and geostatistics - Lei Li; Yin-hang Xia; Shu-juan Liu; Wei Zhang; Xiang-bi Chen; Hua Zheng; Hu-sen Qiu; Xun-yang He; Yi-rong Su (Journal of Mountain Science, 2015)

Long-term nickel exposure altered the bacterial community composition but not diversity in two contrasting agricultural soils - Jing Li; Hang-Wei Hu; Yi-Bing Ma; Jun-Tao Wang; Yu-Rong Liu; Ji-Zheng He (Environmental Science and Pollution Research, 2015)

Host shoot clipping depresses the growth of weedy hemiparasitic Pedicularis kansuensis - Xiao-Lin Sui; Wei Huang; Yun-Ju Li; Kai-Yun Guan; Ai-Rong Li (Journal of Plant Research, 2015)

Phosphorylation of p38 MAPK mediates aquaporin 9 expression in rat brains during permanent focal cerebral ischaemia - Xiaoyu Wei; Xuxia Ren; Rong Jiang; Hui Li; Fei Gao; Yuqin Chen; Jiaojiao Hou; Xueyuan Liu; Shanquan Sun; Mei Yang (Journal of Molecular Histology, 2015)

Study on the Mechanisms of Cartilage Tissue Damage Caused by Hydrogen Peroxide - Xiao Ouyang; Bo Wei; Shi Dong Hong; Jing Rong Wang; Feng Xin; Lin Wang; Xiao Wei Yang; Li Ming Wang (Cell Biochemistry and Biophysics, 2015)

Multilocus sequence typing analysis of Cronobacter spp. isolated from China - Jing-Hua Cui; Xiao-Li Du; Rong-Jie Wei; Hai-Jian Zhou; Wei Li; Stephen Forsythe; Zhi-Gang Cui (Archives of Microbiology, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

Dissipation and Degradation Dynamics of Thifluzamide in Rice Field - Li Na Wei; Ping Wu; Fu Rong Wang; Hong Yang (Water, Air, & Soil Pollution, 2015)

Immune protective effect of human alpha-1-antitrypsin gene during β cell transplantation in diabetic mice - Lu Yang; Yu-Ting Liao; Xiao-Fei Yang; Li-Wei Reng; Hui Qi; Fu-Rong Li (Immunologic Research, 2015)

GmPGIP3 enhanced resistance to both take-all and common root rot diseases in transgenic wheat - Aiyun Wang; Xuening Wei; Wei Rong; Liang Dang; Li-Pu Du; Lin Qi; Hui-Jun Xu; Yanjun Shao; Zengyan Zhang (Functional & Integrative Genomics, 2015)

Bacterial composition and spatiotemporal variation in sediments of Jiaozhou Bay, China - Xin Liu; Hang-Wei Hu; Yu-Rong Liu; Ke-Qing Xiao; Fan-Sheng Cheng; Ji Li; Tian Xiao (Journal of Soils and Sediments, 2015)

Protective effects of hydroxysafflor yellow A (HSYA) on alcohol-induced liver injury in rats - Yanhao He; Qiang Liu; Yanxiang Li; Xiaofeng Yang; Weirong Wang; Tingting Li; Wei Zhang; Yuexin Cui; Chaoyun Wang; Rong Lin (Journal of Physiology and Biochemistry, 2015)

The roles of IL-2 and IL-10 enhance anti-CD45RBmAb immune inhibition in allograft skin - Wei-Jian Guo; Hui Qi; Chun-Yan Deng; Han-Xin Zhou; Shao-Ping Deng; Fu-Rong Li (Immunologic Research, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Optimized Preparation of a 99mTc-Radiolabeled Probe for Tracing MicroRNA - Lei Kang; Xiao-jie Xu; Chao Ma; Rong-fu Wang; Ping Yan; Chun-li Zhang; Hong-wei Sun; Ding Li (Cell Biochemistry and Biophysics, 2015)

Erratum to: Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Kerui Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2015)

Effect of anthracene on the interaction between Platymonas helgolandica var. tsingtaoensis and Heterosigma akashiwo in laboratory cultures - Rong Bi; You Wang; Renjun Wang; Wei Li; Xuexi Tang (Journal of Ocean University of China, 2015)

Humanin attenuates Alzheimer-like cognitive deficits and pathological changes induced by amyloid β-peptide in rats - Gao-Shang Chai; Dong-Xiao Duan; Rong-Hong Ma; Jian-Ying Shen; Hong-Lian Li; Zhi-Wei Ma; Yu Luo; Lu Wang; Xin-Hua Qi; Qun Wang; Jian-Zhi Wang; Zelan Wei; et al. (Neuroscience Bulletin, 2014)

Analysis of DNA methylation of perennial ryegrass under drought using the methylation-sensitive amplification polymorphism (MSAP) technique - Xiao-Mei Tang; Xiang Tao; Yan Wang; Dong-Wei Ma; Dan Li; Hong Yang; Xin-Rong Ma (Molecular Genetics and Genomics, 2014)

Efficient Knockout of Transplanted Green Fluorescent Protein Gene in Medaka Using TALENs - Chao Qiu; Bin Cheng; Yunsheng Zhang; Rong Huang; Lanjie Liao; Yongming Li; Daji Luo; Wei Hu; Yaping Wang (Marine Biotechnology, 2014)

Reference gene selection for real-time RT-PCR normalization in rice field eel (Monopterus albus) during gonad development - Qing Hu; Wei Guo; Yu Gao; Rong Tang; Dapeng Li (Fish Physiology and Biochemistry, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Effect of two-linked mutations of the FMO3 gene on itopride metabolism in Chinese healthy volunteers - Li-Ping Zhou; Zhi-Rong Tan; Hao Chen; Dong Guo; Yao Chen; Wei-Hua Huang; Lian-Sheng Wang; Guo-Gang Zhang (European Journal of Clinical Pharmacology, 2014)

Isolation and functional characterization of a novel rice constitutive promoter - Juan Li; Rong-Fang Xu; Rui-Ying Qin; Hui Ma; Hao Li; Ying-Ping Zhang; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Cell Reports, 2014)

Studies on the analgesic activities of Jia-Yuan-Qing pill and its safety evaluation in mice - Ye Tian; Li-rong Teng; Jing-jing Song; Qing-fan Meng; Jia-hui Lu; Wei-wei Zhang; Kang Wei; Ning Wang; Di Wang; Le-sheng Teng (Protoplasma, 2014)

The expression and functional role of a FOXC1 related mRNA-lncRNA pair in oral squamous cell carcinoma - Xiang-pan Kong; Jie Yao; Wei Luo; Fu-kui Feng; Jun-tao Ma; Yi-peng Ren; De-li Wang; Rong-fa Bu (Molecular and Cellular Biochemistry, 2014)

miR-1246 releases RTKN2-dependent resistance to UVB-induced apoptosis in HaCaT cells - Wei Li; Ya-Fen Wu; Rong-Hua Xu; Hui Lu; Cui Hu; Hua Qian (Molecular and Cellular Biochemistry, 2014)

Shift in abundance and structure of soil ammonia-oxidizing bacteria and archaea communities associated with four typical forest vegetations in subtropical region - Yong-Chun Li; Bu-Rong Liu; Song-Hao Li; Hua Qin; Wei-Jun Fu; Qiu-Fang Xu (Journal of Soils and Sediments, 2014)

Impact of Indian summer monsoon on the South Asian High and its influence on summer rainfall over China - Wei Wei; Renhe Zhang; Min Wen; Xinyao Rong; Tim Li (Climate Dynamics, 2014)

The Accumulation of Glycine Betaine Is Dependent on Choline Monooxygenase (OsCMO), Not on Phosphoethanolamine N-Methyltransferase (OsPEAMT1), in Rice (Oryza sativa L. ssp. japonica) - Jinde Yu; Yuxiang Li; Wei Tang; Jia Liu; Bao-Rong Lu; Yongsheng Liu (Plant Molecular Biology Reporter, 2014)

Advances in preimplantation genetic diagnosis/screening - LiYing Yan; Yuan Wei; Jin Huang; XiaoHui Zhu; XiaoDan Shi; Xi Xia; Jie Yan; CuiLing Lu; Ying Lian; Rong Li; Ping Liu; Jie Qiao (Science China Life Sciences, 2014)

Cosuppression of RBCS3B in Arabidopsis leads to severe photoinhibition caused by ROS accumulation - Gao-Miao Zhan; Rong-Jun Li; Zhi-Yong Hu; Jing Liu; Lin-Bin Deng; Shi-You Lu; Wei Hua (Plant Cell Reports, 2014)

RETRACTED ARTICLE: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2014)

Effect of NeuroD Gene Silencing on the Migration and Invasion of Human Pancreatic Cancer Cells PANC-1 - Yang Wang; Dong Wei Su; Li Gao; Gui Ling Ding; Can Rong Ni; Ming Hua Zhu (Cell Biochemistry and Biophysics, 2014)

A three‐component signalling system fine‐tunes expression kinetics of HPPK responsible for folate synthesis by positive feedback loop during stress response of X anthomonas campestris - Fang‐Fang Wang; Chao‐Ying Deng; Zhen Cai; Ting Wang; Li Wang; Xiao‐Zheng Wang; Xiao‐Ying Chen; Rong‐Xiang Fang; Wei Qian (Environmental Microbiology, 2014)
Summary During adaptation to environments, bacteria employ two‐component signal transduction systems, which contain histidine kinases and response regulators, to sense and respond to exogenous and cellular stimuli in an accurate spatio‐temporal manner. Although the protein phosphorylation process between histidine kinase and response regulator has been well documented, the molecular mechanism fine‐tuning phosphorylation levels of response regulators is comparatively less studied. Here we combined genetic and biochemical approaches to reveal that a hybrid histidine kinase, SreS , is involved in the SreK ‐ SreR phosphotransfer process to control salt stress response in the bacterium X anthomonas campestris . The N ‐terminal receiver domain of SreS acts as a phosphate sink by competing with the response regulator SreR to accept the phosphoryl group from the latter's cognate histidine kinase SreK . This regulatory process is critical for bacterial survival because the dephosphorylated SreR protein participates in activating one of the tandem promoters ( P 2) at the 5′ end of the sreK ‐ sreR ‐ sreS ‐ hppK operon, and then modulates a transcriptional surge of the stress‐responsive gene hppK , which is required for folic acid synthesis. Therefore, our study dissects the biochemical process of a positive feedback loop in which a ‘three‐component’ signalling system fine‐tunes expression kinetics of downstream genes.

Systemic Evaluation of Hypoxic-Ischemic Brain Injury in Neonatal Rats - Ai-Hua Zhu; Yan-Rong Hu; Wei Liu; Feng Gao; Jian-Xin Li; Li-Hui Zhao; Gang Chen (Cell Biochemistry and Biophysics, 2014)

RETRACTED ARTICLE: Construction of pancreatic cancer double-factor regulatory network based on chip data on the transcriptional level - Li-Li Zhao; Tong Zhang; Bing-Rong Liu; Tie-Fu Liu; Na Tao; Li-Wei Zhuang (Molecular Biology Reports, 2014)

High-level soluble expression of the hemA gene from Rhodobacter capsulatus and comparative study of its enzymatic properties - Jia-wei Lou; Li Zhu; Mian-bin Wu; Li-rong Yang; Jian-ping Lin; Pei-lin Cen (Journal of Zhejiang University-SCIENCE B, 2014)

Effects of land cover on soil organic carbon stock in a karst landscape with discontinuous soil distribution - Xiang-bi Chen; Hua Zheng; Wei Zhang; Xun-yang He; Lei Li; Jin-shui Wu; Dao-you Huang; Yi-rong Su (Journal of Mountain Science, 2014)

Cloning and identification of a novel thyroid hormone receptor β isoform expressed in the pituitary gland - Rong-Lan Zhao; Bei Sun; Ying Liu; Jing-Hua Li; Wei-Li Xiong; Dong-Chun Liang; Gang Guo; Ai-Jun Zuo; Jing-Yu Zhang (Molecular and Cellular Biochemistry, 2014)

Cloning and expression analysis of a novel high-mobility group box 2 homologue from Lampetra japonica - Pang Yue; Xiao Rong; Xue Zhuang; Huang Jin Sha; Jin Min Li; Liu Xin; Qing Wei Li (Fish Physiology and Biochemistry, 2014)

Age and composition of the Rebang Co and Julu ophiolites, central Tibet: implications for the evolution of the Bangong Meso-Tethys - Wei-Liang Liu; Bin Xia; Yun Zhong; Jian-Xin Cai; Jian-Feng Li; Hong-Fei Liu; Zhou-Rong Cai; Zhi-Lei Sun (International Geology Review, 2014)

An improved embryo-rescue protocol for hybrid progeny from seedless Vitis vinifera grapes × wild Chinese Vitis species - Gui Rong Li; Wei Ji; Gang Wang; Jian Xia Zhang; Yue Jin Wang (In Vitro Cellular & Developmental Biology - Plant, 2014)

Use of motor abundance in old adults in the regulation of a narrow-based stance - Wei-Li Hsu; Kwan-Hwa Lin; Rong-Sen Yang; Chih-Hsiu Cheng (European Journal of Applied Physiology, 2014)

Co-expression of the Arabidopsis SOS genes enhances salt tolerance in transgenic tall fescue (Festuca arundinacea Schreb.) - Dong-Mei Ma; Wei-Rong Xu; Hui-Wen Li; Feng-Xia Jin; Ling-Na Guo; Jing Wang; Hong-Jun Dai; Xing Xu (Protoplasma, 2014)

Genomic comparison of Salmonella typhimurium DT104 with non-DT104 strains - Er-Ying Zhao; Hong-Xia Bao; Le Tang; Qing-Hua Zou; Wei-Qiao Liu; Da-Ling Zhu; Jessica Chin; Ying-Ying Dong; Yong-Guo Li; Feng-Lin Cao; Cornelis Poppe; Kenneth E. Sanderson; et al. (Molecular Genetics and Genomics, 2013)

Beta Amyloid Peptide (25-35) Leading to Inflammation Through Toll-Like Receptors and the Anti-inflammatory Effect of Genistein in BV-2 Cells - Huan-Ling Yu; Xiao-Ying Li; Xin Zhou; Lin-Hong Yuan; Wei-Wei Ma; Yuan-Di Xi; Xia Zhao; Jian Wu; Rong Xiao (Journal of Molecular Neuroscience, 2013)

Identification and characterization of Pestalotiopsis spp. causing twig blight disease of bayberry (Myrica rubra Sieb. & Zucc) in China - Hai-Ying Ren; Gang Li; Xing-Jiang Qi; Li Fang; Han-Rong Wang; Ji-Guang Wei; Shaobin Zhong (European Journal of Plant Pathology, 2013)

In vitro antifungal activity of antifungalmycin 702, a new polyene macrolide antibiotic, against the rice blast fungus Magnaporthe grisea - Zhi-Qiang Xiong; Xiao-Rong Tu; Sai-Jin Wei; Lin Huang; Xun-Hang Li; Hui Lu; Guo-Quan Tu (Biotechnology Letters, 2013)

Screening of high α-arbutin producing strains and production of α-arbutin by fermentation - Chun-Qiao Liu; Li Deng; Peng Zhang; Shu-Rong Zhang; Luo Liu; Tao Xu; Fang Wang; Tian-Wei Tan (World Journal of Microbiology and Biotechnology, 2013)

Prostaglandin E2 receptor EP1 phosphorylate CREB and mediates MMP2 expression in human cholangiocarcinoma cells - Bo Sun; Rong Rong; Hai Jiang; Hai Zhang; YiPin Wang; Xiaoming Bai; Min Zhang; Juan Ma; Shukai Xia; Wei Shu; Li Zhang; Jing Leng (Molecular and Cellular Biochemistry, 2013)

Evaluation of Burma Reed as Substrate for Production of Pleurotus eryngii - Xian-lu Zeng; Jun-fang Lin; Li-qiong Guo; Rong-wei Cao; Wei-qiang Zeng (Indian Journal of Microbiology, 2013)

Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Keri Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2013)

Lipopolysaccharide-induced failure of the gut barrier is site-specific and inhibitable by growth hormone - Chao Yue; Wei Wang; Wei-Liang Tian; Qian Huang; Ri-Sheng Zhao; Yun-Zhao Zhao; Qiu-Rong Li; Jie-Shou Li (Inflammation Research, 2013)

Lyssavirus surveillance in bats of southern China’s Guangxi Province - Zhuan-Ling Lu; Wen Wang; Wei-Li Yin; Hai-Bo Tang; Yan Pan; Xiang Liang; Qi Liu; Yi Xiong; Nobuyuki Minamoto; Ting Rong Luo (Virus Genes, 2013)

Microspore embryogenesis and production of haploid and doubled haploid plants in carrot (Daucus carota L.) - Jin-Rong Li; Fei-Yun Zhuang; Cheng-Gang Ou; Hong Hu; Zhi-Wei Zhao; Ji-Hua Mao (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

Construction of multiple shRNAs expression vector that inhibits FUT1 gene expression and production of the transgenic SCNT embryos in vitro - Jian-wen Chen; Yu Zhang; Yuan-liang Zhang; Chao Wei; Xing Liu; Na-ru Zhou; Qing Jia; Yun-sheng Li; Xiao-rong Zhang; Yun-hai Zhang (Molecular Biology Reports, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Decreased PADI4 mRNA Association with Global Hypomethylation in Hepatocellular Carcinoma During HBV Exposure - Changsong Zhang; Lieying Fan; Tingting Fan; Dong Wu; Lu Gao; Yang Ling; Jing Zhu; Rong Li; Lixin Wei (Cell Biochemistry and Biophysics, 2013)

Establishment of SYBR green-based qPCR assay for rapid evaluation and quantification for anti-Hantaan virus compounds in vitro and in suckling mice - Fei Wei; Jin-lin Li; Jia-xin Ling; Liang-Jun Chen; Ning Li; Yuan-Yuan Liu; Fan Luo; Hai-Rong Xiong; Wei Hou; Zhan-Qiu Yang (Virus Genes, 2013)

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Triterpenoid saponins from the root of Anemone tomentosa - Yi Wang; Wei Kang; Liang-jian Hong; Wen-li Hai; Xiao-yang Wang; Hai-feng Tang; Xiang-rong Tian (Journal of Natural Medicines, 2013)

Nitrogen transformations and balance in constructed wetlands for slightly polluted river water treatment using different macrophytes - Haiming Wu; Jian Zhang; Rong Wei; Shuang Liang; Cong Li; Huijun Xie (Environmental Science and Pollution Research, 2013)

Advanced glycation end products promote proliferation of cardiac fibroblasts by upregulation of KCa3.1 channels - Li-Mei Zhao; Wei Zhang; Li-Ping Wang; Gui-Rong Li; Xiu-Ling Deng (Pflügers Archiv - European Journal of Physiology, 2012)

A functional polymorphism, rs28493229, in ITPKC and risk of Kawasaki disease: an integrated meta-analysis - Jiao Lou; Sanqing Xu; Li Zou; Rong Zhong; Ti Zhang; Yu Sun; Xuzai Lu; Li Liu; Chuanqi Li; Li Wang; Guanglian Xiong; Wei Wang; et al. (Molecular Biology Reports, 2012)

Use of reverse genetics to develop a novel marker porcine reproductive and respiratory syndrome virus - Tao Lin; Xiangrui Li; Huochun Yao; Zuzhang Wei; Feifei Tan; Runxia Liu; Lichang Sun; Rong Zhang; Wenliang Li; Jiaqi Lu; Guangzhi Tong; Shishan Yuan (Virus Genes, 2012)

Chromosomal distribution of a new centromeric Ty3-gypsy retrotransposon sequence in Dasypyrum and related Triticeae species - GUANG-RONG LI; CHENG LIU; PEI WEI; XIAO-JIN SONG; ZU-JUN YANG (Journal of Genetics, 2012)

Simple and rapid detection of swine hepatitis E virus by reverse transcription loop-mediated isothermal amplification - Liang-Quan Zhang; Fu-Rong Zhao; Zhi-Gang Liu; Wei-Li Kong; Heng Wang; Yun Ouyang; Huan-Bin Liang; Chao-Yi Zhang; Hai-Tao Qi; Chang-Li Huang; Si-Hu Guo; Gui-Hong Zhang (Archives of Virology, 2012)

Virgibacillus albus sp. nov., a novel moderately halophilic bacterium isolated from Lop Nur salt lake in Xinjiang province, China - Yun-Jiao Zhang; Yu Zhou; Man Ja; Rong Shi; Wei-Xun Chun-Yu; Ling-Ling Yang; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

Genetic characterization of a new subtype of Hantaan virus isolated from a hemorrhagic fever with renal syndrome (HFRS) epidemic area in Hubei Province, China - Jin-lin Li; Jia-xin Ling; Dong-ying Liu; Jing Liu; Yuan-yuan Liu; Fei Wei; Fan Luo; Wen Chen; Yi-hui Zhang; Hai-rong Xiong; Wei Hou; Zhan-qiu Yang (Archives of Virology, 2012)

Domestication and geographic origin of O ryza sativa in C hina: insights from multilocus analysis of nucleotide variation of O . sativa and O . rufipogon - Xin Wei; Wei‐Hua Qiao; You‐Tao Chen; Rong‐Sheng Wang; Li‐Rong Cao; Wan‐Xia Zhang; Nan‐Nan Yuan; Zi‐Chao Li; Han‐Lai Zeng; Qing‐Wen Yang (Molecular Ecology, 2012)
Previous studies have indicated that C hina is one of the domestication centres of A sian cultivated rice ( O ryza sativa ), and common wild rice ( O . rufipogon ) is the progenitor of O . sativa . However, the number of domestication times and the geographic origin of A sian cultivated rice in C hina are still under debate. In this study, 100 accessions of A sian cultivated rice and 111 accessions of common wild rice in C hina were selected to examine the relationship between O . sativa and O . rufipogon and thereby infer the domestication and evolution of O . sativa in C hina through sequence analyses of six gene regions, trn C ‐ycf6 in chloroplast genomes, cox3 in mitochondrial genomes and ITS , E hd1 , W axy , H d1 in nuclear genomes. The results indicated that the two subspecies of O . sativa (indica and japonica) were domesticated independently from different populations of O . rufipogon with gene flow occurring later from japonica to indica; S outhern C hina was the genetic diversity centre of O . rufipogon , and the P earl R iver basin near the T ropic of C ancer was the domestication centre of O . sativa in C hina.

Recombinant human endostatin inhibits adjuvant arthritis by down-regulating VEGF expression and suppression of TNF-α, IL-1β production - Wei Hu; Li-Juan Xia; Fei-Hu Chen; Fan-Rong Wu; Jie Tang; Cun-Zhi Chen; Sheng Jiang; Hui-Hui Chen (Inflammation Research, 2012)

Synthesis of aspirin eugenol ester and its biological activity - Jian-yong Li; Yuan-guang Yu; Qi-wen Wang; Ji-yu Zhang; Ya-jun Yang; Bing Li; Xu-zheng Zhou; Jian-rong Niu; Xiao-juan Wei; Xi-wang Liu; Zhi-qi Liu (Medicinal Chemistry Research, 2012)

Association of PDE4B polymorphisms and schizophrenia in Northwestern Han Chinese - Fanglin Guan; Chen Zhang; Shuguang Wei; Hongbo Zhang; Xiaomin Gong; Jiali Feng; Chengge Gao; Rong Su; Huanming Yang; Shengbin Li (Human Genetics, 2012)

Molecular detection of Torque teno mini virus (TTMV) in China - Caixia Zhu; Rong A; Congli Yuan; Ying Yu; Li Cui; S. D. Tang; Zhiwei Liu; Wei Zhao; Xiuguo Hua (Virus Genes, 2012)

Clinical characteristics of hepatitis B virus infection in middle school students born after the universal infant vaccination program in Shanghai, China - Wei-Ling Wang; Zhi-Jun Shu; Li-Xia Zhou; Yan-Rong Zhao (Archives of Virology, 2012)

Expansins are involved in cell growth mediated by abscisic acid and indole-3-acetic acid under drought stress in wheat - Mei-rong Zhao; Yang-yang Han; Ya-nan Feng; Feng Li; Wei Wang (Plant Cell Reports, 2012)

At-line monitoring of key parameters of nisin fermentation by near infrared spectroscopy, chemometric modeling and model improvement - Wei-Liang Guo; Yi-Ping Du; Yong-Can Zhou; Shuang Yang; Jia-Hui Lu; Hong-Yu Zhao; Yao Wang; Li-Rong Teng (World Journal of Microbiology and Biotechnology, 2012)

Decreased expression of Beclin-1 and LC3 in human lung cancer - Zi-Feng Jiang; Li-Jie Shao; Wei-Min Wang; Xue-Bo Yan; Rong-Yu Liu (Molecular Biology Reports, 2012)

Synthesis of Benzimidazoles Containing Pyrazole Group and Quantum Chemistry Calculation of Their Spectroscopic Properties and Electronic Structure - Ren Tie-gang; Cheng Hong-bin; Zhang Jing-lai; Li Wei-jie; Guo Jia; Yang Li-rong (Journal of Fluorescence, 2012)

The mediating and moderating role of personal strain and coping resource in the relationship between work stressor and quality of life among Chinese nurses - Si-Ying Wu; Huang-Yuan Li; Shu-Juan Yang; Wei Zhu; Xiao-Rong Wang (International Archives of Occupational and Environmental Health, 2012)

Increased production of succinic acid in Escherichia coli by overexpression of malate dehydrogenase - Li-ya Liang; Rong-ming Liu; Jiang-feng Ma; Ke-quan Chen; Min Jiang; Ping Wei (Biotechnology Letters, 2011)

Synthesis of novel 6-triazologlycolipids via click chemistry and their preliminary cytotoxicity assessments - Hai-Lin Zhang; Xiao-Peng He; Li Sheng; Yuan Yao; Wei Zhang; Xiao-Xin Shi; Jia Li; Guo-Rong Chen (Molecular Diversity, 2011)

Usefulness of Enhanced Power Doppler Imaging in Monitoring Acral Microcirculation in Type 2 Diabetes Mellitus and its Complications - Fang Ma; Baozhen Zhao; Huiping Zhang; Wei-Ping Li; Yuan-Yuan Liu; Yuan-Yuan Dang; Rong Wu; Le Hang Guo; Chen Lu (Cell Biochemistry and Biophysics, 2011)

Timing, Conditions, and Complications of Post-operative Conception and Pregnancy in Female Renal Transplant Recipients - Long-gen Xu; Shu Han; Yong Liu; Hong-wei Wang; Yi-rong Yang; Feng Qiu; Wan-ling Peng; Li-gong Tang (Cell Biochemistry and Biophysics, 2011)

Genome-wide analysis of OCT4 binding sites in glioblastoma cancer cells - Xue-feng Fang; Wei-yi Zhang; Na Zhao; Wei Yu; Dong Ding; Xu Hong; Li-sha Li; Hua-rong Zhang; Shu Zheng; Biao-yang Lin (Journal of Zhejiang University-SCIENCE B, 2011)

Benefits of a symbiotic association with endophytic fungi are subject to water and nutrient availability in Achnatherum sibiricum - An Zhi Ren; Xia Li; Rong Han; Li Jia Yin; Mao Ying Wei; Yu Bao Gao (Plant and Soil, 2011)

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

Cloning and functions analysis of a pyruvate dehydrogenase kinase in Brassica napus - Rong-Jun Li; Zhi-Yong Hu; Hua-Shan Zhang; Gao-Miao Zhan; Han-Zhong Wang; Wei Hua (Plant Cell Reports, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

A new bioorganic fertilizer can effectively control banana wilt by strong colonization with Bacillus subtilis N11 - Nan Zhang; Kai Wu; Xin He; Shu-qing Li; Zhen-hua Zhang; Biao Shen; Xing-ming Yang; Rui-fu Zhang; Qi-wei Huang; Qi-rong Shen (Plant and Soil, 2011)

Malignant transformation of 293 cells induced by ectopic expression of human Nanog - Yan-Li Lin; Zheng-Bin Han; Fu-Yin Xiong; Li-Yuan Tian; Xiao-Jie Wu; Shi-Wei Xue; Yan-Rong Zhou; Ji-Xian Deng; Hong-Xing Chen (Molecular and Cellular Biochemistry, 2011)

Expansin-regulated cell elongation is involved in the drought tolerance in wheat - Mei-rong Zhao; Feng Li; Ying Fang; Qiang Gao; Wei Wang (Protoplasma, 2011)

Effects of elevated CO2 levels on root morphological traits and Cd uptakes of two Lolium species under Cd stress - Yan Jia; Shi-rong Tang; Xue-hai Ju; Li-na Shu; Shu-xing Tu; Ren-wei Feng; Lorenzino Giusti (Journal of Zhejiang University-SCIENCE B, 2011)

Genistein alters caffeine exposure in healthy female volunteers - Yao Chen; Chang-Qiong Xiao; Yi-Jing He; Bi-Lian Chen; Guo Wang; Gan Zhou; Wei Zhang; Zhi-Rong Tan; Shan Cao; Li-Ping Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2011)

The Development and Stability of the Genus Bacteriodes from Human Gut Microbiota in HFA Mice Model - Jing Yuan; Benhua Zeng; Rong Niu; Huan Tang; Wenxia Li; Zhixue Zhang; Hong Wei (Current Microbiology, 2011)

Construction of a Tn5-Tagged Mutant Library of Xanthomonas oryzae pv. oryzicola as An Invaluable Resource for Functional Genomics - Hua-Song Zou; Liang Yuan; Wei Guo; Yu-Rong Li; Yi-Zhou Che; Li-Fang Zou; Gong-You Chen (Current Microbiology, 2011)

Comparison of DNA extraction methods for the PCR-single-strand-conformation polymorphism analysis of kefir - Shu-Jun Chen; Qing Wang; Jian-Rong Han; Yu Wang; Zhi-Wei Li (World Journal of Microbiology and Biotechnology, 2011)

Quantitative estimation of the shrub canopy LAI from atmosphere-corrected HJ-1 CCD data in Mu Us Sandland - Wei Chen; ChunXiang Cao; QiSheng He; HuaDong Guo; Hao Zhang; RenQiang Li; Sheng Zheng; Min Xu; MengXu Gao; Jian Zhao; Sha Li; XiLiang Ni; et al. (Science China Earth Sciences, 2010)

The pentapeptide PLNPK inhibits systemic lupus erythematosus-associated renal damage - Jun-qiang Lv; Wen Zhang; Song Wang; Lin Zhao; Rui Ma; Jin-wei Hu; Li-juan Wang; Jie Meng; Chun-lei Zhou; Gang Lin; Rong Lu; Zhi Yao (Inflammation Research, 2010)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

Allelopathic effects of root exudates from watermelon and rice plants on Fusarium oxysporum f.sp. niveum - Wen-ya Hao; Li-xuan Ren; Wei Ran; Qi-rong Shen (Plant and Soil, 2010)

Inhibition of acid-sensing ion channels in articular chondrocytes by amiloride attenuates articular cartilage destruction in rats with adjuvant arthritis - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Jian-ping Li; Cheng-Wan Li; Rui-Sheng Xu; Fan-Rong Wu; Wei Hu; Teng-Yue Zhang (Inflammation Research, 2010)

Effect of glycyrrhizin on the activity of CYP3A enzyme in humans - Jiang-Hua Tu; Yi-Jing He; Yao Chen; Lan Fan; Wei Zhang; Zhi-Rong Tan; Yuan-Fei Huang; Dong Guo; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2010)

Retrieval of Substrate Bearing Strength from Hyperspectral Imagery during the Virginia Coast Reserve (VCR’07) Multi-Sensor Campaign - Charles M. Bachmann; C. Reid Nichols; Marcos J. Montes; Rong-Rong Li; Patrick Woodward; Robert A. Fusina; Wei Chen; Vimal Mishra; Wonkook Kim; James Monty; Kevin Mcilhany; Ken Kessler; et al. (Marine Geodesy, 2010)

Differential expression of TRPC channels in the left ventricle of spontaneously hypertensive rats - Fang-fang Liu; Zhi-yong Ma; Duo-ling Li; Jin-bo Feng; Kai Zhang; Rong Wang; Wei Zhang; Li Li; Yun Zhang (Molecular Biology Reports, 2010)

Acid-sensing ion channel 1a mediates acid-induced increases in intracellular calcium in rat articular chondrocytes - Feng-Lai Yuan; Fei-Hu Chen; Wei-Guo Lu; Xia Li; Fan-Rong Wu; Jian-Ping Li; Cheng-Wan Li; Yu Wang; Teng-Yue Zhang; Wei Hu (Molecular and Cellular Biochemistry, 2010)

Improvement of heat and drought photosynthetic tolerance in wheat by overaccumulation of glycinebetaine - Gui-Ping Wang; Zhen Hui; Feng Li; Mei-Rong Zhao; Jin Zhang; Wei Wang (Plant Biotechnology Reports, 2010)

The phylogeny analysis of MyoG gene in different pig breeds - Li Zhu; Xue-Wei Li; Su-Rong Shuai; Ming-Zhou Li; Lei Chen; Yi-Ren Gu; Kai Zhang (Interdisciplinary Sciences: Computational Life Sciences, 2010)

Isolation and characterization of an abamectin-degrading Burkholderia cepacia-like GB-01 strain - Shinawar Waseem Ali; Rong Li; Wei-you Zhou; Ji-quan Sun; Peng Guo; Ji-ping Ma; Shun-peng Li (Biodegradation, 2010)

Expression of a bee venom phospholipase A2 from Apis cerana cerana in the baculovirus-insect cell - Li-rong Shen; Mei-hui Ding; Li-wen Zhang; Wei-guang Zhang; Liang Liu; Duo Li (Journal of Zhejiang University-SCIENCE B, 2010)

Simvastatin attenuates TNF-α-induced growth inhibition and apoptosis in murine osteoblastic MC3T3-E1 cells - Yun-mei Yang; Wei-dong Huang; Qiang-min Xie; Zhe-rong Xu; Qi-jiang Zhao; Xi-mei Wu; Fen-fen Li; Xin-wei Dong (Inflammation Research, 2010)

CYP3A4*1G genetic polymorphism influences CYP3A activity and response to fentanyl in Chinese gynecologic patients - Wei Zhang; Yan-Zi Chang; Quan-Cheng Kan; Li-Rong Zhang; Zhi-Song Li; Hui Lu; Zhong-Yu Wang; Qin-Jun Chu; Jie Zhang (European Journal of Clinical Pharmacology, 2010)

Clear and independent associations of several HLA-DRB1 alleles with differential antibody responses to hepatitis B vaccination in youth - Yufeng Li; Rong Ni; Wei Song; Wenshuo Shao; Sadeep Shrestha; Sushma Ahmad; Coleen K. Cunningham; Patricia M. Flynn; Bill G. Kapogiannis; Craig M. Wilson; Jianming Tang (Human Genetics, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Dong Niu; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Niu Dong; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Detection of plasmid-mediated IMP-1 metallo-β-lactamase and quinolone resistance determinants in an ertapenem-resistant Enterobacter cloacae isolate - Li-rong Chen; Hong-wei Zhou; Jia-chang Cai; Rong Zhang; Gong-xiang Chen (Journal of Zhejiang University-SCIENCE B, 2009)

Respiratory face mask: a novel and cost-effective device for use during the application of myocardial ischemia in rats - Yuan Yuan; Fei Li; Yue-min Wang; Rong-qing Zhang; Li-ping Wei; Hai-chang Wang (Journal of Zhejiang University-SCIENCE B, 2009)

Induction of cytochrome P450 2B6 activity by the herbal medicine baicalin as measured by bupropion hydroxylation - Lan Fan; Jin-Chao Wang; Feng Jiang; Zhi-Rong Tan; Yao Chen; Qing Li; Wei Zhang; Guo Wang; He-Ping Lei; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

An investigation on the polymorphisms of two DNA repair genes and susceptibility to ESCC and GCA of high-incidence region in northern China - Na Wang; Xiu-juan Dong; Rong-miao Zhou; Wei Guo; Xiao-juan Zhang; Yan Li (Molecular Biology Reports, 2009)

Effect of Temperature on Iron Leaching from Bauxite Residue by Sulfuric Acid - Zhi-Rong Liu; Kai Zeng; Wei Zhao; Ying Li (Bulletin of Environmental Contamination and Toxicology, 2009)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Depressive-like behavior in mice recently recovered from motor disorders after 3-nitropropionic acid intoxication - Xiao-Min Li; Bing-Gen Zhu; Sha Ma; Wei Zhou; Zheng Wei; Yu-Xiang Zheng; Xu-Dong Zhao; Rong-Shen Zhu (Neuroscience Bulletin, 2008)

Androgen receptor: a new player associated with apoptosis and proliferation of pancreatic beta-cell in type 1 diabetes mellitus - Ru-Jiang Li; Shu-Dong Qiu; Hai-Xu Wang; Hong Tian; Li-Rong Wang; Yong-Wei Huo (Apoptosis, 2008)

Effects and complications of placement of motility coupling post in porous polyethylene orbital implants - Hong-guang Cui; Rong-rong Hu; Hui-yan Li; Wei Han (Journal of Zhejiang University-SCIENCE B, 2008)

Four new aromatic allenic ethers from the fungus Xylaria sp. No. 2508 - San-Yong Wang; Zhong-Liang Xu; Wei-Wei Mao; Zhi-Gang She; Ni Tan; Chun-Rong Li; Yong-Cheng Lin (Natural Product Research, 2008)

A preliminary study on the teratogenesis of dexamethasone and the preventive effect of vitamin B12 on murine embryonic palatal shelf fusion in vitro - Sheng-jun Lu; Wei He; Bing Shi; Tian Meng; Xiao-yu Li; Yu-rong Liu (Journal of Zhejiang University-SCIENCE B, 2008)

High-Level Secretion of a Chimeric Thermostable Lichenase from Bacillus subtilis by Screening of Site-Mutated Signal Peptides with Structural Alterations - Ling-lin Fu; Zi-rong Xu; Jiang-bing Shuai; Chun-xia Hu; Wei Dai; Wei-fen Li (Current Microbiology, 2008)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Molecular cloning of Brassica napus TRANSPARENT TESTA 2 gene family encoding potential MYB regulatory proteins of proanthocyanidin biosynthesis - Yun-Liang Wei; Jia-Na Li; Jun Lu; Zhang-Lin Tang; Dong-Chun Pu; You-Rong Chai (Molecular Biology Reports, 2007)

Timing and duration of supergene mineralization at the Xinrong manganese deposit, western Guangdong Province, South China: cryptomelane 40Ar/39Ar dating - Jian-Wei Li; Paulo Vasconcelos; Wei Zhang; Xiao-Dong Deng; Nurdan Duzgoren-Aydin; Dai-Rong Yan; Jian-Qiang Zhang; Ming-An Hu (Mineralium Deposita, 2007)

Passage number affects the pluripotency of mouse embryonic stem cells as judged by tetraploid embryo aggregation - Xiang-yun Li; Qing Jia; Ke-qian Di; Shu-min Gao; Xiao-hui Wen; Rong-yan Zhou; Wei Wei; Li-ze Wang (Cell and Tissue Research, 2007)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

Identification of differentially expressed genes in seeds of two near-isogenic Brassica napus lines with different oil content - Rong-Jun Li; Han-Zhong Wang; Han Mao; Ying-Tang Lu; Wei Hua (Planta, 2006)

Crop yield, nitrogen uptake and nitrate-nitrogen accumulation in soil as affected by 23 annual applications of fertilizer and manure in the rainfed region of Northwestern China - Sheng-Mao Yang; S. S. Malhi; Jian-Rong Song; You-Cai Xiong; Wei-Yun Yue; Li Li Lu; Jian-Guo Wang; Tian-Wen Guo (Nutrient Cycling in Agroecosystems, 2006)

Changes in Soil Microbial Community Associated with Invasion of the Exotic Weed, Mikania micrantha H.B.K - Wei-hua Li; Cong-bang Zhang; Hong-bo Jiang; Guo-rong Xin; Zhong-yi Yang (Plant and Soil, 2006)

Evaluation of caspase-dependent apoptosis during fluoride-induced liver lesion in pigs - Xiu An Zhan; Min Wang; Zi Rong Xu; Wei Fen Li; Jian Xin Li (Archives of Toxicology, 2006)

Novel CACNA1S mutation causes autosomal dominant hypokalemic periodic paralysis in a Chinese family - Qiufen Wang; Mugen Liu; Chunsheng Xu; Zhaohui Tang; Yuhua Liao; Rong Du; Wei Li; Xiaoyan Wu; Xu Wang; Ping Liu; Xianqin Zhang; Jianfang Zhu; et al. (Journal of Molecular Medicine, 2005)

Ile118Val genetic polymorphism of CYP3A4 and its effects on lipid-lowering efficacy of simvastatin in Chinese hyperlipidemic patients - An Wang; Bang-Ning Yu; Chen-Hui Luo; Zhi-Rong Tan; Gan Zhou; Lian-Sheng Wang; Wei Zhang; Zhi Li; Jie Liu; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2005)

Direct plantlet regeneration from the tuber of Stachys sieboldii - Wei Li; Huan-Huan Gao; Rong Lu; Guang-Qing Guo; Guo-Chang Zheng (Plant Cell, Tissue and Organ Culture (PCTOC), 2002)

Activation of Signal Transduction Kinases by Tamoxifen - Jauh-Lin Duh; Rong Yu; Jie-Jun Jiao; George A. Matwyshyn; Wei Li; Tse-Hua Tan; A.-N. Tony Kong (Pharmaceutical Research, 1997)